Herbicolin A, an antifungal lipopeptide produced by Pantoea agglomerans APC 4211 is a promising biocontrol agent against food spoilage fungi - Eleni Kamilari; Paula M. O'Connor; Jerry Reen; Promi Das; Aiswariya Deliephan; Daragh Hill; Oxana Fursenko; Jonathan Weise; Ay Sha Naomi Moore; Colin Hill; Catherine Stanton; Paul R. Ross (International Journal of Food Microbiology, 2026)

Application of QPS- and GRAS-status microorganisms and bacteriocins for sustainable food preservation - Eleni Kamilari; Catherine Stanton; Colin Hill; R. Paul Ross (International Journal of Food Microbiology, 2026)

Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Habitat Selection and Intrapopulation Spatial Segregation in an Arctic Top Predator at the Southern Limit of Its Range - Tyler R. Ross; Gregory W. Thiemann; Martyn E. Obbard; Kevin R. Middel; Joseph M. Northrup (Global Change Biology, 2026)
Accounting for spatial structure within populations is critical for defining appropriate scales of management, particularly in the Arctic, where habitats of ice‐dependent species such as the polar bear ( Ursus maritimus ) are being transformed at an accelerated rate. We examined broad‐scale patterns of space use and finer‐scale habitat selection by adult female polar bears in James Bay, located at the southernmost extent of the species' global range. Using satellite telemetry data collected during the annual on‐ice period from 2012 to 2017, we estimated individual‐ and population‐level utilization distributions (UDs) and applied hierarchical clustering to assess whether individuals formed distinct spatial groups based on the degree of UD overlap. We also fit step‐selection functions (SSFs) to evaluate selection for sea‐ice concentration, ocean depth, and distance to coast. Fifteen bears with data spanning at least one complete on‐ice period had individual 95% UDs averaging 74,770 km 2 (SE = 11,663). Results of hierarchical clustering identified two distinct spatial groups: three “resident” bears remained within southern James Bay, whereas 12 “non‐resident” bears had larger UDs extending into Hudson Bay. Overlap between groups remained near zero throughout winter, including during the breeding season. Step‐selection analyses, which included an additional four bears ( n total = 19), indicated consistent positive selection for high sea‐ice concentration, with individual variation in selection strength. For non‐resident bears, selection for distance to coast and ocean depth varied seasonally, with bears selecting areas farther from the Ontario coast during freeze‐up, closer to the coast during April–May, and deeper offshore areas during breakup. Together with previous genetic evidence, our results suggest resident southern James Bay bears represent a spatially structured component of the broader subpopulation that warrants continued monitoring and explicit consideration in future harvest‐risk assessments and conservation planning, particularly as sea‐ice loss continues to alter habitat availability.

Bifidobacterium longum subsp. infantis CCFM1445 Promotes Bone Growth in Growing Mice Via Modulating Gut Microbiota and Arginine Metabolism Pathway - Mingjie Li; Bowen Li; Haiqin Chen; Qixiao Zhai; Catherine Stanton; R. Paul Ross; Jianxin Zhao; Wei Chen; Bo Yang (Probiotics and Antimicrobial Proteins, 2026)

Stalled assembly of supercontinent Columbia: Evidence from Palaeoproterozoic (1864 Ma) intraplate ferrosyenite magmatism of the Cuddapah Intrusive Province, Eastern Dharwar Craton, India - K. Saikrishna; R. Mallikarjuna Reddy; Xu Liu; Xianqing Jing; Ross N. Mitchell (Gondwana Research, 2026)

Drought conditioning influences conifer seedling height but not survival three growing seasons after planting - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; David L.R. Affleck; Andrew J. Larson (Forest Ecology and Management, 2026)

Corrigendum to ‘Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control’ [Aquaculture Volume 622 15 July 2026 744046] - Jessica Hintzsche; Lorenzo Vincenzo Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

EPR characterization of a metal-binding site in RquA - Rachelle K. Stowell; Trilok Neupane; Kristian C. Mankiller; Tanner L. Manning; Lily N. Boercker; Charlotte V. DiGaetano; Lauren R. Gotshall; Maegan N. Burke; Andrew Ozarowski; Eric E. Ross; David N. Langelaan; Jennifer N. Shepherd; et al. (JBIC Journal of Biological Inorganic Chemistry, 2026)

Ecological influences on biofouling associated with salmon aquaculture pen netting - R. Cappaert; D. Moreno; D.J. Ross; C. Johnston; C.A. White (Aquaculture, 2026)

Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control - Jessica Hintzsche; Lorenzo V. Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly S. Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

Effect of recombinant equine chorionic gonadotropin on fertility of lactating dairy cows - P.D. Carvalho; A.H. Souza; L. Cattaneo; R. Moreira; E.O. Batista; F. Randi; R.S. Belli; C.E.C. Consentini; P.J. Ross; G.A. Bó; P.S. Baruselli; V.G. Santos (Theriogenology, 2026)

Metabolic, structural, and ecological foundations underlying the health benefits of HMO-adapting Bifidobacterium longum subsp. infantis - Zheng Huang; Mengfan Ding; Jianxin Zhao; Catherine Stanton; R. Paul Ross; Wei Chen; Bo Yang (Trends in Food Science & Technology, 2026)

Prenatal exposure to gas stoves, mold, and water damage: Associations with gestational duration and fetal growth in the ECHO cohort - Jiwon Oh; Lesliam Quirós-Alcalá; Mohamad Burjak; Anna J. Ross; Lisa A. Croen; Aisha S. Dickerson; Assiamira Ferrara; Rima Habre; Irva Hertz-Picciotto; Margaret R. Karagas; Christine T. Loftus; Rebecca J. Schmidt; et al. (Environmental Pollution, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Calibration of the species threat abatement and restoration metric's threat abatement component in a Costa Rican landscape - Louise Mair; Thomas M. Brooks; Randall R. Jimenez; Nicholas B. W. Macfarlance; Tony Nello; Antonin Vergez; Leon Bennun; Florence Curet; Annie Dakmejian; Edward Ellis; Melibea Gallo; Philip J. K. McGowan; et al. (Conservation Biology, 2026)
Achieving global conservation policy goals requires the ability to set and measure progress toward science‐based targets for biodiversity. The species threat abatement and restoration (STAR) metric was developed to enable actors to set science‐based targets for species. STAR scores quantify the potential contribution of actions to abate threats and restore habitat to reduce species extinction risk in a particular place and can be aggregated and disaggregated among species, threats, and areas of interest. Estimated STAR scores are based on data from the International Union for Conservation of Nature Red List and provide initial information on the species and threats expected to be present in an area. Operationalization of the metric requires verification of the presence of species and the presence and severity of threats in the area to inform calculation of a calibration STAR score. We applied a pilot calibration process for the threat abatement component of STAR (STAR T ) in the San Jose northern subcatchments landscape in Costa Rica. We used specialist knowledge and geospatial analyses of habitat loss to determine the species present and the intensity of threats affecting them in the landscape. Calibration yielded a more even distribution of scores among threats than was apparent from estimated STAR T and identified that reducing the threat from livestock farming and ranching had the greatest potential to reduce species extirpation risk. Calibration also showed that there is an opportunity to prevent the extinction of a critically endangered endemic amphibian, but the species’ presence requires confirmation. The pilot demonstrated how specialist knowledge and geospatial analyses can be combined during calibration to produce a calibrated STAR T score capable of informing science‐based targets for species conservation. Our calibration process can be applied to other areas.

Identifying potential invasion hotspots for non-native fluvial fishes throughout the conterminous United States - Hao Yu; Arthur R. Cooper; Jared A. Ross; Wesley M. Daniel; Jack E. Taylor; Alina Sargsyan; Dana M. Infante (Biological Invasions, 2026)
Identifying habitats that non-native fluvial fishes are likely to invade provides information for proactive management, conservation planning, and understanding the ecology of biological invasions. We identified streams in the conterminous United States with high invasion risk from 20 non-native fluvial fish species. Specifically, we (1) developed habitat suitability models for each species using nine natural and six anthropogenic predictors within nine large ecoregions, identifying the potential invasion hotspots; (2) evaluated the relative importance of natural and anthropogenic predictors for each species; and (3) assessed potential invasion risk to protected stream habitats. Predicted invasion hotspots included much of Florida, coastal regions of Texas and Louisiana, and areas surrounding major metropolitan centers such as Chicago, New York, and Phoenix. Model predictions indicate that goldfish ( Carassius auratus ), pirapitinga ( Piaractus brachypomus ), and pond loach ( Misgurnus anguillicaudatus ) could occupy extensive suitable habitats across the conterminous United States. The most influential natural predictor across species was network catchment area (a surrogate for stream size), while the most influential anthropogenic predictor was human population density. Goldfish were predicted to be present in protected areas across all nine ecoregions, highlighting their high invasion potential. Collectively, our results provide critical information on regions vulnerable to invasion and the species most likely to become established and identify areas at risk of invasion within protected landscapes.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Systematic review of wild birds as reservoirs of antimicrobial resistance: Implications for roof-harvested rainwater safety - Mira Cooper-Beknazarova; Ben van den Akker; Barbara Drigo; Kirstin Ross; Harriet Whiley; Craig R. Williams (International Journal of Hygiene and Environmental Health, 2026)

Early-life bovine colostrum supplementation alleviates atopic dermatitis through gut microbiota remodeling and enhanced immune regulation - Siya Wu; Qing Zhang; Zheng Huang; Shumao Cui; Catherine Stanton; R. Paul Ross; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Mermaids in pools: Ex-situ conservation as a cornerstone for sirenian management worldwide - D.N. Castelblanco-Martínez; E.A. Ramos; A. Alvarez-Aleman; L. von Fersen; R.S. Amaral; F.L.N. Attademo; J.C.G. Borges; L.J. Cabrias-Contreras; D. Caicedo-Herrera; T. Calleson; V.L. Carvalho; A. Dávila-Peñaloza; et al. (Journal for Nature Conservation, 2026)

Pixel-level quantification of biofouling taxa associated with salmon aquaculture infrastructure using deep learning - R. Cappaert; W. Yang; D.J. Ross; C. Johnston; C. MacLeod; C.A. White (Aquacultural Engineering, 2026)

Drained Agricultural Peatlands as Persistent Carbon Sources: Implications for Carbon and Water Use Intensity in Food Production - Brenda D'Acunha; Chris D. Evans; Alanna Bodo; Hollie Cooper; Dafydd Egryn Crabtree; Alexander Cumming; Jennifer M. Rhymes; Daniel Rylett; Rebekka R. E. Artz; Ross Morrison (Global Change Biology, 2026)
Peatlands have the capacity to sequester large quantities of carbon and can therefore play an important role in climate change mitigation. However, anthropogenic activities alter their hydrological regimes, converting them from net CO 2 sinks into net sources. In England and elsewhere, lowland peatlands have been heavily drained and modified for agricultural land use, resulting in some of the most productive farmland in the UK. Estimates of CO 2 emissions and water use from the area are scarce, but these data are required to understand the consequences of maintaining agricultural output whilst simultaneously reducing GHG emissions. In this paper, we compiled a uniquely comprehensive dataset of CO 2 and H 2 O flux measurements from flux towers on cropped lowland peat, and coupled this with crop calorific values to estimate carbon and water use intensities of food production on peat. Our results showed that croplands on peat emitted 23.1 ± 10.4 ton CO 2 ha −1 y −1 (mean ± SD). Sites with peat depth > 40 cm emitted 25.1 ± 9.2 ton CO 2 ha −1 , while wasted peat sites emitted 11.8 ± 4.8 ton CO 2 ha −1 . Effective water table depth and organic carbon content were the main drivers of variation in annual net ecosystem production and ecosystem respiration across sites; crop type partly followed these gradients, so may not be a direct driver of variations in emissions. ET was less variable across site‐years and depended on the phenology of crop production. When considering CO 2 emissions and water use per calorie produced, lettuce and celery rotations were the most C and water use intensive crops, with values an order of magnitude larger than cereal crops. Overall, this paper highlights the scale of CO 2 emissions from managed peatlands and the importance of balancing GHG emissions and water use with ongoing food production from these economically important areas.

Top‐Down and Bottom‐Up Processes Jointly Explain Mesopredator Movement and Foraging Ecology - Katie R. N. Florko; Tyler R. Ross; Steven H. Ferguson; Joseph M. Northrup; Martyn E. Obbard; Gregory W. Thiemann; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2026)
Prey availability and predation risk drive animal distribution, movement, and foraging ecology, yet studies rarely analyse multiple predator–prey levels together. Understanding how predators optimise risk–reward tradeoffs is important for species conservation and management, especially in systems facing extreme ecosystem change. We examined how top‐down (modelled polar bear habitat selection) and bottom‐up (modelled fish diversity) processes influence the habitat selection, movement, and foraging behaviour of 26 ringed seals (greater than 70,000 dives and 10,000 locations over 877 seal days). Our results suggest that polar bears spatially restrict seal movements and reduce the time seals spend foraging, potentially decreasing foraging success. Seals were more likely to be present and dive longer in high‐predation risk areas when prey diversity was high. Further, seal habitat selection models excluding polar bears overestimated core space use. These findings illustrate the dynamic tradeoffs that mesopredators make when balancing predation risk and resource acquisition.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Anhydrous lithic clasts in four CM2 carbonaceous chondrites derived from a thermally metamorphosed planetesimal with CM and CY affinities - Martin R. Lee; Sammy Griffin; Ross Findlay; Xuchao Zhao; Ian A. Franchi (Geochimica et Cosmochimica Acta, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Taphonomy of soft-tissue preservation in ferricrete at the McGraths Flat Lagerstätte - Tara Djokic; Patrick M. Smith; Jeff R. Havig; Michael Frese; Paulo Vasconcelos; Jochen Brocks; Michael Ellwood; David J. Cantrill; Dayna McGeeney; Ross Pogson; Chris Ryan; Yu Wang; et al. (Gondwana Research, 2026)

Sigma-2 Receptor Antagonism Enhances the Neuroprotective Effects of Pridopidine, a Sigma-1 Receptor Agonist, in Huntington’s Disease - Jing Jin; Randal Hand; May Meltzer; Carmen Abate; Michal Geva; Michael R. Hayden; Christopher A. Ross (Molecular Neurobiology, 2026)

Commercial biostimulant seed treatments showed minimal impact on soybean seed yield across the United States - Fabiano Colet; Spyridon Mourtzinis; Rachel A. Vann; Seth Naeve; Shawn P. Conley; Emma G. Matcham; Andre Borja Reis; Hans Kandel; David Moseley; Michael Plumblee; Eros Francisco; Giovani Preza Fontes; et al. (Field Crops Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Subcellular localization of the P2X4 receptor in sensory hair cells of Wistar rat cochlea - Ziyin Huang; Jacqueline M. Ross; Shelly C. Y. Lin; Prakansha N. Kumar; Kevin Roy; Srdjan M. Vlajkovic; Peter R. Thorne; Haruna Suzuki-Kerr (Histochemistry and Cell Biology, 2025)
Our sense of hearing starts in the inner ear organ, the cochlea, which contains two types of auditory hair cells for signal transduction. Earlier research showed that the complex cochlear physiology is regulated in part by purinergic signalling through activation of purine-mediated P2X, P2Y and adenosine receptors expressed in the cochlea. This study aims to extend our knowledge of purinergic signalling in the cochlea by comprehensively characterising the expression of the P2X4 receptor subtype. Wistar rat cochlea (embryonic day 20.5–6 weeks, both sexes) were collected, and the P2X4 expression was examined by immunohistochemistry. Robust P2X4 expression was found in the organ of Corti (OoC) in the inner hair cells (IHCs) and outer hair cells (OHCs), confirmed by double-labelling with hair cells (HCs) marker myosin VIIa. In IHCs, a robust cytoplasmic P2X4 expression occurred throughout the cell body, with the most intense signal at the medial side. In OHCs, P2X4 formed puncta near the apical and basal ends of the cell body. Using markers for subcellular organelles, P2X4 immunoreactivity was predominately associated with the trans-Golgi network apparatus and early endosomes in IHC and with early endosomes and lysosomes in OHC in the mature cochlea. In both cell types, some co-localisation of P2X4 with presynaptic marker was also observed. Taken together, these observations suggest unique roles for P2X4 in mature IHCs and OHCs as a purinergic receptor subtype responsible for the homeostatic regulation of hair cells and auditory sensory transduction.

Development of a High-throughput Morphological Assay for Evaluating Mesenchymal Stromal Cell-derived Extracellular Vesicle Modulation of Brain Pericyte Secretory Phenotype - Courtney E. Campagna; Andrew M. Larey; Kanupriya R. Daga; Morgan Roos; Sneha Ghosh; Neil Grimsey; Jin Han; Ross A. Marklein (Stem Cell Reviews and Reports, 2025)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are a promising therapeutic tool for treating many neurodegenerative diseases. Neuroinflammation plays a major role in many of these conditions through an orchestration of interdependent processes that lead to the breakdown of the blood-brain barrier (BBB), infiltration of immune cells and neuronal death. MSC-EVs have shown preliminary evidence of modulating neuroinflammation, but their mechanisms of action are still unknown. Therefore, we explored the potential of MSC-EVs in modulating brain pericytes, a cell type that plays a critical role in BBB maintenance but has not been investigated as a therapeutic target for MSC-EVs. Brain pericytes are multifaceted cells that can modulate neuroinflammation through their involvement in BBB homeostasis, as well as the innate and adaptive immune response. Pericyte morphology has been shown to change in response to inflammatory stimuli in vivo, hence, we used this behavior to develop a quantitative morphological profiling approach to assess the immunomodulatory function of MSC-EVs in a high-throughput, low-cost manner. Using this assay, we were able to demonstrate that MSC-EVs manufactured under various conditions (2D, 3D, and in response to cytokine priming) could induce distinct pericyte morphological responses indicative of changes in secretion of chemokines and cytokines relevant to neuroinflammation.

Morphological and physiological response of conifer seedlings to drought conditioning - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; Alex Goke; Cara R. Nelson; David L. R. Affleck; Andrew J. Larson (New Forests, 2025)

Abandoned fields show higher insectivorous Bat species and functional diversity than forest fragments in a communal land area of the Eastern Cape, South Africa - Khia R. van der Meulen; Leigh R. Richards; Ross T. Shackleton; Michael I. Cherry (Biodiversity and Conservation, 2025)
Deagrarianisation is a global phenomenon with high potential for both carbon sequestration and biodiversity conservation. Work on this topic has focused on plant succession and associated plant diversity, but few studies have considered faunal communities, particularly in Africa. We used passive acoustic monitoring to record insectivorous bat communities within forest fragments and former fields under communal land tenure in the Transkei region (Eastern Cape Province) of South Africa. Insectivorous bat diversity in fields, abandoned in the 1960s to 1980s, resembling late stages of succession, were compared to fragments of Transkei Coastal Scarp Forest embedded within the landscape. We found that former fields hosted 14 species from 11 genera, comprising greater species richness, activity, Shannon-Weiner diversity, and functional diversity, irrespective of age, compared to forest fragments, which hosted nine species from seven genera. Furthermore, former fields exhibited comparable species richness to, and higher functional diversity than, three large neighbouring intact Transkei Scarp forests. Interestingly, the time since cultivation had ceased (35—64 years ago) had no significant effect on species and functional diversity. Former fields exhibited extensive invasion by Lantana camara (an alien shrub), and the indigenous pioneer tree Vachellia karoo , but nonetheless these landscapes have conservation value as they are diverse in both terms of insectivorous bat species and function. Mechanisms to enhance both biodiversity conservation; and the utility of the land for impoverished local communities, should be considered for former fields in tandem with forest patches, which remain important for bat roosting and foraging ecology, especially for specialist species.

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Magma fragmentation and tephra deposition from a small-volume phreatomagmatic eruption: Blue Lake crater, Oregon, USA - Sophia Leiter; Pierre-Simon Ross; Emily R. Johnson (Bulletin of Volcanology, 2025)

100 Years of Penaeid Domestication and Meta-Analysis of Breeding Traits - Shengjie Ren; José M. Yáñez; Ricardo Perez-Enriquez; Morten Rye; Ross D. Houston; David A. Hurwood; Jose R. Gonzalez-Galaviz; Marcela Salazar; Adriana Max-Aguilar; Nicholas M. Wade; Dean R. Jerry (Reviews in Fisheries Science & Aquaculture, 2025)

The effect of pregnancy, heat stress and altrenogest supplementation on the porcine mid-luteal phase corpus luteum proteome - R. Blythe Schultz; Malavika K. Adur; Zoë E. Kiefer; Jamie M. Studer; Katie L. Bidne; Matthew R. Romoser; Lance H. Baumgard; Aileen F. Keating; Jason W. Ross (Theriogenology, 2025)

Stream Chemistry After Colorado’s Largest Wildfire: Solute-Specific Responses to Ash and Rainstorms - Charles C. Rhoades; Timothy S. Fegel; Allison E. Rhea; Jared Heath; Sam Struthers; Katie Willi; Matthew R. V. Ross (Ecosystems, 2025)

Flip or flop? Behavioral response to stranding in fish representing six teleost orders - Michael R. Minicozzi; Shannon Hansen; Michael Akland; Ana Braga; Owen Kyle; C. Loren Buck; Miriam Ashley-Ross; Alice C. Gibb (Zoology, 2025)

A tool to support food substance safety evaluations in the United States - Christine M. Crincoli; Jennifer L.G. van de Ligt; Alex K. Eapen; Anthony T. Pavel; Paul R. Hanlon; Kelly Almond-Abbate; Esther Haugabrooks; Jason Hlywka; Vivian Lu; Fleur de Mooij; Margaret Pandis; Ross Peterson; et al. (Regulatory Toxicology and Pharmacology, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Long‑term monitoring of mercury in Vermont’s forest soils: trends over 20 years in near–surface horizons - Donald S. Ross; James B. Shanley; Angelica T. Quintana; Thomas R. Villars; Joshua M. Halman; Scott W. Bailey; Jennifer A. Bower (Environmental Monitoring and Assessment, 2025)

Assessing the Benefits and Challenges of Recirculating Aquaculture Systems (RAS) for Atlantic Salmon Production - A. Ross Brown; Rod W. Wilson; Charles R. Tyler (Reviews in Fisheries Science & Aquaculture, 2025)

Inferring near-surface ozone production regimes: Insights from using satellite retrievals over the contiguous US - Akanksha Singh; Allison M. Ring; Hao He; Dale J. Allen; Russell R. Dickerson; Ross J. Salawitch; Timothy P. Canty (Atmospheric Environment, 2025)

Do soil enzymes respond to silvicultural management? - Fernanda C.C. Oliveira; Allan Bacon; Thomas R. Fox; Eric J. Jokela; Michael B. Kane; Timothy A. Martin; Asko Noormets; C. Wade Ross; Jason Vogel; Daniel Markewitz (Forest Ecology and Management, 2025)

Bifidobacterium longum subsp. Infantis modulates intestinal immunity in growing mice in a strain-specific manner - Qing Zhang; Mengfan Ding; Zheng Huang; Shilong Jiang; Jianxin Zhao; Catherine Stanton; R. Paul Ross; Wei Chen; Bo Yang (Food Bioscience, 2025)

Seasonal occurrence and condition of leopard seals at an extralimital Sub-Antarctic Island - Michael D. Ross; Monica Leitner; W. Chris Oosthuizen; Marthán N. Bester; Rowan K. Jordaan; Michael D. Voysey; Everhard C. Conradie; Banele Dosi; Sean Evans; Kyle J. Lloyd; Zafar Monier; Jean Purdon; et al. (Polar Biology, 2025)
Leopard seals ( Hydrurga leptonyx ) occur mainly south of the Antarctic Polar Front, but immatures, in particular, seasonally move beyond this range during the austral winter and spring, typically under increased sea ice conditions. Extralimital occurrences of leopard seals can be observed at several sub-Antarctic islands where they haul out to rest. We present new records of leopard seal sightings at Marion Island, southern Indian Ocean, from 2006 to 2024 and discuss fluctuations in their seasonal and annual abundance (drawing on data collected since 1980) and body condition based on regular surveys. The eastern beaches at Marion Island were surveyed every 7–10 days while the western beaches were visited monthly. Observed leopard seals were photographed and given a body condition score based on the visibility of bony protrusions. From 2006 to 2024, we identified 35 presumed unique immature leopard seals between July and November, with a peak in September, all being immatures. Individuals to which we could assign body condition scores were either in good or excellent condition. This contrasted with the prevailing hypothesis that leopard seal body condition deteriorates with decreasing latitude. However, we could not determine whether this was because of an actual shift in body condition or because we used a different scoring system from other studies. We recommend adopting a standardised scoring system for visually estimating pinniped body condition and a global repository to monitor leopard seal haul-outs. As an apex predator, leopard seals may be important indicators in Antarctic and sub-Antarctic ecosystems, and monitoring changes in their distribution and body condition may indicate environmental and biological changes in these remote regions.

The effects of series elastic stiffness and cutaneous sensitivity on leg muscle reflex responses to unanticipated slips during walking - Ross E. Smith; Andrew D. Shelton; Gregory S. Sawicki; Jason R. Franz (Experimental Brain Research, 2025)
Fall-related injuries are a large public health concern for older adults (OA). Delayed or inappropriate afferent signaling may hinder detection of balance perturbation (e.g., slip), predisposing OA to falls and less efficacious corrective actions. Perturbation detection is largely governed by proprioceptive acuity, consisting of sensory information from skin and musculotendinous receptors. While skin and muscle receptors’ signaling thresholds increase with age, feedback from muscle may be uniquely delayed and diminished by age-related decreases in series elastic tissue stiffness which, during a rapid, unanticipated joint position change, could decrease the velocity of muscle stretch, delaying detection. Ultimately, the association between skin and muscle afferent signaling integrity and muscle reflex timing in response to walking balance perturbations has yet to be well established. This study evaluated the associations between plantar cutaneous sensitivity (PS) and Achilles tendon stiffness (k AT ) to muscle reflex responsiveness of ankle plantar- and dorsiflexor muscles following treadmill-induced slip perturbations in younger and OA. Compared to younger adults (YA), we found that OA had lesser PS and k AT and delayed tibialis anterior excitation onset. However, neither sensory outcome associated with muscle onset times. Later in stance, OA exhibited earlier triceps surae onsets than YA. However, only in YA did earlier gastrocnemius activity associate with greater k AT , which may indicate an ankle dominant balance recovery strategy in YA. Our results point to specific age-related changes in the timing of neuromuscular corrections to mitigate instability, which may underlie age-related differences in balance recovery efficacy and subsequent injury severity.

Exploring the consequences of introducing alternative fishing gear in an effort-limited fishery: Casita utilization in the spiny lobster, Panulirus argus, fishery in Florida - Gabrielle F. Renchen; Erica P. Ross; Thomas R. Matthews (Fisheries Research, 2025)

Seasonal monitoring of dissolved and particulate algal biotoxins in the northern Salish Sea using high performance liquid chromatography and tandem mass spectrometry - Andrew R.S. Ross; Béatrice Ip; Mackenzie Mueller; Blair Surridge; Harry Hartmann; Navinder Hundal; Nathan Matthews; Hayleigh Shannon; Melissa Hennekes; Akash Sastri; R. Ian Perry (Harmful Algae, 2025)

Hindcasting Farmed Salmon Mortality to Improve Future Health and Production Outcomes - Benjamin R. Knight; Eric A. Treml; Zac Waddington; Ross Vennell; Kate S. Hutson (Journal of Fish Diseases, 2025)
Intracellular, free‐floating and biofilm‐forming bacterial pathogens have been implicated in summer mortality of farmed Chinook salmon, Oncorhynchus tshawytscha , in New Zealand. A mortality event in 2022 in the Pelorus Sound, Marlborough, was linked to high water temperatures (> 18°C), and bacterial skin disease associated with Piscirickettsia spp. (= Rickettsia ‐like organisms) and Tenacibaculum species. To understand the progression of infection and potential drivers of the mortality, simulation of the event was conducted using a networked susceptible, infectious and recovered (SIR) model. Parameter exploration shows that reconstruction of observed mortality rates across three affected farm sites was possible. The best SIR simulations identified plausible values for key drivers of disease, which are consistent with previously estimated disease parameter ranges for Piscirickettsia salmonis . Our modelling shows the 2022 Pelorus Sound event likely experienced spread of bacterial pathogens within healthy fish populations at salmon farm sites over a 10‐week long incubation period, before elevated mortality was observed. We show evidence that vaccine use at one site likely prevented 10% higher mortality and that an alternative site for the vaccination could have further reduced mortalities. This result highlights the importance of future vaccine developments in aquaculture and the potential to improve vaccine efficacy through considered site selection.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Lactiplantibacillus plantarum CCFM8661 improves intestinal barrier function and regulates gut microbiota to alleviate enterotoxigenic Escherichia coli-induced diarrhea in mice - Yu Zhang; Chi Chen; Jianxin Zhao; Catherine Stanton; R. Paul Ross; Wei Chen; Bo Yang (Food Bioscience, 2025)

Improved estimation of aquaculture associated European introgression in a captive breeding program for endangered Atlantic salmon - Melissa K. Holborn; Tony Kess; Cameron M. Nugent; Nathalie N. Brodeur; Joke Adesola; Evan Cronmiller; Lorraine C. Hamilton; Ross A. Jones; Beth L. Lenentine; Anna MacDonnell; Meghan McBride; Amber Messmer; et al. (Conservation Genetics, 2025)
The rapid, range-wide decline in Atlantic salmon, Salmo salar , populations is well documented and has led to establishment of captive rearing and breeding programs in order to preserve populations. However, recovery potential may be limited by the inclusion of non-local genotypes, which can be both difficult to detect and quantify. In the genetically unique Inner Bay of Fundy population located in Canada, three Live Gene Bank programs have been established to aid recovery of this endangered conservation unit. Evidence of aquaculture associated non-local (i.e., European) introgression had previously been detected using small panels of microsatellite markers with limited power. Here we show how advances in sequencing and machine learning technologies can support a conservation program. We used machine learning and a corresponding panel of 301 SNPs to estimate individual-level proportions of European ancestry. To assess the degree of introgression in each program and to assess changes over time, fish were randomly selected across several program generations. Estimates were validated by genotyping a subset of individuals on a 220 K SNP array and using established admixture methods. Of the 1741 fish analyzed, only 48 were found to have European ancestry greater than the detection threshold. We found the amount of European ancestry was previously overestimated, and that very few wild-collected founder individuals had large proportions of European ancestry. Moreover, because European ancestry was introduced to Bay of Fundy populations via introgression from aquaculture escapees, these values represent the minimum amount of aquaculture introgression in these captive populations.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Bioeconomic modeling of on-growing Caribbean spiny lobster in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Sherry Larkin; Thomas R. Matthews; Erica Ross (Aquaculture, 2025)

The use of sex-sorted semen in horses - JC Samper; JC Hernandez Aviles; LF Ramirez-Agamez; CC Love; C Gonzalez-Marin; P Fleury; P Dini; A De La Fuente; R Foss; FL Campos; PJ Ross (Journal of Equine Veterinary Science, 2025)

An update on beverage consumption patterns and caffeine intakes in a representative sample of the US population - Diane C. Mitchell; Megan Trout; Ross Smith; Robyn Teplansky; Harris R. Lieberman (Food and Chemical Toxicology, 2025)

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Predicting population‐level impacts of projected climate heating on a temperate freshwater fish - Kate S. Mintram; A. Ross Brown; Samuel K. Maynard; Pernille Thorbek; Charles R. Tyler (Journal of Fish Biology, 2024)
Climate heating has the potential to drive changes in ecosystems at multiple levels of biological organization. Temperature directly affects the inherent physiology of plants and animals, resulting in changes in rates of photosynthesis and respiration, and trophic interactions. Predicting temperature‐dependent changes in physiological and trophic processes, however, is challenging because environmental conditions and ecosystem structure vary across biogeographical regions of the globe. To realistically predict the effects of projected climate heating on wildlife populations, mechanistic tools are required to incorporate the inherent physiological effects of temperature changes, as well as the associated effects on food availability within and across comparable ecosystems. Here we applied an agent‐based bioenergetics model to explore the combined effects of projected temperature increases for 2100 (1.4, 2.7, and 4.4°C), and associated changes in prey availability, on three‐spined stickleback ( Gasterosteus aculeatus ) populations representing latitudes 50, 55, and 60°N. Our results showed a decline in population density after a simulated 1.4°C temperature increase at 50°N. In all other modeled scenarios there was an increase (inflation) in population density and biomass (per unit area) with climate heating, and this inflation increased with increasing latitude. We conclude that agent‐based bioenergetics models are valuable tools in discerning the impacts of climate change on wild fish populations, which play important roles in aquatic food webs.

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Development of an image binarization software tool for net occlusion estimations - R. Cappaert; W. Yang; D.J. Ross; C. Johnston; C. MacLeod; C.A. White (Aquacultural Engineering, 2024)

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

Reflex impairment as a predictor of mortality in Panulirus argus: Implications for the live export market - Erica P. Ross; Casey B. Butler; Carly M. Hannah; Thomas R. Matthews (Fisheries Research, 2024)

Biscuits for the gut: A symphony of FODMAPs and dietary fibre in gut microbiome for irritable bowel syndrome (IBS) management - Fatma Koc; Jonas Atzler; Aylin W. Sahin; Elke Arendt; R. Paul Ross; Catherine Stanton (Innovative Food Science & Emerging Technologies, 2024)

Gastric mill ossicles record chronological age in the Caribbean spiny lobster (Panulirus argus) - Emily Hutchinson; Thomas R. Matthews; Erica Ross; Samantha Hagedorn; Mark J. Butler (Fisheries Research, 2024)

Sex determination of South Africa's Encephalartos - A conservation perspective - James A.R. Clugston; Nathasha R. Mahunye; Ross D. Stewart; Hendrik Niemann; Michelle van der Bank (South African Journal of Botany, 2024)

Pulsed nicotine infusions as a model for smoking: validating a tool to explore nicotine thresholds in humans - Suprit Parida; R. Ross MacLean; Ralitza Gueorguieva; Mehmet Sofuoglu (Psychopharmacology, 2024)

Estimating the monetary cost of biological invasions to South Africa - Emily J. McCulloch-Jones; Ross N. Cuthbert; Brian W. van Wilgen; John R. U. Wilson (Biological Invasions, 2024)
Estimates of the cost of damage caused by invasive alien speices and the money spent addressing biological invasions are needed to guide policy and management. Here, we quantify the known monetary costs of biological invasions to South Africa, using data from the InvaCost database, literature searches, and stakeholders. The Department of Forestry, Fisheries and the Environment, and agencies directly funded by them, provided most of the information on money spent, with very little information was available from other government agencies and the private sector. There was also very little information on the monetary costs due to the impacts of invasions. Between 1960 and 2023, ZAR9.6 billion (adjusted to 2022 values) was spent managing biological invasions in South Africa. This is only 4% of the money predicted as being necessary for management, which amounted to ZAR231.8 billion in 2022 values. There is uncertainty in the obtained estimates due to a paucity of information on both impacts and management costs. A few key points emerged from our analysis: the cost of damage caused by invasions far exceeds expenditure on control; the amount spent on control is much less than what is predicted to be needed; almost all management has focussed on a few invasive plant species; and there are large gaps in information that reduce the confidence in our estimates. Transparent cost reporting, strategic public–private collaborations, standardised impact metrics, and reliable assessments of management effectiveness are needed to enable South Africa to more effectively account for and prioritise investments.

A preliminary estimate of the contribution of coastal blue carbon to climate change mitigation in New Zealand - Finnley W. R. Ross; Dana E. Clark; Olga Albot; Anna Berthelsen; Richard Bulmer; Josie Crawshaw; Peter I. Macreadie (New Zealand Journal of Marine and Freshwater Research, 2024)
The scale at which New Zealand is currently storing and sequestering blue carbon, and could create additional blue carbon via restoration, has been unclear. Here, we calculate a preliminary estimate for the current extent of three key blue carbon ecosystems (saltmarshes, mangrove forests and seagrass meadows), their carbon stocks and their carbon sequestration rates using the best available data to provide a preliminary estimate of blue carbon in New Zealand. We also use local examples to explore opportunities to create additional blue carbon. Based on the available literature, we estimate the current extent of New Zealand's blue carbon ecosystems to be 76,152 ha, which is 1.0% of the area of terrestrial native forests. Our preliminary estimate of New Zealand's blue carbon stock is 2.66–3.76 Mt of carbon, with a current carbon sequestration rate of 0.12 (0.05–0.26) Mt/CO 2 /yr, which is equivalent to 0.16% of New Zealand's 2021 gross emissions. Restoration of saltmarshes could enhance their carbon sink capacity, mangrove forests are naturally expanding and seagrass meadow restoration techniques at scale are still in development. Developing a national framework for blue carbon protection, monitoring and restoration is important as part of New Zealand's climate change mitigation and adaptation efforts.

Spatial variation in genomic signatures of local adaptation during the cane toad invasion of Australia - Marc A. Beer; Daryl R. Trumbo; Rhett M. Rautsaw; Christopher P. Kozakiewicz; Brendan Epstein; Paul A. Hohenlohe; Ross A. Alford; Lin Schwarzkopf; Andrew Storfer (Molecular Ecology, 2024)
Adaptive evolution can facilitate species' range expansions across environmentally heterogeneous landscapes. However, serial founder effects can limit the efficacy of selection, and the evolution of increased dispersal during range expansions may result in gene flow swamping local adaptation. Here, we study how genetic drift, gene flow and selection interact during the cane toad's ( Rhinella marina ) invasion across the heterogeneous landscape of Australia. Following its introduction in 1935, the cane toad colonised eastern Australia and established several stable range edges. The ongoing, more rapid range expansion in north‐central Australia has occurred concomitant with an evolved increase in dispersal capacity. Using reduced representation genomic data of Australian cane toads from the expansion front and from two areas of their established range, we test the hypothesis that high gene flow constrains local adaptation at the expansion front relative to established areas. Genetic analyses indicate the three study areas are genetically distinct but show similar levels of allelic richness, heterozygosity and inbreeding. Markedly higher gene flow or recency of colonisation at the expansion front have likely hindered local adaptation at the time of sampling, as indicated by reduced slopes of genetic‐environment associations (GEAs) estimated using a novel application of geographically weighted regression that accounts for allele surfing; GEA slopes are significantly steeper in established parts of the range. Our work bolsters evidence supporting adaptation of invasive species post‐introduction and adds novel evidence for differing strengths of evolutionary forces among geographic areas with different invasion histories.

Exploiting lactic acid bacteria for colorectal cancer: a recent update - Yang Chen; Bo Yang; Jianxin Zhao; R. Paul Ross; Catherine Stanton; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Extravehicular activity on the lunar surface: Mapping mitigation risk consequence for crew needing assistance or rescue - M. Walton; J. Norcross; R. Sanders; S. Myers; N. Newby; S. Ross (Journal of Space Safety Engineering, 2024)

In vitro evaluation of intersubject variability in pediatric intranasal drug delivery using nasal spray suspension products - Amir R. Esmaeili; John V. Wilkins; Sana Hosseini; Ali Alfaifi; Mohammad Hejazi; Michael Hindle; Worth Longest; Theodore Schuman; Sneha Dhapare; Anubhav Kaviratna; Ross Walenga; Bryan Newman; et al. (Journal of Aerosol Science, 2024)

Heterologous Expression of Plantaricin 423 and Mundticin ST4SA in Saccharomyces cerevisiae - Michelle Rossouw; Rosemary A. Cripwell; Ross R. Vermeulen; Anton D. van Staden; Willem H. van Zyl; Leon M. T. Dicks; Marinda Viljoen-Bloom (Probiotics and Antimicrobial Proteins, 2024)
Antimicrobial peptides or bacteriocins are excellent candidates for alternative antimicrobials, but high manufacturing costs limit their applications. Recombinant gene expression offers the potential to produce these peptides more cost-effectively at a larger scale. Saccharomyces cerevisiae is a popular host for recombinant protein production, but with limited success reported on antimicrobial peptides. Individual recombinant S. cerevisiae strains were constructed to secrete two class IIa bacteriocins, plantaricin 423 (PlaX) and mundticin ST4SA (MunX). The native and codon-optimised variants of the plaA and munST4SA genes were cloned into episomal expression vectors containing either the S. cerevisiae alpha mating factor (MFα1) or the Trichoderma reesei xylanase 2 (XYNSEC) secretion signal sequences. The recombinant peptides retained their activity and stability, with the MFα1 secretion signal superior to the XYNSEC secretion signal for both bacteriocins. An eight-fold increase in activity against Listeria monocytogenes was observed for MunX after codon optimisation, but not for PlaX-producing strains. After HPLC-purification, the codon-optimised genes yielded 20.9 mg/L of MunX and 18.4 mg/L of PlaX, which displayed minimum inhibitory concentrations (MICs) of 108.52 nM and 1.18 µM, respectively, against L. monocytogenes . The yields represent a marked improvement relative to an Escherichia coli expression system previously reported for PlaX and MunX. The results demonstrated that S. cerevisiae is a promising host for recombinant bacteriocin production that requires a simple purification process, but the efficacy is sensitive to codon usage and secretion signals.

Price variation in the Caribbean spiny lobster fishery: Incentives for ongrowing wild-caught lobsters in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Thomas R. Matthews; Erica Ross (Fisheries Research, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Positive tipping points for the sustainable growth of bivalve shellfish mariculture in England and Wales - A. Ross Brown; Tim Huntington; Lisa K. Bickley; Tom Powell; Charles R. Tyler (Marine Policy, 2024)

Consumer isoscapes reveal heterogeneous food webs in deep-sea submarine canyons and adjacent slopes - Amanda W.J. Demopoulos; Brian J. Smith; Jill R. Bourque; Jason D. Chaytor; Jennifer McClain-Counts; Nancy Prouty; Steve W. Ross; Sandra Brooke; Gerard Duineveld; Furu Mienis (Progress in Oceanography, 2024)

Blanford's fox (Vulpes cana) habitat suitability in Saudi Arabia: Insights from camera trapping and ensemble species distribution modelling - J. Philip B. Faure; Marine Drouilly; Alexander E. Botha; Michael D. Ross; J. Andrew Spalton; Mesfer AlHlafi; Carolyn E. Dunford; David R. Mills; Ross De Bruin; Emma Gallacher; Gareth K.H. Mann (Journal of Arid Environments, 2024)

Corrigendum to “Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein” [Food Structure 37 (2023) 100342] - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2024)

Home sweet home: Comparison of epibiont assemblages associated with cultivated and wild sugar kelp (Saccharina latissima), co-cultivated blue mussels (Mytilus edulis) and farm infrastructure - Sophie Corrigan; A. Ross Brown; Charles R. Tyler; Catherine Wilding; Carly Daniels; Ian G. C. Ashton; Dan A. Smale (Journal of Applied Phycology, 2024)
Seaweed farming is expanding in Europe and may provide environmental benefits similar to those from natural kelp forests and shellfish farms, including habitat provisioning. Few studies have substantiated these claims however, and it remains uncertain whether seaweed farms will support similar biodiversity to kelp forests or provide valuable long-term habitat beyond the harvest season. We repeatedly surveyed an integrated sugar kelp ( Saccharina latissima ) and blue mussel ( Mytilus edulis ) farm in southwest UK to compare epibiont assemblages between cultivated kelps, to those from three nearby wild kelp populations, and to epibionts on farmed mussel lines and unseeded ‘bare’ lines. We found farmed kelps supported over 217 times the abundance of epibionts living on wild kelps at harvest time, however, taxonomic diversity per kelp was lower at the farm. Farmed kelp assemblages were dominated by amphipods, which were present on the wild kelps but in much lower numbers. Farmed kelp also supported distinct assemblages to cultivated mussels, which were similarly dominated by amphipods, but hosted higher relative abundances of crabs, echinoderms, worms and red algal biomass. The bare lines were heavily colonised by another pseudo-kelp, Saccorhiza polyschides , which supported similar epibiont assemblages to the seeded S. latissima lines. Our findings indicate that cultivating bivalves alongside seaweed can increase habitat provisioning at a seaweed farm and extend its permanence beyond typical seaweed cultivation periods as bivalves have longer, continuous farming periods. However, the presence of mussels will likely influence the epibiont assemblages on the farmed kelp, which are distinct from wild kelp populations.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Elevated lead (Pb) in urban European starling (Sturnus vulgaris) feathers is not correlated to physiology or behavior - Michelle Ross; Joanna L. Corimanya; Rachel Kaplan; Denyelle A.V. Kilgour; Courtney R. Linkous; Sarah Guindre-Parker (Science of The Total Environment, 2024)

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Genetic sex determination improves Canadian Atlantic salmon ( Salmo salar ) population assessments - Martha J. Robertson; Sarah J. Lehnert; Nicholas I. Kelly; Lorraine C. Hamilton; Ross A. Jones; Alex L. Levy; Rebecca Poole; Chantelle M. Burke; Steven J. Duffy; Amber Messmer; Ian R. Bradbury (Fisheries Management and Ecology, 2024)
Estimating egg deposition for Atlantic salmon population assessments is made difficult by their lack of sexual dimorphism prior to the autumn spawning season. We quantified the effect of sex misclassification from subjective examination of external morphology on egg deposition estimates in four Atlantic salmon populations across multiple years. Sex classification of Canadian salmon using the genetic sex marker ( sd Y) was accurate (>97%), whereas sex classification based on subjective examination of external morphology was inaccurate, with misclassification rates dependent on sea age, life history, and sampling season. Sex misclassification led to annual egg deposition estimates that ranged from −36% to +56%. We found that sex could not be discriminated based on measures of external morphology.

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Divergent ecological responses to typhoon disturbance revealed via landscape‐scale acoustic monitoring - Samuel R. P.‐J. Ross; Nicholas R. Friedman; Kenneth L. Dudley; Takuma Yoshida; Masashi Yoshimura; Evan P. Economo; David W. Armitage; Ian Donohue (Global Change Biology, 2024)
Climate change is increasing the frequency, intensity, and duration of extreme weather events across the globe. Understanding the capacity for ecological communities to withstand and recover from such events is critical. Typhoons are extreme weather events that are expected to broadly homogenize ecological dynamics through structural damage to vegetation and longer‐term effects of salinization. Given their unpredictable nature, monitoring ecological responses to typhoons is challenging, particularly for mobile animals such as birds. Here, we report spatially variable ecological responses to typhoons across terrestrial landscapes. Using a high temporal resolution passive acoustic monitoring network across 24 sites on the subtropical island of Okinawa, Japan, we found that typhoons elicit divergent ecological responses among Okinawa's diverse terrestrial habitats, as indicated by increased spatial variability of biological sound production (biophony) and individual species detections. This suggests that soniferous communities are capable of a diversity of different responses to typhoons. That is, spatial insurance effects among local ecological communities provide resilience to typhoons at the landscape scale. Even though site‐level typhoon impacts on soundscapes and bird detections were not particularly strong, monitoring at scale with high temporal resolution across a broad spatial extent nevertheless enabled detection of spatial heterogeneity in typhoon responses. Further, species‐level responses mirrored those of acoustic indices, underscoring the utility of such indices for revealing insight into fundamental questions concerning disturbance and stability. Our findings demonstrate the significant potential of landscape‐scale acoustic sensor networks to capture the understudied ecological impacts of unpredictable extreme weather events.

Comparability of Outputs between Traditional and Simulation-Based Approaches to Collision Risk Modelling - Nicholas Horne; Pál Schmitt; Ross Culloch; Ben Wilson; Jonathan D. R. Houghton; Andrew Dale; Louise Kregting (Journal of Marine Science and Engineering, 2023)
Tidal stream energy is a predictable renewable energy source; however, environmental consent of developments remains a key barrier to the expansion of this industry. Uncertainty around collision risk, i.e., the risk of animals colliding with a tidal device, remains a major barrier to consent. Collision risk models are used in environmental impact assessments. Common collision risk models, like the Encounter Rate and Band Models, have limitations in accommodating new device designs and flexibility. To address this, a simulation-based approach was developed. To provide confidence in its use, it is important that the simulation-based approach is compared against the Band model and the Encounter rate model, which have been regularly used in the UK. Here, we compared collision risk estimates from the three models under the same exact conditions and one alternative condition. The results of the main scenario (where all conditions were the same) showed that the three models produced comparable results with

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Comparative genomics of Lactobacillus johnsonii reveals extensive intraspecific genetic variation - Kexue Chen; Xingya Zhou; Jianxin Zhao; R. Paul Ross; Catherine Stanton; Wei Chen; Bo Yang (Food Bioscience, 2023)

Neurodevelopmental Consequences of Dietary Zinc Deficiency: A Status Report - Madeline M. Ross; Diego R. Hernandez-Espinosa; Elias Aizenman (Biological Trace Element Research, 2023)

Evidence for the weather-driven deterioration of ageing transportation earthworks in the UK - Kevin M. Briggs; Peter R. Helm; Joel A. Smethurst; Alister Smith; Ross Stirling; Aleksandra Svalova; Yuderka Trinidad González; Fleur A. Loveridge; Stephanie Glendinning (Transportation Geotechnics, 2023)

Fossilisation processes and our reading of animal antiquity - Ross P. Anderson; Christina R. Woltz; Nicholas J. Tosca; Susannah M. Porter; Derek E.G. Briggs (Trends in Ecology & Evolution, 2023)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

Textural characteristics of ore mineral dendrites in banded quartz veins from low-sulfidation epithermal deposits: implications for the formation of bonanza-type precious metal enrichment - Erik R. Tharalson; Tadsuda Taksavasu; Thomas Monecke; T. James Reynolds; Nigel M. Kelly; Katharina Pfaff; Aaron S. Bell; Ross Sherlock (Mineralium Deposita, 2023)

Food Insecurity and Diet Quality Among Adults on Medicaid With and Without a Mental Illness Diagnosis - Emma Anderson; Jessica L. McCurley; Ross Sonnenblick; Sydney McGovern; Vicki Fung; Douglas E. Levy; Cheryl R. Clark; Anne N. Thorndike (Journal of the Academy of Nutrition and Dietetics, 2023)

Integrated and data Science-informed seabed characterisation for optimised foundation design - M.P. O'Neill; A.L. Osuchowski; Y. Cai; M.F. Bransby; P.G. Watson; C. Gaudin; J. Doherty; E. Dalgaard; R. Ross (Ocean Engineering, 2023)

An island apart: Cranial endocast variation and sensory function in Tenrecomorpha - R. Benjamin Sulser; Ross D. E. MacPhee (Journal of Mammalian Evolution, 2023)

The development of a solid lipid nanoparticle (SLN)-based lacticin 3147 hydrogel for the treatment of wound infections - Aoibhín Ryan; Pratikkumar Patel; Poonam Ratrey; Paula M. O’Connor; Julie O’Sullivan; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2023)
Chronic wounds affect millions of people globally. This number is set to rise with the increasing incidence of antimicrobial-resistant bacterial infections, such as methicillin-resistant Staphylococcus aureus (MRSA), which impair the healing of chronic wounds. Lacticin 3147 is a two-peptide chain bacteriocin produced by Lactococcus lactis that is active against S. aureus including MRSA strains. Previously, poor physicochemical properties of the peptides were overcome by the encapsulation of lacticin 3147 into solid lipid nanoparticles. Here, a lacticin 3147 solid lipid nanoparticle gel is proposed as a topical treatment for S. aureus and MRSA wound infections. Initially, lacticin 3147’s antimicrobial activity against S. aureus was determined before encapsulation into solid lipid nanoparticles. An optimised gel formulation with the desired physicochemical properties for topical application was developed, and the lacticin-loaded solid lipid nanoparticles and free lacticin 3147 aqueous solution were incorporated into separate gels. The release of lacticin 3147 from both the solid lipid nanoparticle and free lacticin gels was measured where the solid lipid nanoparticle gel exhibited increased activity for a longer period (11 days) compared to the free lacticin gel (9 days). Both gels displayed potent activity ex vivo against S. aureus- infected pig skin with significant bacterial eradication (> 75%) after 1 h. Thus, a long-acting potent lacticin 3147 solid lipid nanoparticle gel with the required physicochemical properties for topical delivery of lacticin 3147 to the skin for the potential treatment of S. aureus -infected chronic wounds was developed. Graphical abstract

Human‐induced salinity changes impact marine organisms and ecosystems - Till Röthig; Stacey M. Trevathan‐Tackett; Christian R. Voolstra; Cliff Ross; Samuel Chaffron; Paul J. Durack; Laura M. Warmuth; Michael Sweet (Global Change Biology, 2023)
Climate change is fundamentally altering marine and coastal ecosystems on a global scale. While the effects of ocean warming and acidification on ecology and ecosystem functions and services are being comprehensively researched, less attention is directed toward understanding the impacts of human‐driven ocean salinity changes. The global water cycle operates through water fluxes expressed as precipitation, evaporation, and freshwater runoff from land. Changes to these in turn modulate ocean salinity and shape the marine and coastal environment by affecting ocean currents, stratification, oxygen saturation, and sea level rise. Besides the direct impact on ocean physical processes, salinity changes impact ocean biological functions with the ecophysiological consequences are being poorly understood. This is surprising as salinity changes may impact diversity, ecosystem and habitat structure loss, and community shifts including trophic cascades. Climate model future projections (of end of the century salinity changes) indicate magnitudes that lead to modification of open ocean plankton community structure and habitat suitability of coral reef communities. Such salinity changes are also capable of affecting the diversity and metabolic capacity of coastal microorganisms and impairing the photosynthetic capacity of (coastal and open ocean) phytoplankton, macroalgae, and seagrass, with downstream ramifications on global biogeochemical cycling. The scarcity of comprehensive salinity data in dynamic coastal regions warrants additional attention. Such datasets are crucial to quantify salinity‐based ecosystem function relationships and project such changes that ultimately link into carbon sequestration and freshwater as well as food availability to human populations around the globe. It is critical to integrate vigorous high‐quality salinity data with interacting key environmental parameters (e.g., temperature, nutrients, oxygen) for a comprehensive understanding of anthropogenically induced marine changes and its impact on human health and the global economy.

Exploiting lactic acid bacteria for inflammatory bowel disease: A recent update - Yang Chen; He Gao; Jianxin Zhao; R. Paul Ross; Catherine Stanton; Hao Zhang; Wei Chen; Bo Yang (Trends in Food Science & Technology, 2023)

Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2023)

Individual variation in the avian gut microbiota: The influence of host state and environmental heterogeneity - Shane E. Somers; Gabrielle L. Davidson; Crystal N. Johnson; Michael S. Reichert; Jodie M. S. Crane; R. Paul Ross; Catherine Stanton; John L. Quinn (Molecular Ecology, 2023)
The gut microbiota have important consequences for host biological processes and there is some evidence that they also affect fitness. However, the complex, interactive nature of ecological factors that influence the gut microbiota has scarcely been investigated in natural populations. We sampled the gut microbiota of wild great tits ( Parus major ) at different life stages allowing us to evaluate how microbiota varied with respect to a diverse range of key ecological factors of two broad types: (1) host state, namely age and sex, and the life history variables, timing of breeding, fecundity and reproductive success; and (2) the environment, including habitat type, the distance of the nest to the woodland edge, and the general nest and woodland site environments. The gut microbiota varied with life history and the environment in many ways that were largely dependent on age. Nestlings were far more sensitive to environmental variation than adults, pointing to a high degree of flexibility at an important time in development. As nestlings developed their microbiota from one to two weeks of life, they retained consistent (i.e., repeatable) among‐individual differences. However these apparent individual differences were driven entirely by the effect of sharing the same nest. Our findings point to important early windows during development in which the gut microbiota are most sensitive to a variety of environmental drivers at multiple scales, and suggest reproductive timing, and hence potentially parental quality or food availability, are linked with the microbiota. Identifying and explicating the various ecological sources that shape an individual's gut bacteria is of vital importance for understanding the gut microbiota's role in animal fitness.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Long-term tracking reveals a dynamic crocodylian social system - Cameron J. Baker; Céline H. Frère; Craig E. Franklin; Hamish A. Campbell; Terri R. Irwin; Ross G. Dwyer (Animal Behaviour, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

At the interfaces of the hydrologic sciences: Connecting water, elements, ecosystems, and people through the major contributions of Dr. Emily Bernhardt - Ashley M. Helton; Jennifer L. Morse; Elizabeth B. Sudduth; Marcelo Ardón; Raven Bier; Kristofor A. Voss; Matthew R.V. Ross; Joanna R. Blaszczak; Jessica E. Brandt; Marie Simonin; Jennifer D. Rocca; Alice Carter; et al. (Journal of Hydrology, 2023)

Cnr1−/− has minimal impact on chlorpyrifos-mediated effects in the mouse endocannabinoid system, but it does alter lipopolysaccharide-induced cytokine levels in splenocytes - Brittany N. Szafran; James Nichols; Ashleigh Nicaise; Abdolsamad Borazjani; Russell L. Carr; Juliet R. Wilson; Matthew K. Ross; Barbara L.F. Kaplan (Chemico-Biological Interactions, 2023)

Inferred vehicular emissions at a near-road site: Impacts of COVID-19 restrictions, traffic patterns, and ambient air temperature - Dolly L. Hall-Quinlan; Hao He; Xinrong Ren; Timothy P. Canty; Ross J. Salawitch; Phillip Stratton; Russell R. Dickerson (Atmospheric Environment, 2023)

Conservation management in the context of unidentified and unmitigated threatening processes - Dejan Stojanovic; Carolyn J. Hogg; Fernanda Alves; G. Barry Baker; James R. Biggs; Laura Bussolini; Mark J. Carey; Ross Crates; Michael J. L. Magrath; Rachel Pritchard; Shannon Troy; Catherine M. Young; et al. (Biodiversity and Conservation, 2023)
The decision to intervene in endangered species management is often complicated. Migratory species exemplify this difficulty because they experience diverse threats at different times and places that can act cumulatively and synergistically on their populations. We use population viability analysis (PVA) to compare potential conservation interventions on the critically endangered, migratory Orange-bellied Parrot Neophema chrysogaster . This species suffers high juvenile mortality, but it is not clear why this is so. Given uncertainty about the best recovery strategy, we compare PVA scenarios that simulate various ways of utilizing captive-bred parrots to support the wild population in the context of unresolved threatening processes. Increasing the number of juveniles entering the population each year had the greatest benefit for population growth rate and size. Directly lowering juvenile mortality rates is difficult given uncertainty about the drivers of mortality in the wild. In lieu of this, releasing 100 juveniles from captivity to the wild population each autumn (either as a stand-alone action, or in combination with other interventions) was the most feasible and straightforward intervention of the options we tested. However, our PVAs also show that unless substantial and sustainable reductions can be made to juvenile mortality rates, Orange-bellied Parrots will remain dependent on intensive conservation management. This study highlights the utility of PVAs for answering practical questions about how to implement species conservation. PVAs provide a way to incorporate the best available information in a replicable modelling framework, and to identify impacts of parameter uncertainty on demographic trends.

Authors’ Response - Michelle I. Cardel; Faith A. Newsome; Rebecca L. Pearl; Kathryn M. Ross; Julia R. Dillard; Jacqueline F. Hayes; Denise Wilfley; Pamela K. Keel; Emily J. Dhurandhar; Katherine N. Balantekin (Journal of the Academy of Nutrition and Dietetics, 2023)

Anthropogenic VOCs in the Long Island Sound, NY Airshed and their role in ozone production - Allison M. Ring; Russell R. Dickerson; Abby E. Sebol; Xinrong Ren; Sarah E. Benish; Ross J. Salawitch; Andrea Galasyn; Paul J. Miller; Timothy P. Canty (Atmospheric Environment, 2023)

Conditional alternative movement tactics in male crocodiles - Kaitlin E. Barham; Cameron J. Baker; Craig E. Franklin; Hamish A. Campbell; Celine H. Frére; Terri R. Irwin; Ross G. Dwyer (Behavioral Ecology and Sociobiology, 2023)
In species where conflict is costly, individuals adopt alternative movement tactics to minimise the risk of competitive interactions. Dominant males often maintain defined territories, while less competitive males may be forced to adopt alternative tactics to maximise fitness and reduce conflict. However, the extent to which males switch tactics according to current social or physiological status is poorly understood. Using implanted acoustic tags and a fixed array of tracking receivers, we investigated how the behaviour of 78 male estuarine crocodiles ( Crocodylus porosus ) shifted over an 11-year period in relation to ontogeny, body condition, and the extent of physical injuries. We discovered that male crocodiles sorted into three common movement classes, with 51% of males maintaining the same movement class across consecutive years (max = 9 years). Males > 4 m in total length maintained confined territories both within and across years and had the greatest extent of injuries and the highest condition score, indicative of territory holders. In contrast, smaller males sorted into high movement roamer or low movement site-philopatric tactics, where the tactic an individual adopted was less stable between years and did not correlate with condition or external injuries. Our study reveals the socio-biological mechanisms by which estuarine crocodiles coexist within a restricted habitat. Significance statement Identifying individual-level differences in movement helps us predict which individuals are more likely to be involved in human-wildlife interactions. However, studying long-term shifts in movement is challenging, as large datasets of co-occurring individuals tracked in their natural environment over multiple years are required. We tracked a population of 78 male estuarine crocodiles (1030–4687 mm total length) in a shared environment over 11 years and assessed how eight movement traits were linked to body size and physical condition. At the population level, males sorted into different movement tactics according to ontogeny, with large territorial males having better body condition yet a greater incidence of injury. However, 49% of males showed variability across years, suggesting that tactics were conditional relative to environmental variability and a male’s own status. Our study provides insights into the mechanisms and costs of movement tactics in wild crocodile populations.

Transgenerational transfer of the microbiome is altered by ocean acidification in oyster larvae - Elliot Scanes; Pauline M. Ross; Justin R. Seymour; Nachshon Siboni; Michael C. Dove; Wayne A. O'Connor; Callum Dittes; Laura M. Parker (Aquaculture, 2023)

A decade-long connectivity study of Permit (Trachinotus falcatus) in Florida supports a spatial management approach - Ross E. Boucek; Robert D. Ellis; Andrew R. Forauer; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Fog trends in India: Relationships to fog type and western disturbances - Daniel K. E. Smith; Stephen R. Dorling; Ian A. Renfrew; Andrew N. Ross; Craig Poku (International Journal of Climatology, 2023)
Fog is a major hazard in wintertime over India, particularly in the Indo‐Gangetic Plains, leading to significant impacts for transport and human health. Using 3‐hourly surface observations, from 69 sites across India, all fog and dense fog events between 2000 and 2020 are identified. For each event, the main fog formation mechanism is objectively categorized using a classification algorithm, distinguishing between radiation, advection, evaporation, precipitation or cloud‐base lowering fog types. In contrast to the findings of other international studies, radiation fog dominates as the most common fog type at the vast majority of locations in India, accounting for 68.1% of all fog events and 70.0% of dense fog events. Statistically significant positive trends are seen in the frequency of all fog events at Delhi, Lucknow and Patna, in the Indo‐Gangetic plains, between 1997/1998 and 2018/2019, dominated by comparable statistically significant positive trends in radiation fogs. Western disturbances (WD) are often linked to the formation of fog in India. Using a climatology of WDs, we show that 46.9% of radiation fog onsets in Delhi in December and January, the primary fog months, happened in conjunction with an active WD event. Conversely, only 32.3% of WDs during these same months coincided with the onset of a radiation fog event. WD‐related radiation fog events are shown to cluster into three distinct groups, with WD centres located to the northwest (51.4% of cases), southwest (13.3%) and east (35.2%) of Delhi. Each cluster is shown to have coherent and distinct near‐surface characteristics which are conducive to fog formation. Trends in WD frequency cannot fully account for the observed trends in fog events. We argue that the fog trends are more likely the result of a complex interaction between urban expansion and the associated rapid change in aerosol loading, resulting in impacts on radiation balance, microphysics and heat‐island processes.

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Texture and geochemistry of pyrite from the Jinya, Nakuang and Gaolong gold deposits in the Youjiang Basin: implications for basin-scale gold mineralization - Lin Yang; Qingfei Wang; Ross R. Large; Denis Fougerouse; Indrani Mukherjee; Qizuan Zhang; Jun Deng (Mineralium Deposita, 2022)

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Quantifying habitat provisioning at macroalgal cultivation sites - Sophie Corrigan; Andrew Ross Brown; Ian G. C. Ashton; Dan A. Smale; Charles R. Tyler (Reviews in Aquaculture, 2022)
Macroalgal cultivation is expanding rapidly, and promises to contribute significantly towards future food and energy security, sustainable livelihoods, ecosystem services and habitat provisioning for a range of associated organisms globally. Habitat provisioning underpins biodiversity and ecosystem structure and functioning, supports many ecosystem services and has possible benefits to other marine industries, including enhancement of commercial fish stocks. In macroalgal cultivation, however, only recently has habitat provisioning started to be assessed at a local scale (within a farm's footprint) and with a range of different approaches. This review evaluates techniques used to quantify habitat provisioning in and around macroalgal cultivation sites, for species ranging from microorganisms to megafauna, and outlines recommendations to enable a more comprehensive ecological valuation of macroalgal cultivation in the future. The majority of information on biodiversity associated with macroalgal cultivation is associated with quantifying biofouling or pest organisms, rather than the contribution of colonising species to healthy ecosystem functioning. We suggest how better monitoring of macroalgal cultivation could enable an ecosystem approach to aquaculture (EAA) in the future. To achieve this, we highlight the need for standardised and robust methods for quantifying habitat provisioning that will enable assessment and monitoring of macroalgal cultivation sites of varying scales and within different regions and environmental settings. Increased evidence for the potential habitat value of macroalgal cultivation sites will help inform and shape marine legislation, licencing and certification for macroalgal farmers and potentially reduce marine user conflicts, helping the industry to continue to grow sustainably using EAA.

Location-weighted traffic-related air pollution and asthma symptoms in urban adolescents - Anne Mielnik; Sheena E. Martenies; Judy M. Heiderscheidt; Jason Su; Zev Ross; Michael Jerrett; John R. Balmes; Sheryl Magzamen (Air Quality, Atmosphere & Health, 2022)

Sea-Level Rise and the Persistence of Tree Islands in Coastal Landscapes - Michael S. Ross; Susana L. Stoffella; Rosario Vidales; John F. Meeder; David C. Kadko; Leonard J. Scinto; Suresh C. Subedi; Jed R. Redwine (Ecosystems, 2022)

Same Space, Different Standards: A Review of Cumulative Effects Assessment Practice for Marine Mammals - Emily L. Hague; Carol E. Sparling; Ceri Morris; Duncan Vaughan; Rebecca Walker; Ross M. Culloch; Alastair R. Lyndon; Teresa F. Fernandes; Lauren H. McWhinnie (Frontiers in Marine Science, 2022)
Marine mammals are vulnerable to a variety of acute and chronic anthropogenic stressors, potentially experiencing these in isolation, successively and/or simultaneously. Formal assessment of the likely impact(s) of the cumulative effects of multiple stressors on a defined population is carried out through a Cumulative Effects Assessment (CEA), which is a mandatory component of the Environmental Impact Assessment (EIA) process in many countries. However, for marine mammals, the information required to feed into CEA, such as thresholds for disturbance, frequency of multiple (and simultaneous) exposures, interactions between stressors, and individual variation in response, is extremely limited, though our understanding is slowly improving. The gaps in knowledge make it challenging to effectively quantify and subsequently assess the risk of individual and population consequences of multiple disturbances in the form of a CEA. To assess the current state of practice for assessing cumulative effects on marine mammals within UK waters, 93 CEAs were reviewed across eleven maritime industries. An objective framework of thirteen evaluative criteria was used to score each assessment on a scale of 13-52 (weak - strong). Scores varied significantly by industry. On average, the aquaculture industry produced the lowest scoring CEAs, whilst the large offshore windfarm industry (≥ 20 turbines) scored highest, according to the scoring criteria used. There was a significant increase in scores over the sample period (2009-2019), though this was mostly attributed to five industries (cable, large and small offshore wind farms, tidal and wave energy). There was inconsistency in the language used to define and describe cumulative effects and a lack of routinely applied methodology. We use the findings presented here, along with a wider review of the literature, to provide recommendations and discussion points aimed at supporting the standardisation and improvement of CEA practice. Although this research focused on how marine mammals were considered within UK CEAs, recommendations made are broadly applicable to assessments conducted for other receptors, countries and/or environments. Adoption of these proposals would help to ensure a more consistent approach, and would aid decision-makers and practitioners in mitigating any potential impacts, to ensure conservation objectives of marine mammal populations are not compromised.

Complementary diet analyses reveal intraspecific and temporal variation in ringed seal (Pusa hispida) foraging in the Canadian high arctic - Tyler R. Ross; Gregory W. Thiemann; Brent G. Young; Steven H. Ferguson (Polar Biology, 2022)

Bacterial composition in the toheroa (Paphies ventricosa), a threatened surf clam from Aotearoa (New Zealand) - Matthew Bennion; Phil M. Ross; Henry S. Lane; Ian R. McDonald (Marine Biology, 2022)
The toheroa ( Paphies ventricosa ) is an Aotearoa (New Zealand) endemic surf clam that remains threatened following population collapse due to overfishing in the twentieth century. Despite protective measures being in place for more than 4 decades, toheroa populations have inexplicably failed to recover. As part of an investigation into the possible role of disease in preventing their recovery, an exploration of the bacterial composition in toheroa was conducted over their entire geographic range. The bacterial composition in toheroa tissues was dominated by Spirochaetaceae, Mycoplasmataceae , and Endozoicomonadaceae , and varied at both large (between geographically separated sites) and small spatial scales (beds < 10 km apart). At small scales, it was habitat, in this case the presence or absence of freshwater outflows, which appeared to be a major influence on bacterial composition. Given that the decline of toheroa has also coincided with changes in land use that have reduced the amount of freshwater reaching the toheroa beaches, it is possible that habitat-related shifts in the abundance of certain bacterial symbionts are affecting the health and impeding recovery of this iconic and culturally significant species.

A landscape approach for identifying potential reestablishment sites for extirpated stream fishes: an example with Arctic grayling (Thymallus arcticus) in Michigan - Ralph W. Tingley; Dana M. Infante; Emily M. Dean; Douglas W. Schemske; Arthur R. Cooper; Jared A. Ross; Wesley Daniel (Hydrobiologia, 2022)

Inhaled nitric oxide does not improve maximal oxygen consumption in endurance trained and untrained healthy individuals - Andrew R. Brotto; Devin B. Phillips; Victoria L. Meah; Bryan A. Ross; Desi P. Fuhr; Rhys I. Beaudry; Sean van Diepen; Michael K. Stickland (European Journal of Applied Physiology, 2022)

TitaniQ revisited: expanded and improved Ti-in-quartz solubility model for thermobarometry - Zach R. Osborne; Jay B. Thomas; William O. Nachlas; Ross J. Angel; Christopher M. Hoff; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Predators mitigate the destabilising effects of heatwaves on multitrophic stream communities - Samuel R. P.‐J. Ross; Jorge García Molinos; Atsushi Okuda; Jackson Johnstone; Keisuke Atsumi; Ryo Futamura; Maureen A. Williams; Yuichi Matsuoka; Jiro Uchida; Shoji Kumikawa; Hiroshi Sugiyama; Osamu Kishida; et al. (Global Change Biology, 2022)
Amidst the global extinction crisis, climate change will expose ecosystems to more frequent and intense extreme climatic events, such as heatwaves. Yet, whether predator species loss—a prevailing characteristic of the extinction crisis—will exacerbate the ecological consequences of extreme climatic events remains largely unknown. Here, we show that the loss of predator species can interact with heatwaves to moderate the compositional stability of ecosystems. We exposed multitrophic stream communities, with and without a dominant predator species, to realistic current and future heatwaves and found that heatwaves destabilised algal communities by homogenising them in space. However, this happened only when the predator was absent. Additional heatwave impacts on multiple aspects of stream communities, including changes to the structure of algal and macroinvertebrate communities, as well as total algal biomass and its temporal variability, were not apparent during heatwaves and emerged only after the heatwaves had passed. Taken together, our results suggest that the ecological consequences of heatwaves can amplify over time as their impacts propagate through biological interaction networks, but the presence of predators can help to buffer such impacts. These findings underscore the importance of conserving trophic structure, and highlight the potential for species extinctions to amplify the effects of climate change and extreme events.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Habitat size influences community stability - Hamish S. Greig; Peter A. McHugh; Ross M. Thompson; Helen J. Warburton; Angus R. McIntosh (Ecology, 2022)
Mechanisms linked to demographic, biogeographic, and food‐web processes thought to underpin community stability could be affected by habitat size, but the effects of habitat size on community stability remain relatively unknown. We investigated whether those habitat‐size‐dependent properties influenced community instability and vulnerability to perturbations caused by disturbance. This is particularly important given that human exploitation is contracting ecosystems, and abiotic perturbations are becoming more severe and frequent. We used a perturbation experiment in which 10 streams, spanning three orders of magnitude in habitat size, were subjected to simulated bed movement akin to a major flood disturbance event. We measured the resistance, resilience, and variability of basal resources, and population and community‐level responses across the stream habitat‐size gradient immediately before, and at 0.5, 5, 10, 20, and 40 d post‐disturbance. Resistance to disturbance consistently increased with stream size in all response variables. In contrast, resilience was significantly higher in smaller streams for some response variables. However, this higher resilience of small ecosystems was insufficient to compensate for their lower resistance, and communities of smaller streams were thus more variable over time than those of larger streams. Compensatory dynamics of populations, especially for predators, stabilized some aspects of communities, but these mechanisms were unrelated to habitat size. Together, our results provide compelling evidence for the links between habitat size and community stability, and should motivate ecologists and managers to consider how changes in the size of habitats will alter the vulnerability of ecosystems to perturbations caused by environmental disturbance.

Long-term monitoring of Vermont’s forest soils: early trends and efforts to address innate variability - Donald S. Ross; Scott W. Bailey; Thomas R. Villars; Angelica Quintana; Sandy Wilmot; James B. Shanley; Joshua M. Halman; James A. Duncan; Jennifer A. Bower (Environmental Monitoring and Assessment, 2021)

Implications of Genetic Structure for Aquaculture and Cultivar Translocation of the Kelp Ecklonia radiata in Northern New Zealand - Jacob Nepper-Davidsen; Marie Magnusson; Christopher R. K. Glasson; Philip M. Ross; Rebecca J. Lawton (Frontiers in Marine Science, 2021)
The fast expansion of the global seaweed aquaculture industry has created an interest in translocating seedlings cultivated from wild type brood stock. However, such translocations must be applied with caution as introduced cultivars can reduce genetic structure and diversity of wild populations. An understanding of the genetic structure and connectivity of target species is required to guide decision making around aquaculture translocation activities. In this study we used 14 microsatellite loci in a three-level hierarchical sampling design to analyze the genetic structure and connectivity of the native kelp Ecklonia radiata across 12 sites among four geographic regions (Northland, Bay of Plenty, Gisborne, and Wellington) in the North Island of New Zealand. Our aim was to provide guidance for translocation of cultivars to prevent the introduction of locally absent genotypes of E. radiata . Strong genetic structure and low geneflow were observed at all hierarchical levels, indicating the presence of multiple genetically distinct sub-populations. On a regional scale, high genetic differentiation was found between the Wellington region and the other three regions (F ST = 0.407–0.545), and within regions most sites were significantly different (measured by pairwise F ST ) with high relatedness found between individuals within sites (mean 28.2% ± 0.7 SE). Bayesian modeling and redundancy analysis showed a high degree of genetic clustering and indicate that ocean currents and other factors that have resulted in biogeographical breaks along the coast are likely to be the main factors shaping genetic structure and connectivity of E. radiata on the North Island, rather than isolation by distance. Based on these findings, we recommend that that cultivars of E. radiata should not be translocated outside their area of origin to avoid introducing locally absent genotypes to local sub-populations.

Correction to: An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

Overcoming the acquired resistance to gefitinib in lung cancer brain metastasis in vitro and in vivo - Zhongwei Liu; Neal Shah; Kent L. Marshall; Samuel A. Sprowls; Pushkar Saralkar; Afroz Mohammad; Kathryn E. Blethen; Tasneem A. Arsiwala; Ross Fladeland; Paul R. Lockman; Weimin Gao (Archives of Toxicology, 2021)

Sex‐specific expression and DNA methylation in a species with extreme sexual dimorphism and paternal genome elimination - Stevie A. Bain; Hollie Marshall; Andrés G. de la Filia; Dominik R. Laetsch; Filip Husnik; Laura Ross (Molecular Ecology, 2021)
Phenotypic differences between sexes are often mediated by differential expression and alternative splicing of genes. However, the mechanisms that regulate these expression and splicing patterns remain poorly understood. The mealybug, Planococcus citri , displays extreme sexual dimorphism and exhibits an unusual instance of sex‐specific genomic imprinting, paternal genome elimination (PGE), in which the paternal chromosomes in males are highly condensed and eliminated from the sperm. Planococcus citri has no sex chromosomes and both sexual dimorphism and PGE are predicted to be under epigenetic control. We recently showed that P . citri females display a highly unusual DNA methylation profile for an insect species, with the presence of promoter methylation associated with lower levels of gene expression. Here, we therefore decided to explore genome‐wide differences in DNA methylation between male and female P . citri using whole‐genome bisulphite sequencing. We identified extreme differences in genome‐wide levels and patterns between the sexes. Males display overall higher levels of DNA methylation which manifest as more uniform low levels across the genome. Whereas females display more targeted high levels of methylation. We suggest these unique sex‐specific differences are due to chromosomal differences caused by PGE and may be linked to possible ploidy compensation. Using RNA‐Seq, we identify extensive sex‐specific gene expression and alternative splicing, but we find no correlation with cis ‐acting DNA methylation.

The Prospect of Global Coral Reef Bathymetry by Combining Ice, Cloud, and Land Elevation Satellite-2 Altimetry With Multispectral Satellite Imagery - Arthur C. R. Gleason; Ross Smith; Sam J. Purkis; Kyle Goodrich; Alexandra Dempsey; Alejandro Mantero (Frontiers in Marine Science, 2021)
Empirical methods for estimating shallow-water bathymetry using passive multispectral satellite imagery are robust and globally applicable, in theory, but they require copious local measurements of water depth for algorithm calibration. Such calibration data have historically been unavailable for most locations, but NASA’s Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), a satellite-based LiDAR, might hold unique promise to fill this critical data gap. Although ICESat-2 was not designed as a marine altimeter, its ATLAS sensor consists of six green (532 nm) lasers that can penetrate a water surface and return photons reflected by the seabed, thereby generating bathymetric profiles. Utilizing TCarta’s NSF SBIR-funded Space-Based Laser Bathymetry Extraction Tool and ICESat-2’s ATL03 geolocated photon data product, we have compared ICESat-2 bathymetric retrievals with a portfolio of soundings acquired in situ using a vessel-mounted single-beam echosounder. This analysis demonstrated very high correlation ( R 2 = 0.96) between the field and space-based bathymetry data. The comparisons were made at multiple Caribbean and Pacific coral reef sites over water depths ranging from 1 to 20 m. Results suggest that ICESat-2 could be an effective approach for calibrating and validating empirical and radiative transfer methods, alike, for estimating shallow-water bathymetry from remote sensing imagery, thereby enabling the immediate potential for shallow-water bathymetric mapping of Earth’s reefs.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Breathing space: deoxygenation of aquatic environments can drive differential ecological impacts across biological invasion stages - James W. E. Dickey; Neil E. Coughlan; Jaimie T. A. Dick; Vincent Médoc; Monica McCard; Peter R. Leavitt; Gérard Lacroix; Sarah Fiorini; Alexis Millot; Ross N. Cuthbert (Biological Invasions, 2021)
The influence of climate change on the ecological impacts of invasive alien species (IAS) remains understudied, with deoxygenation of aquatic environments often-overlooked as a consequence of climate change. Here, we therefore assessed how oxygen saturation affects the ecological impact of a predatory invasive fish, the Ponto-Caspian round goby ( Neogobius melanostomus ), relative to a co-occurring endangered European native analogue, the bullhead ( Cottus gobio ) experiencing decline in the presence of the IAS. In individual trials and mesocosms, we assessed the effect of high, medium and low (90%, 60% and 30%) oxygen saturation on: (1) functional responses (FRs) of the IAS and native, i.e. per capita feeding rates; (2) the impact on prey populations exerted; and (3) how combined impacts of both fishes change over invasion stages (Pre-invasion, Arrival, Replacement, Proliferation). Both species showed Type II potentially destabilising FRs, but at low oxygen saturation, the invader had a significantly higher feeding rate than the native. Relative Impact Potential, combining fish per capita effects and population abundances, revealed that low oxygen saturation exacerbates the high relative impact of the invader. The Relative Total Impact Potential (RTIP), modelling both consumer species’ impacts on prey populations in a system, was consistently higher at low oxygen saturation and especially high during invader Proliferation. In the mesocosm experiment, low oxygen lowered RTIP where both species were present, but again the IAS retained high relative impact during Replacement and Proliferation stages at low oxygen. We also found evidence of multiple predator effects, principally antagonism. We highlight the threat posed to native communities by IAS alongside climate-related stressors, but note that solutions may be available to remedy hypoxia and potentially mitigate impacts across invasion stages.

Overwintering and migration behaviour of post‐spawned Atlantic salmon Salmo salar in a large hydropower‐regulated river and reservoir - Amanda B. Babin; Mouhamed Ndong; Katy Haralampides; Stephan Peake; Ross Jones; R. Allen Curry; Tommi Linnansaari (Journal of Fish Biology, 2021)
Tracking 47 post‐spawned adult Atlantic salmon Salmo salar L. in a hydropower‐regulated river through autumn, winter and spring revealed that winter survival was 56% and 75% in two study years, respectively, with higher mortality of males than females (50% vs . 33% and 100% vs . 13%, respectively). Some kelts ( n = 7) displayed nondirected movements that were interpreted as a reconditioning period for an average of 9–17 days prior to directed downstream movements indicating the initiation of migration. Survival after the initiation of migration in spring was 83% and 94% to the hydropower dam in the first and second study years, and decreased to 60 and 63%, respectively, after dam passage. There were no further losses in the downriver reach in the second year, with the first year having a cumulative survival estimate of 53% to the river mouth. Kelts approached the dam when the spillway gates were available as a passage option most of the time (64%–75%), but some kelts arrived at the dam or had not yet passed when spillways were closed ( n = 6) and the only remaining passage option was restricted to the turbines. However, all but one kelt that must have passed via turbine were successful in reaching the river mouth. Migratory delay presumably due to searching behaviour caused by low water flow was estimated at approximately 6 days as migration rates were significantly slower in the reservoir (median ± s.e. 8.5 ± 2.5 km day −1 ) than up‐ (29.7 ± 5.0 km day −1 ) or downriver (22.1 ± 3.1 km day −1 ). The proportion of time (median 30%) that kelts spent swimming upstream (searching behaviour) in the reservoir was a significant variable for migration success.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

Threshold dose for intravenous nicotine self-administration in young adult non-dependent smokers - R. Ross MacLean; Elise E. DeVito; Tore Eid; Suprit Parida; Ralitza Gueorguieva; Mehmet Sofuoglu (Psychopharmacology, 2021)

Dysfunctional mode switching between fixation and saccades: collaborative insights into two unusual clinical disorders - Janet C. Rucker; John-Ross Rizzo; Todd E. Hudson; Anja K. E. Horn; Jean A. Buettner-Ennever; R. John Leigh; Lance M. Optican (Journal of Computational Neuroscience, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Correction to: An evaluation of risk factors to predict target concentration non-attainment in critically ill patients prior to empiric β-lactam therapy - Sahand Imani; Hergen Buscher; Richard Day; Sheridan Gentili; Graham R. D. Jones; Debbie Marriott; Ross Norris; Indy Sandaradura (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Pharmaceutical design of a delivery system for the bacteriocin lacticin 3147 - Aoibhín Ryan; Pratikkumar Patel; Paula M. O’Connor; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2021)
Lacticin 3147 is a dual-acting two-peptide bacteriocin which is generally active against Gram-positive bacteria, including Listeria monocytogenes and antimicrobial-resistant bacteria such as Closteroides difficile in the colon. L. monocytogenes infections can cause life-long effects in the elderly and vulnerable and can cause severe complications in pregnant women. C. difficile causes one of the most common healthcare-associated infections and can be fatal in vulnerable groups such as the elderly. Although lacticin 3147 is degraded by intestinal proteases and has poor aqueous solubility, encapsulation of the bacteriocin could enable its use as an antimicrobial for treating these bacterial infections locally in the gastrointestinal tract. Lacticin 3147 displayed activity in aqueous solutions at a range of pH values and in gastric and intestinal fluids. Exposure to trypsin and α-chymotrypsin resulted in complete inactivation, implying that lacticin 3147 should be protected from these enzymes to achieve successful local delivery to the gastrointestinal tract. The amount of lacticin 3147 dissolved, i.e. its solution concentration, in water or buffered solutions at pH 1.6 and 7.4 was low and varied with time but increased and was stabilized in gastrointestinal fluids by the phospholipid and bile salt components present. Thus, the feasibility of a solid lipid nanoparticle (SLN) delivery system for local administration of lacticin 3147 was investigated. Bacteriocin activity was observed after encapsulation and release from a lipid matrix. Moreover, activity was seen after exposure to degrading enzymes. Further optimization of SLN delivery systems could enable the successful pharmaceutical development of active lacticin 3147 as an alternative to traditional antibiotics. Graphical abstract

Mandibular muscle troponin of the Florida carpenter ant Camponotus floridanus: extending our insights into invertebrate Ca2+ regulation - Yun Shi; Julia P. Bethea; Hannah L. Hetzel-Ebben; Maicon Landim-Vieira; Ross J. Mayper; Regan L. Williams; Lauren E. Kessler; Amanda M. Ruiz; Kathryn Gargiulo; Jennifer S. M. Rose; Grayson Platt; Jose R. Pinto; et al. (Journal of Muscle Research and Cell Motility, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Climate sensitivity of understory trees differs from overstory trees in temperate mesic forests - Christine R. Rollinson; M. Ross Alexander; Alex W. Dye; David J. P. Moore; Neil Pederson; Valerie Trouet (Ecology, 2021)
The response of understory trees to climate variability is key to understanding current and future forest dynamics. However, analyses of climatic effects on tree growth have primarily focused on the upper canopy, leaving understory dynamics unresolved. We analyzed differences in climate sensitivity based on canopy position of four common tree species ( Acer rubrum , Fagus grandifolia , Quercus rubra , and Tsuga canadensis ) using growth information from 1,084 trees across eight sites in the northeastern United States. Effects of canopy position on climate response varied, but were significant and often nonlinear, for all four species. Compared to overstory trees, understory trees showed stronger reductions in growth at high temperatures and varied shifts in precipitation response. This contradicts the prevailing assumption that climate responses, particularly to temperature, of understory trees are buffered by the overstory. Forest growth trajectories are uncertain in compositionally and structurally complex forests, and future demography and regeneration dynamics may be misinferred if not all canopy levels are represented in future forecasts.

Teneurin C-Terminal Associated Peptide (TCAP)-3 Increases Metabolic Activity in Zebrafish - Ross M. Reid; Andrea L. Reid; David A. Lovejoy; Peggy R. Biga (Frontiers in Marine Science, 2021)
Teneurin C-terminal associated peptides (TCAP), bioactive peptides located on the C-terminal end of teneurin proteins, have been shown to regulate stress axis functions due to the high conservation between TCAP and corticotropin releasing factor (CRF). Additionally, recent work demonstrated that TCAP can increase metabolism in rats via glucose metabolism. These metabolic actions are not well described in other organisms, including teleosts. Here we investigated the expression of a tcap isoform, tcap-3 , and the potential role of TCAP-3 as a regulator of metabolism across zebrafish life-stages. Using pcr-based analyses, tcap-3 appears to be independently transcribed, in relation to teneurin-3 , in muscle tissue of adult zebrafish. Resazurin, respirometry chambers, and mitochondrial metabolism analyses were used to study the metabolic effects of synthetic rainbow trout TCAP-3 (rtTCAP-3) in larval and adult zebrafish. Overall, metabolic activity was enhanced by 48 h of rtTCAP-3 treatment in larvae (bath immersion) and adults (intraperitoneal injections). This metabolic activity increase was due to mitochondrial uncoupling, as mitochondrial respiration increase by rtTCAP-3 was due to proton leak. Additionally, rtTCAP-3 protected larval fish from reduced metabolic activity induced by low temperatures. Subsequently, rtTCAP-3 increased metabolic output in adult zebrafish subjected to accelerated swimming speeds, demonstrating the potent role of rtTCAP-3 in zebrafish metabolism regulation during metabolic challenges. Collectively, these results demonstrate the conserved roles for rtTCAP-3 as a metabolic activator in zebrafish.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Exploring good cycling cities using multivariate statistics - Andrew J. Collins; Craig A. Jordan; R. Michael Robinson; Caitlin Cornelius; Ross Gore (Environment Systems and Decisions, 2020)

Metabolite pools of the reef building coral Montipora capitata are unaffected by Symbiodiniaceae community composition - Jennifer L. Matthews; Ross Cunning; Raphael Ritson-Williams; Clinton A. Oakley; Adrian Lutz; Ute Roessner; Arthur R. Grossman; Virginia M. Weis; Ruth D. Gates; Simon K. Davy (Coral Reefs, 2020)

Photothermal Floats for Evaporation Enhancement and Waterfowl Deterrence - Ross Monasmith; Grant Myhre; Jared Geer; Ryan Moe; Bryan Chamba Vasquez; Shyla Allred; Madison Cyr; Emma Wooldridge; Hans Swenson; Stella Capoccia; Dario Prieto Centurion; Courtney Young; et al. (Mine Water and the Environment, 2020)

Proper Adhesive Choice Increases Photothermal Float Durability in Mine Water Disposal Applications - Ross Monasmith; Katherine R. Zodrow (Mine Water and the Environment, 2020)

Basal resource quality and energy sources in three habitats of a lowland river ecosystem - Paul J. McInerney; Galen Holt; Rebecca E. Lester; Ross M. Thompson; Barbara Robson; Darren S. Ryder; Nick R. Bond; Darren S. Baldwin; Ben Gawne; Rochelle Petrie (Limnology and Oceanography, 2020)
Understanding energy flow through ecosystems and among sub‐habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats—river channels, anabranches and wetlands—of a lowland river floodplain in the Murray River catchment, Australia during a period of disconnected surface flow. We used a combination of stable isotope and fatty acid analyses to determine which basal resources were assimilated by the backswimmer Anisops thienemanni and the Eastern mosquitofish Gambusia holbrooki and assessed food quality across the three habitats. Seston was a primary basal resource for both animals in all three habitats, but was of higher quality within floodplain habitats than in the river channel. Although floodplain seston contained higher concentrations of essential fatty acids, fatty acid profiles of animals from different habitats remained similar. Our research suggests that inundation of floodplains and subsequent reconnection to the river could be valuable to afford riverine animals the opportunity to access high quality resources, but highlights a need to quantitatively assess the transfer of essential fatty acids between trophic levels to determine how much riverine animals are in fact limited by poorer quality food resources. We demonstrate the importance of estimating the quality of organic matter fluxes into food webs, and the potential role of targeted environmental flows to re‐establish high quality energy pathways in riverine ecosystems.

Correspondence between Breeding Values of the Same Pinus taeda L. Genotypes from Clonal Trials and Half-Sib Seedling Progeny Trials - Mohammad Nasir Shalizi; Salvador Alejandro Gezan; Steven E McKeand; Joshua R Sherrill; W Patrick Cumbie; Ross W Whetten; Fikret Isik (Forest Science, 2020)
The correspondence between breeding values of 65 loblolly pine (Pinus taeda L.) genotypes from clonal genetic tests and half-sib seedling progeny tests was studied in the southern United States. The two experiments were established separately, 10 years apart. Additive genetic variance estimates from clonal tests were larger compared with the estimates from the half-sib progeny tests, regardless of the covariance structure used in the statistical models and the traits. However, clone-mean and half-sib family-mean heritability estimates were comparable for all traits, ranging between 0.88 and 0.99. Based on the independent analysis, the correlation between the breeding values of the same genotypes from two propagule types was moderate (0.59) for tree height and stem volume. The combined analysis resulted in a strong genetic correlation (>0.93) between the breeding values of two propagule types. Herein the large discrepancy is mainly the outcome of different data analytical approaches. Conclusively, selecting genotypes for deployment based on clonal testing may not be optimal, but forest tree breeders can use the results from clonal tests to make some informed decisions.

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Diet of capelin (Mallotus villosus) in the Eastern Canadian Arctic inferred from stomach contents and stable isotopes - Wesley R. Ogloff; Steve H. Ferguson; Ross F. Tallman; Gail K. Davoren (Polar Biology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Why did the invasive walking catfish cross the road? Terrestrial chemoreception described for the first time in a fish - Noah R. Bressman; Jeffrey E. Hill; Miriam A. Ashley‐Ross (Journal of Fish Biology, 2020)
Clarias batrachus (walking catfish) is an invasive species in Florida, renowned for its air‐breathing and terrestrial locomotor capabilities. However, it is unknown how this species orients in terrestrial environments. Furthermore, while anecdotal life history information is widespread for this species in its nonnative range, little of this information exists in the literature. The goals of this study were to identify sensory modalities that C. batrachus use to orient on land, and to describe the natural history of this species in its nonnative range. Fish ( n = 150) were collected from around Ruskin, FL, and housed in a greenhouse, where experiments took place. Individual catfish were placed in the center of a terrestrial arena and were exposed to nine treatments: two controls, L‐alanine, quinine, allyl isothiocynate, sucrose, volatile hydrogen sulphide, pond water and aluminium foil. These fish exhibited significantly positive chemotaxis toward alanine and pond water, and negative chemotaxis away from volatile hydrogen sulphide, suggesting chemoreception – both through direct contact and through the air – is important to their terrestrial orientation. Additionally, 88 people from Florida wildlife‐related Facebook groups who have personal observations of C. batrachus on land were interviewed for information regarding their terrestrial natural history. These data were combined with observations from 38 YouTube videos. C. batrachus appear to emerge most frequently during or just after heavy summer rains, particularly from stormwater drains in urban areas, where they may feed on terrestrial invertebrates. By better understanding the full life history of C. batrachus , we can improve management of this species.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Experimental Assessment of Two Non-Contrast MRI Sequences Used for Computational Fluid Dynamics: Investigation of Consistency Between Techniques - C. J. MacDonald; R. Hellmuth; L. Priba; E. Murphy; S. Gandy; S. Matthew; R. Ross; J. G. Houston (Cardiovascular Engineering and Technology, 2020)
Purpose Recent studies have noted a degree of variance between the geometries segmented by different groups from 3D medical images that are used in computational fluid dynamics (CFD) simulations of patient-specific cardiovascular systems. The aim of this study was to determine if the applied sequence of magnetic resonance imaging (MRI) also introduced observable variance in CFD results. Methods Using a series of phantoms MR images of vessels of known diameter were assessed for the time-of-flight and multi-echo data image combination sequences. Following this, patient images of arterio-venous fistulas were acquired using the same sequences. Comparisons of geometry were made using the phantom and patient images, and of wall shear stress quantities using the CFD results from the patient images. Results Phantom images showed deviations in diameter between 0 and 15% between the sequences, depending on vessel diameter. Patient images showed different geometrical features such as narrowings that were not present on both sequences. Distributions of wall shear stress (WSS) quantities differed from simulations between the geometries obtained from the sequences. Conclusion In conclusion, choosing different MRI sequences resulted in slightly different geometries of the same anatomy, which led to compounded errors in WSS quantities from CFD simulation.

Assessing risks and mitigating impacts of harmful algal blooms on mariculture and marine fisheries - Andrew Ross Brown; Martin Lilley; Jamie Shutler; Chris Lowe; Yuri Artioli; Ricardo Torres; Elisa Berdalet; Charles R. Tyler (Reviews in Aquaculture, 2020)
Aquaculture is the fastest growing food sector globally and protein provisioning from aquaculture now exceeds that from wild capture fisheries. There is clear potential for the further expansion of marine aquaculture (mariculture), but there are associated risks. Some naturally occurring algae can proliferate under certain environmental conditions, causing deoxygenation of seawater, or releasing toxic compounds (phycotoxins), which can harm wild and cultured finfish and shellfish, and also human consumers. The impacts of these so‐called harmful algal blooms ( HAB s) amount to approximately 8 $billion/yr globally, due to mass mortalities in finfish, harvesting bans preventing the sale of shellfish that have accumulated unsafe levels of HAB phycotoxins and unavoided human health costs. Here, we provide a critical review and analysis of HAB impacts on mariculture (and wild capture fisheries) and recommend research to identify ways to minimise their impacts to the industry. We examine causal factors for HAB development in inshore versus offshore locations and consider how mariculture itself, in its various forms, may exacerbate or mitigate HAB risk. From a management perspective, there is considerable scope for strategic siting of offshore mariculture and holistic Environmental Approaches for Aquaculture, such as offsetting nutrient outputs from finfish farming, via the co‐location of extractive shellfish and macroalgae. Such pre‐emptive, ecosystem‐based approaches are preferable to reactive physical, chemical or microbiological control measures aiming to remove or neutralise HAB s and their phycotxins. To facilitate mariculture expansion and long‐term sustainability, it is also essential to evaluate HAB risk in conjunction with climate change.

Sampling, extraction and incidence of redberry mites (Acalitus essigi) on blackberries in Australia - Hui Meng Law; Geoff R. Allen; Jamie T. Davies; Ross Corkrey; Michele Buntain; Stephen R. Quarrell (Experimental and Applied Acarology, 2020)

Going Downriver: Patterns and Cues in Hurricane-Driven Movements of Common Snook in a Subtropical Coastal River - Jordan A. Massie; Bradley A. Strickland; Rolando O. Santos; Javiera Hernandez; Natasha Viadero; Ross E. Boucek; Hugh Willoughby; Michael R. Heithaus; Jennifer S. Rehage (Estuaries and Coasts, 2020)

Correction to: Using a Touchscreen Paradigm to Evaluate Food Preferences and Response to Novel Photographic Stimuli of Food in Three Primate Species (Gorilla gorilla gorilla, Pan troglodytes, and Macaca fuscata) - Sarah M. Huskisson; Sarah L. Jacobson; Crystal L. Egelkamp; Stephen R. Ross; Lydia M. Hopper (International Journal of Primatology, 2020)

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Strategies in herbivory by mammals revisited: The role of liver metabolism in a juniper specialist ( Neotoma stephensi ) and a generalist ( Neotoma albigula ) - Teri J. Orr; Smiljka Kitanovic; Katharina M. Schramm; Michele M. Skopec; P. Ross Wilderman; James R. Halpert; M. Denise Dearing (Molecular Ecology, 2020)
Although herbivory is widespread among mammals, few species have adopted a strategy of dietary specialization. Feeding on a single plant species often exposes herbivores to high doses of plant secondary metabolites (PSMs), which may exceed the animal's detoxification capacities. Theory predicts that specialists will have unique detoxification mechanisms to process high levels of dietary toxins. To evaluate this hypothesis, we compared liver microsomal metabolism of a juniper specialist, Neotoma stephensi (diet >85% juniper), to a generalist, N. albigula (diet ≤30% juniper). Specifically, we quantified the concentration of a key detoxification enzyme, cytochrome P450 2B (CYP2B) in liver microsomes, and the metabolism of α‐pinene, the most abundant terpene in the juniper species consumed by the specialist woodrat. In both species, a 30% juniper diet increased the total CYP2B concentration (2–3×) in microsomes and microsomal α‐pinene metabolism rates (4‐fold). In N. stephensi , higher levels of dietary juniper (60% and 100%) further induced CYP2B and increased metabolism rates of α‐pinene. Although no species‐specific differences in metabolism rates were observed at 30% dietary juniper, total microsomal CYP2B concentration was 1.7× higher in N. stephensi than in N. albigula ( p N. stephensi produces one or more variant of CYP2B that is less efficient at processing α‐pinene. In N. stephensi , the rates of α‐pinene metabolism increased with dietary juniper and were positively correlated with CYP2B concentration. The ability of N. stephensi to elevate CYP2B concentration and rate of α‐pinene metabolism with increasing levels of juniper in the diet may facilitate juniper specialization in this species.

Determining Coral Density Thresholds for Identifying Structurally Complex Vulnerable Marine Ecosystems in the Deep Sea - Ashley A. Rowden; Tabitha R. R. Pearman; David Anthony Bowden; Owen F. Anderson; Malcolm Ross Clark (Frontiers in Marine Science, 2020)

Using a Touchscreen Paradigm to Evaluate Food Preferences and Response to Novel Photographic Stimuli of Food in Three Primate Species (Gorilla gorilla gorilla, Pan troglodytes, and Macaca fuscata) - Sarah M. Huskisson; Sarah L. Jacobson; Crystal L. Egelkamp; Stephen R. Ross; Lydia M. Hopper (International Journal of Primatology, 2020)

A survey of the oral cavity microbiome of New Zealand fur seal pups ( Arctocephalus forsteri ) - Arsalan Emami‐Khoyi; Isma Benmazouz; James G. Ross; Laura J. Boren; Elaine C. Murphy; Bettine Jansen van Vuuren; Peter R. Teske; Adrian M. Paterson (Marine Mammal Science, 2020)

Minocycline does not affect experimental pain or addiction-related outcomes in opioid maintained patients - Caroline A. Arout; Andrew J. Waters; R. Ross MacLean; Peggy Compton; Mehmet Sofuoglu (Psychopharmacology, 2019)

Prolonged post-differentiation culture influences the expression and biophysics of Na+ and Ca2+ channels in induced pluripotent stem cell-derived ventricular-like cardiomyocytes - Gracious R. Ross; Farhan Rizvi; Larisa Emelyanova; A. Jamil Tajik; Arshad Jahangir (Cell and Tissue Research, 2019)

Assessing historical and future habitat models for four conservation‐priority Mojave Desert species - Ross J. Guida; Scott R. Abella; Chris L. Roberts; Carrie M. Norman; William J. Smith (Journal of Biogeography, 2019)
Aim Modelling and quantifying habitat changes using three historical field surveys for four Mojave Desert species and projecting future scenarios. Location Newberry Mountains, southern Nevada, USA. Methods Three vegetation field surveys were conducted, ending in 1979, 2008 and 2016, respectively. Field data collection across three time steps resulted in a unique dataset with 100 re‐surveyed 0.06‐ha plots. Using Maxent ecological niche modelling and 800‐m resolution Parameter Elevation Regressions on Independent Slopes Model (PRISM) temperature and precipitation data, habitat was assessed for four high‐elevation species. Recognizing that missing location data is a common challenge in species distribution modelling, sensitivity analysis was conducted utilizing three high‐elevation plots that species inhabited during the first two field surveys but that were unable to be sampled in 2016. Area under the curve for three species’ model runs exceeded 0.95, while one wider‐distributed species exceeded 0.79 for all runs. Future scenarios were also modelled under temperature increases and 16% and 0% reductions in precipitation. Results The number of presence locations and densities for Juniperus californica , Pinus monophylla , Quercus turbinella and Yucca schidigera decreased from 1979 to 2016, while their average elevational distribution increased. Using the 100 plots measured each of the three study years, models for all four species indicated decreases in potential suitable habitat ranging from 10% to 45%. When including the three highest elevation plots not re‐sampled in 2016, but likely still containing the modelled species, modelled habitat loss ranged from 0% to 29%. Future model projections show drastic reductions in the suitable habitat of all four modelled species. Main conclusions While many Maxent ecological modelling studies have been conducted, few have incorporated repeat surveys of identical plots as in our study. Model projections using a unique 100‐plot dataset suggest that suitable habitat area is contracting for the species studied, and this correlated with climatic warming and drying in the Mojave Desert. Despite model projections that show nearly complete loss of suitable habitat in 2053, care should be taken given uncertain estimates of the velocity of climate change and the slower pace of habitat contractions measured in the field.

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

Field investigation to measure airflow velocities of a ram dump car using circular routing at a Midwestern underground coal mine: a case study - W. R. Reed; M. Shahan; G. Ross; K. Singh; R. Cross; T. Grounds (Environmental Monitoring and Assessment, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Where do fish go when stranded on land? Terrestrial orientation of the mangrove rivulus Kryptolebias marmoratus - Noah R. Bressman; Mark Simms; Benjamin M. Perlman; Miriam A. Ashley‐Ross (Journal of Fish Biology, 2019)
The goal of the present study was to determine which sensory cues the mangrove rivulus Kryptolebias marmoratus , a quasi‐amphibious, hermaphroditic fish, uses to orient in an unfamiliar terrestrial environment. In a laboratory setting, K. marmoratus were placed on a terrestrial test arena and were provided the opportunity to move toward reflective surfaces, water, dark colours v . light colours, and orange colouration. Compared with hermaphrodites, males moved more often toward an orange section of the test arena, suggesting that the response may be associated with camouflage or male–male competition, since only males display orange colouration. Younger individuals also moved more often toward the orange quadrant than older individuals, suggesting age‐dependent orientation performance or behaviour. Sloped terrain also had a significant effect on orientation, with more movement downhill, suggesting the importance of the otolith‐vestibular system in terrestrial orientation of K. marmoratus . By understanding the orientation of extant amphibious fishes, we may be able to infer how sensory biology and behaviour might have evolved to facilitate invasion of land by amphibious vertebrates millions of years ago.

Radiological Estimation of Intracranial Blood Volume and Occurrence of Hydrocephalus Determines Stress-Induced Hyperglycemia After Aneurysmal Subarachnoid Hemorrhage - Joshua A Santucci; Stephen R Ross; John C Greenert; Faranak Aghaei; Lance Ford; Kimberly M Hollabaugh; Benjamin O Cornwell; Dee H Wu; Bin Zheng; Bradley N Bohnstedt; Bappaditya Ray (Translational Stroke Research, 2019)

The return of the frogs: The importance of habitat refugia in maintaining diversity during a disease outbreak - Donald T. McKnight; Monal M. Lal; Deborah S. Bower; Lin Schwarzkopf; Ross A. Alford; Kyall R. Zenger (Molecular Ecology, 2019)
Recent decades have seen the emergence and spread of numerous infectious diseases, often with severe negative consequences for wildlife populations. Nevertheless, many populations survive the initial outbreaks, and even undergo recoveries. Unfortunately, the long‐term effects of these outbreaks on host population genetics are poorly understood; to increase this understanding, we examined the population genetics of two species of rainforest frogs ( Litoria nannotis and Litoria serrata ) that have largely recovered from a chytridiomycosis outbreak at two national parks in the Wet Tropics of northern Australia. At the wetter, northern park there was little evidence of decreased genetic diversity in either species, and all of the sampled sites had high minor allele frequencies (mean MAF = 0.230–0.235), high heterozygosity (0.318–0.325), and few monomorphic markers (1.4%–4.0%); however, some recovered L. nannotis populations had low N e values (59.3–683.8) compared to populations that did not decline during the outbreak (1,537.4–1,756.5). At the drier, southern park, both species exhibited lower diversity (mean MAF = 0.084–0.180; heterozygosity = 0.126–0.257; monomorphic markers = 3.7%–43.5%; N e = 18.4–676.1). The diversity patterns in this park matched habitat patterns, with both species having higher diversity levels and fewer closely related individuals at sites with higher quality habitat. These patterns were more pronounced for L. nannotis, which has lower dispersal rates than L. serrata . These results suggest that refugia with high quality habitat are important for retaining genetic diversity during disease outbreaks, and that gene flow following disease outbreaks is important for re‐establishing diversity in populations where it was reduced.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Ontogenetic shifts in the nesting behaviour of female crocodiles - Cameron J. Baker; Craig E. Franklin; Hamish A. Campbell; Terri R. Irwin; Ross G. Dwyer (Oecologia, 2019)

Atmosphere oxygen cycling through the Proterozoic and Phanerozoic - Ross R. Large; Indrani Mukherjee; Dan Gregory; Jeff Steadman; Ross Corkrey; Leonid V. Danyushevsky (Mineralium Deposita, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Foraging in a social setting: a comparative analysis of captive gorillas and chimpanzees - Kristin E. Bonnie; Laura M. Bernstein-Kurtycz; Marisa A. Shender; Stephen R. Ross; Lydia M. Hopper (Primates, 2019)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

An evaluation of risk factors to predict target concentration non-attainment in critically ill patients prior to empiric β-lactam therapy - Sahand Imani; Hergen Buscher; Richard Day; Sheridan Gentili; Graham R. D. Jones; Debbie Marriott; Ross Norris; Indy Sandaradura (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Geochemistry of shale and sedimentary pyrite as a proxy for gold fertility in the Selwyn basin area, Yukon - Patrick J. Sack; Ross R. Large; Daniel D. Gregory (Mineralium Deposita, 2018)

Correction to: Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

Novel disturbance interactions between fire and an emerging disease impact survival and growth of resprouting trees - Allison B. Simler; Margaret R. Metz; Kerri M. Frangioso; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2018)
Human‐altered ecological disturbances may challenge system resilience and disrupt biological legacies maintaining ecosystem recovery. Yet, the extent to which novel regimes challenge these legacies varies. This may be partially explained by differences in the vulnerability of life history strategies to disturbance characteristics. In the fire‐prone, resprouter‐dominated coast redwood forests of California, the introduced disease sudden oak death (SOD) alters fuel profiles, fire behavior, and aboveground tree mortality; however, this system is dominated by resprouting trees that are well‐adapted to aboveground damage, and belowground survival of individuals may represent the principal biological legacy connecting pre‐ and post‐fire communities. Much of the research exploring altered disturbances and forest recovery has focused on legacies determined by seed dispersal and aboveground survival of adults. In this work, we use pre‐ and post‐fire data from a long‐term monitoring network to assess the impacts of novel disturbance interactions between wildfire and SOD on the belowground survival and vegetative reproduction of resprouters. We found that increasing accumulation of coarse woody surface fuels from SOD‐killed hosts decreased the likelihood of belowground survival for resprouting tanoak trees, but not for redwoods. Tanoaks' belowground survival was negatively related to substrate burn severity, which increased with the volume of surface fuels from hosts, suggesting heat damage as a possible mechanism influencing altered patterns of resprouter mortality. These impacts increased with decreasing tree size. By contrast, redwood and tanoak trees that survived both disturbances resprouted more vigorously, regardless of post‐fire infection by P. ramorum , and generated similar recruitment at the stand level. Our results demonstrate that disease–fire interactions can narrow recruitment filters for resprouters, which could impact long‐term population and demographic structure; yet, compounded disturbance may also reduce stand density and disease pressure, allowing competitive release of survivors. Resprouters displayed vulnerabilities to altered disturbance, but our research suggests that legacies maintained by resprouting may be more resilient to certain compounded disturbances, compared to seed‐obligate species, because of high rates of individual survival under increasingly severe events. These trends have important implications for conservation of declining tree species in SOD‐impacted forests, as well as predictions of human impacts in other disturbance‐prone systems where resprouters are present.

Aboveground carbon sequestration in dry temperate forests varies with climate not fire regime - Christopher E. Gordon; Eli R. Bendall; Mitchell G. Stares; Luke Collins; Ross A. Bradstock (Global Change Biology, 2018)
The storage of carbon in plant tissues and debris has been proposed as a method to offset anthropogenic increases in atmospheric [ CO 2 ]. Temperate forests represent significant above‐ground carbon ( AGC ) “sinks” because their relatively fast growth and slow decay rates optimise carbon assimilation. Fire is a common disturbance event in temperate forests globally that should strongly influence AGC because: discrete fires consume above‐ground biomass releasing carbon to the atmosphere, and the long‐term application of different fire‐regimes select for specific plant communities that sequester carbon at different rates. We investigated the latter process by quantifying AGC storage at 104 sites in the Sydney Basin Bioregion, Australia, relative to differences in components of the fire regime: frequency, severity and interfire interval. To predict the potential impacts of future climate change on fire/ AGC interactions, we stratified our field sites across gradients of mean annual temperature and precipitation and quantified within‐ and between‐factor interactions between the fire and climate variables. In agreement with previous studies, large trees were the primary AGC sink, accounting for ~70% of carbon at sites. Generalised additive models showed that mean annual temperature was the strongest predictor of AGC storage, with a 54% near‐linear decrease predicted across the 6.1°C temperature range experienced at sites. Mean annual precipitation, fire frequency, fire severity and interfire interval were consistently poor predictors of total above‐ground storage, although there were some significant relationships with component stocks. Our results show resilience of AGC to frequent and severe wildfire and suggest temperature mediated decreases in forest carbon storage under future climate change predictions.

Formation by silicate–fluoride + phosphate melt immiscibility of REE-rich globular segregations within aplite dikes - Charles R. Stern; Julien M. Allaz; Markus B. Raschke; G. Lang Farmer; M. Alexandra Skewes; Jeremy T. Ross (Contributions to Mineralogy and Petrology, 2018)

Lactobacillus spp. impair the ability of Listeria monocytogenes FBUNT to adhere to and invade Caco-2 cells - P. Castellano; M. Pérez Ibarreche; L. Longo Borges; F. C. Niño Arias; G. R. Ross; E. C. Pereira De Martinis (Biotechnology Letters, 2018)

Comparative genomics of Cp8viruses with special reference to Campylobacter phage vB_CjeM_los1, isolated from a slaughterhouse in Ireland - Lisa O’Sullivan; Alan Lucid; Horst Neve; Charles M. A. P. Franz; Declan Bolton; Olivia McAuliffe; R. Paul Ross; Aidan Coffey (Archives of Virology, 2018)

Minimizing opportunity costs to aquatic connectivity restoration while controlling an invasive species - Austin W. Milt; Matthew W. Diebel; Patrick J. Doran; Michael C. Ferris; Matthew Herbert; Mary L. Khoury; Allison T. Moody; Thomas M. Neeson; Jared Ross; Ted Treska; Jesse R. O'Hanley; Lisa Walter; et al. (Conservation Biology, 2018)
Controlling invasive species is critical for conservation but can have unintended consequences for native species and divert resources away from other efforts. This dilemma occurs on a grand scale in the North American Great Lakes, where dams and culverts block tributary access to habitat of desirable fish species and are a lynchpin of long‐standing efforts to limit ecological damage inflicted by the invasive, parasitic sea lamprey ( Petromyzon marinus ). Habitat restoration and sea‐lamprey control create conflicting goals for managing aging infrastructure. We used optimization to minimize opportunity costs of habitat gains for 37 desirable migratory fishes that arose from restricting sea lamprey access (0–25% increase) when selecting barriers for removal under a limited budget (US$1–105 million). Imposing limits on sea lamprey habitat reduced gains in tributary access for desirable species by 15–50% relative to an unconstrained scenario. Additional investment to offset the effect of limiting sea‐lamprey access resulted in high opportunity costs for 30 of 37 species (e.g., an additional US$20–80 million for lake sturgeon [ Acipenser fulvescens ]) and often required ≥5% increase in sea‐lamprey access to identify barrier‐removal solutions adhering to the budget and limiting access. Narrowly distributed species exhibited the highest opportunity costs but benefited more at less cost when small increases in sea‐lamprey access were allowed. Our results illustrate the value of optimization in limiting opportunity costs when balancing invasion control against restoration benefits for diverse desirable species. Such trade‐off analyses are essential to the restoration of connectivity within fragmented rivers without unleashing invaders.

Looking Without Landing—Using Remote Piloted Aircraft to Monitor Fur Seal Populations Without Disturbance - Rebecca R. McIntosh; Ross Holmberg; Peter Dann (Frontiers in Marine Science, 2018)

The biology, ecology and history of toheroa ( Paphies ventricosa ): a review of scientific, local and customary knowledge - P. M. Ross; M. P. Beentjes; J. Cope; W. P. de Lange; B. G. McFadgen; P. Redfearn; B. Searle; M. Skerrett; H. Smith; S. Smith; J. Te Tuhi; J. Tamihana; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
Toheroa ( Paphies ventricosa ) were formerly abundant on west and south‐facing New Zealand surf beaches. Harvesting of this surf clam was intense during the early to mid‐1900s, and populations declined to levels where harvesting was no longer viable. Despite having now been protected for 35–45 years, toheroa have failed to recover. This paper reviews the history of human interactions with toheroa and our understanding of their ecology, with a view to identifying knowledge requirements for management and restoration. Historical and legal documents pertaining to the use of marine resources are reviewed and scientific understanding compared with customary and local knowledge. We consider the factors that may be preventing toheroa recovery and make recommendations for research into life history, habitat requirements and the ecological consequences of changing land use. Management options are suggested to address the effects of vehicle use on beaches, poaching and the failings of the customary harvest system.

The microbiology and treatment of human mastitis - Angeliki Angelopoulou; Des Field; C. Anthony Ryan; Catherine Stanton; Colin Hill; R. Paul Ross (Medical Microbiology and Immunology, 2018)

Relative influences of multiple sources of uncertainty on cumulative and incremental tree-ring-derived aboveground biomass estimates - M. Ross Alexander; Christine R. Rollinson; Flurin Babst; Valerie Trouet; David J. P. Moore (Trees, 2018)

Sensory Evaluation of Eleven Baked Russet-type Potato Varieties and Clones - Rulon R. Spear; Zach J. Holden; C. F. Ross; B. J. Weddell; Mark J. Pavek (American Journal of Potato Research, 2018)

Role of cytochrome P450 2B sequence variation and gene copy number in facilitating dietary specialization in mammalian herbivores - Smiljka Kitanovic; Teri J. Orr; Daniel Spalink; Granger B. Cocke; Katharina Schramm; P. Ross Wilderman; James R. Halpert; M. Denise Dearing (Molecular Ecology, 2018)
Theory postulates that dietary specialization in mammalian herbivores is enabled by a specialized set of liver enzymes that process the high concentrations of similar plant secondary metabolites (PSMs) in the diets of specialists. To investigate whether qualitative and quantitative differences in detoxification mechanisms distinguish dietary specialists from generalists, we compared the sequence diversity and gene copy number of detoxification enzymes in two woodrat species: a generalist, the white‐throated woodrat ( Neotoma albigula ) and a juniper specialist, Stephens’ woodrat ( N. stephensi ). We focused on enzymes in the cytochrome P450 subfamily 2B (CYP2B), because previous research suggests this subfamily plays a key role in the processing of PSMs. For both woodrat species, we obtained and sequenced CYP2B cDNA, generated CYP2B phylogenies, estimated CYP2B gene copy number and created a homology model of the active site. We found that the specialist possessed on average ~5 more CYP2B gene copies than the generalist, but the specialist's CYP2B sequences were less diverse. Phylogenetic analysis of putative CYP2B homologs resolved woodrat species as reciprocally monophyletic and suggested evolutionary convergence of distinct homologs on similar key amino acid residues in both species. Homology modelling of the CYP2B enzyme suggests that interspecific differences in substrate preference and function likely result from amino acid differences in the enzyme active site. The characteristics of CYP2B in the specialist, that is greater gene copy number coupled with less sequence variation, are consistent with specialization to a narrow range of dietary toxins.

Historical biogeography of the palaeoendemic toad genus Oreophrynella (Amphibia: Bufonidae) sheds a new light on the origin of the Pantepui endemic terrestrial biota - Philippe J. R. Kok; Sebastian Ratz; Ross D. MacCulloch; Amy Lathrop; Raheleh Dezfoulian; Fabien Aubret; D. Bruce Means (Journal of Biogeography, 2018)
Aim Using the Pantepui palaeoendemic toad genus Oreophrynella , we explored (1) the origin of Pantepui endemism and the hypothesis of Pantepui being a source of diversity for the surrounding areas, including the geologically younger Andes; (2) whether early diversification of Oreophrynella conforms with that of Stefania (Hemiphractidae), another Pantepui endemic amphibian, which was recently shown to have vicariantly diverged from Pantepui highlands widespread Oligocene ancestors. Location The fractured island‐like topography of the Pantepui biogeographical region in north‐eastern South America. Methods We inferred the molecular phylogeny of Oreophrynella and other “basal” Bufonidae genera using three mitochondrial and two nuclear DNA sequences under Bayesian and maximum likelihood methods. We estimated divergence times using a relaxed‐clock model and reconstructed ancestral areas through multiple models in a common likelihood framework. Results Phylogenetic analyses recovered a monophyletic Oreophrynella sister to Atelopus . Biogeographical analyses strongly suggested colonization of Pantepui via a pre‐Miocene (Eocene/Oligocene) long‐distance dispersal of a proto‐Andean ancestor, followed by pre‐Quaternary (lower Miocene) vicariant divergences of main lineages, and endemism of these main lineages to distinct biogeographical subunits. Main conclusions Our results suggest that at least part of the Pantepui diversity stemmed from dispersals from the proto‐Andes. Three hypotheses emerge for the origin and evolution of Pantepui endemism, the Distance Dispersal theory, the Plateau theory and the Disturbance–Vicariance theory. Our results indicate that the early diversification of Oreophrynella conforms to that of Stefania , but hint at different factors responsible for the survival or extinction of different tepui summit amphibians.

Lack of Heterogeneity in Bacteriocin Production Across a Selection of Commercial Probiotic Products - J. W. Hegarty; C. M. Guinane; R. P. Ross; C. Hill; P. D. Cotter (Probiotics and Antimicrobial Proteins, 2017)

Effects of emerging infectious diseases on host population genetics: a review - Donald T. McKnight; Lin Schwarzkopf; Ross A. Alford; Deborah S. Bower; Kyall R. Zenger (Conservation Genetics, 2017)

Fighting an uphill battle: the recovery of frogs in Australia's Wet Tropics - Donald T. McKnight; Ross A. Alford; Conrad J. Hoskin; Lin Schwarzkopf; Sasha E. Greenspan; Kyall R. Zenger; Deborah S. Bower (Ecology, 2017)

Trophic state indicators are a better predictor of Florida bass condition compared to temperature in Florida’s freshwater bodies - Ross Boucek; Christian Barrientos; Michael R. Bush; David A. Gandy; Kyle L. Wilson; Joy M. Young (Environmental Biology of Fishes, 2017)

Can animal habitat use patterns influence their vulnerability to extreme climate events? An estuarine sportfish case study - Ross E. Boucek; Michael R. Heithaus; Rolando Santos; Philip Stevens; Jennifer S. Rehage (Global Change Biology, 2017)
Global climate forecasts predict changes in the frequency and intensity of extreme climate events ( ECE s). The capacity for specific habitat patches within a landscape to modulate stressors from extreme climate events, and animal distribution throughout habitat matrices during events, could influence the degree of population level effects following the passage of ECE s. Here, we ask (i) does the intensity of stressors of an ECE vary across a landscape? And (ii) Do habitat use patterns of a mobile species influence their vulnerability to ECE s? Specifically, we measured how extreme cold spells might interact with temporal variability in habitat use to affect populations of a tropical, estuarine‐dependent large‐bodied fish Common Snook , within Everglades National Park estuaries ( FL US ). We examined temperature variation across the estuary during cold disturbances with different degrees of severity, including an extreme cold spell. Second, we quantified Snook distribution patterns when the passage of ECE s is most likely to occur from 2012 to 2016 using passive acoustic tracking. Our results revealed spatial heterogeneity in the intensity of temperature declines during cold disturbances, with some habitats being consistently 3–5°C colder than others. Surprisingly, Snook distributions during periods of greatest risk to experience an extreme cold event varied among years. During the winters of 2013–2014 and 2014–2015 a greater proportion of Snook occurred in the colder habitats, while the winters of 2012–2013 and 2015–2016 featured more Snook observed in the warmest habitats. This study shows that Snook habitat use patterns could influence vulnerability to extreme cold events, however, whether Snook habitat use increases or decreases their vulnerability to disturbance depends on the year, creating temporally dynamic vulnerability. Faunal global change research should address the spatially explicit nature of extreme climate events and animal habitat use patterns to identify potential mechanisms that may influence population effects following these disturbances.

Imaging in Vascular Access - Eoin A. Murphy; Rose A. Ross; Robert G. Jones; Stephen J. Gandy; Nicolas Aristokleous; Marco Salsano; Jonathan R. Weir-McCall; Shona Matthew; John Graeme Houston (Cardiovascular Engineering and Technology, 2017)

Secular distribution of highly metalliferous black shales corresponds with peaks in past atmosphere oxygenation - Sean C. Johnson; Ross R. Large; Raymond M. Coveney; Karen D. Kelley; John F. Slack; Jeffrey A. Steadman; Daniel D. Gregory; Patrick J. Sack; Sebastien Meffre (Mineralium Deposita, 2017)

Distribution and socio-ecological impacts of the invasive alien cactus Opuntia stricta in eastern Africa - Ross T. Shackleton; Arne B. R. Witt; Francis M. Piroris; Brian W. van Wilgen (Biological Invasions, 2017)

New perspectives on the regulation of iron absorption via cellular zinc concentrations in humans - Marija Knez; Robin D. Graham; Ross M. Welch; James C. R. Stangoulis (Critical Reviews in Food Science and Nutrition, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Factors influencing the post-exercise hepcidin-25 response in elite athletes - Peter Peeling; Alannah K. A. McKay; David B. Pyne; Kym J. Guelfi; Rachel H. McCormick; Coby M. Laarakkers; Dorine W. Swinkels; Laura A. Garvican-Lewis; Megan L. R. Ross; Avish P. Sharma; Jill J. Leckey; Louise M. Burke (European Journal of Applied Physiology, 2017)

Whole grain in manufactured foods: Current use, challenges and the way forward - Christelle Schaffer-Lequart; Undine Lehmann; Alastair B. Ross; Olivier Roger; Alison L. Eldridge; Edwin Ananta; Marie-France Bietry; Luis R. King; Alice V. Moroni; Sathaporn Srichuwong; Anne-Sophie Wavreille; Robert Redgwell; et al. (Critical Reviews in Food Science and Nutrition, 2017)

Ecological niche partitioning within a large predator guild in a nutrient‐limited estuary - Philip Matich; Jerald S. Ault; Ross E. Boucek; David R. Bryan; Kirk R. Gastrich; Christine L. Harvey; Michael R. Heithaus; Jeremy J. Kiszka; Valeria Paz; Jennifer S. Rehage; Adam E. Rosenblatt (Limnology and Oceanography, 2017)
Within oligotrophic ecosystems, resource limitations coupled with interspecific variation in morphology, physiology, and life history traits may lead to niche partitioning among species. How generalist predators partition resources and their mechanisms, however, remain unclear across many ecosystems. We quantified niche partitioning among upper trophic level coastal and estuarine species: American alligators ( Alligator mississippiensis ), bull sharks ( Carcharhinus leucas ), common bottlenose dolphins ( Tursiops truncatus ), common snook ( Centropomus undecimalis ), and Atlantic tarpon ( Megalops atlanticus ) in the Shark River Estuary of the Florida Coastal Everglades, USA using acoustic telemetry, stable isotope analysis, and visual surveys, combined with published diet and life history demographic information. Spatial and isotopic niche overlap occurred among most species, with variability in partitioning among interspecific interactions. However, seasonal variability in habitat use, movements patterns, and trophic interactions may promote coexistence within this resource‐limited estuary. Beyond guild‐level niche partitioning, predators within the Shark River Estuary also exhibit partitioning within species through individual specializations and divergent phenotypes, which may lead to intraspecific variability in niche overlap with other predators. Niche differentiation expressed across multiple organizational levels (i.e., populations and communities) coupled with behavioral plasticity among predators in oligotrophic ecosystems may promote high species diversity despite resource limitations, which may be important when species respond to natural and human‐driven environmental change.

A metamorphic mineral source for tungsten in the turbidite-hosted orogenic gold deposits of the Otago Schist, New Zealand - Ben J. Cave; Iain K. Pitcairn; Dave Craw; Ross R. Large; Jay M. Thompson; Sean C. Johnson (Mineralium Deposita, 2017)

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Species‐specific responses to climate change and community composition determine future calcification rates of Florida Keys reefs - Remy R. Okazaki; Erica K. Towle; Ruben van Hooidonk; Carolina Mor; Rivah N. Winter; Alan M. Piggot; Ross Cunning; Andrew C. Baker; James S. Klaus; Peter K. Swart; Chris Langdon (Global Change Biology, 2017)
Anthropogenic climate change compromises reef growth as a result of increasing temperatures and ocean acidification. Scleractinian corals vary in their sensitivity to these variables, suggesting species composition will influence how reef communities respond to future climate change. Because data are lacking for many species, most studies that model future reef growth rely on uniform scleractinian calcification sensitivities to temperature and ocean acidification. To address this knowledge gap, calcification of twelve common and understudied Caribbean coral species was measured for two months under crossed temperatures (27, 30.3 °C) and CO 2 partial pressures ( p CO 2 ) (400, 900, 1300 μatm). Mixed‐effects models of calcification for each species were then used to project community‐level scleractinian calcification using Florida Keys reef composition data and IPCC AR 5 ensemble climate model data. Three of the four most abundant species, Orbicella faveolata, Montastraea cavernosa, and Porites astreoides , had negative calcification responses to both elevated temperature and p CO 2 . In the business‐as‐usual CO 2 emissions scenario, reefs with high abundances of these species had projected end‐of‐century declines in scleractinian calcification of >50% relative to present‐day rates. Siderastrea siderea , the other most common species, was insensitive to both temperature and p CO 2 within the levels tested here. Reefs dominated by this species had the most stable end‐of‐century growth. Under more optimistic scenarios of reduced CO 2 emissions, calcification rates throughout the Florida Keys declined S. siderea are not already dominant. This study demonstrates how species composition influences reef community responses to climate change and how reduced CO 2 emissions can limit future declines in reef calcification.

Connecting the trophic dots: responses of an aquatic bird species to variable abundance of macroinvertebrates in northern boreal wetlands - K. E. B. Gurney; R. G. Clark; S. M. Slattery; L. C. M. Ross (Hydrobiologia, 2017)

Evolution in the South American ‘Lost World’: insights from multilocus phylogeography of stefanias (Anura, Hemiphractidae, Stefania ) - Philippe J. R. Kok; Valerio G. Russo; Sebastian Ratz; D. Bruce Means; Ross D. MacCulloch; Amy Lathrop; Fabien Aubret; Franky Bossuyt (Journal of Biogeography, 2017)
Aim To investigate the influence of tepuian geomorphology on species diversification in the Pantepui biogeographical region based on the phylogenetic relationships and divergence times of tepui‐endemic clades of stefania frogs ( Stefania , Hemiphractidae). Location The ‘tepuis’ and uplands/lowlands of the Pantepui biogeographical region of northern South America, one of the least accessible and least studied areas in the world. Methods Two mitochondrial and two nuclear DNA sequences from 60 individuals of Stefania from 24 localities in Pantepui were employed to infer phylogenetic affinities and estimate divergence times within the genus using both concatenation and species tree analyses. Ancestral areas were inferred using multiple models in a common likelihood framework. Results Phylogenetic analyses revealed high diversity in the genus Stefania with 10 candidate species in the Eastern Pantepui District. Four strongly supported clades are recovered in the area, one being exclusively composed of microendemics on isolated tepui summits. Biogeographical analyses suggest episodes of fragmentation of widespread tepuian ancestors from the onset of diversification of the genus, estimated in the Oligocene ( c. 26 Ma), therefore suggesting a neglected vicariant model of Pantepui evolution, the Plateau Theory. Main conclusions Although our results suggest that vicariance played an important role in the diversification of Stefania , speciation in Pantepui followed an intricate pattern implying multiple nonexclusive processes. Vicariance and dispersal likely influenced diversification patterns of the Pantepui fauna, possibly according to the following sequence: (1) Cenozoic vicariance; (2) reorganization of species diversity due to periods of climatic instability; (3) recent invasions (Pleistocene) of widespread upland taxa.

Modelling Canopy Flows over Complex Terrain - Eleanor R. Grant; Andrew N. Ross; Barry A. Gardiner (Boundary-Layer Meteorology, 2016)

Evaluation of Immobilized Metal-Ion Affinity Chromatography and Electrospray Ionization Tandem Mass Spectrometry for Recovery and Identification of Copper(II)-Binding Ligands in Seawater Using the Model Ligand 8-Hydroxyquinoline - Richard L. Nixon; Andrew R. S. Ross (Frontiers in Marine Science, 2016)

Influence of the Mississippi River on Pseudo-nitzschia spp. Abundance and Toxicity in Louisiana Coastal Waters - Sibel Bargu; Melissa M. Baustian; Nancy N. Rabalais; Ross Del Rio; Benjamin Von Korff; R. Eugene Turner (Estuaries and Coasts, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Mixed population genomics support for the central marginal hypothesis across the invasive range of the cane toad ( Rhinella marina ) in Australia - Daryl R. Trumbo; Brendan Epstein; Paul A. Hohenlohe; Ross A. Alford; Lin Schwarzkopf; Andrew Storfer (Molecular Ecology, 2016)
Understanding factors that cause species' geographic range limits is a major focus in ecology and evolution. The central marginal hypothesis ( CMH ) predicts that species cannot adapt to conditions beyond current geographic range edges because genetic diversity decreases from core to edge due to smaller, more isolated edge populations. We employed a population genomics framework using 24 235–33 112 SNP loci to test major predictions of the CMH in the ongoing invasion of the cane toad ( Rhinella marina ) in Australia. Cane toad tissue samples were collected along broad‐scale, core‐to‐edge transects across their invasive range. Geographic and ecological core areas were identified using GIS and habitat suitability indices from ecological niche modelling. Bayesian clustering analyses revealed three genetic clusters, in the northwest invasion‐front region, northeast precipitation‐limited region and southeast cold temperature‐limited region. Core‐to‐edge patterns of genetic diversity and differentiation were consistent with the CMH in the southeast, but were not supported in the northeast and showed mixed support in the northwest. Results suggest cold temperatures are a likely contributor to southeastern range limits, consistent with CMH predictions. In the northeast and northwest, ecological processes consisting of a steep physiological barrier and ongoing invasion dynamics, respectively, are more likely explanations for population genomic patterns than the CMH .

Daily travel distances of zoo-housed chimpanzees and gorillas: implications for welfare assessments and space requirements - Stephen R. Ross; Marisa A. Shender (Primates, 2016)

A simple framework to quantitatively describe monthly precipitation and temperature climatology - Wouter R. Berghuijs; Ross A. Woods (International Journal of Climatology, 2016)
Climate descriptors and classifications are vital for ordering past, current and future climatic conditions. Yet, these parsimonious descriptors of climatic conditions only capture specific aspects of this climate signal, and lose all other information available in the observations. As a result, climate descriptions are often not physically insightful when they are applied in other studies. In this study, we show that a sinusoidal function with an annual period can adequately describe the vast majority of monthly precipitation and temperature climates around the world. This finding allows us to synthesize intra‐annual monthly precipitation and temperature climatology using five indices that are easy to interpret. The indices describe (1) the mean precipitation rate ( ), (2) the mean temperature ( ), (3) the seasonal precipitation amplitude ( δ P ), (4) the seasonal temperature amplitude (Δ T ) and (5) the phase difference between the precipitation and temperature regimes ( s d ). The combination of the five indices describes the relative time series of precipitation and temperature climatology, in contrast to earlier proposed similarity indices that only capture specific aspects of these time series. We demonstrate how the framework can reproduce many earlier proposed indices and classifications, and provide an example how the framework can be used to classify regions. We argue that the framework provides comprehensive insight into global climatology and can function as a quantitative conceptual basis for climate descriptions among different sciences.

Multicentric performance analysis of HCV quantification assays and its potential relevance for HCV treatment - F. Wiesmann; G. Naeth; A. Berger; H. H. Hirsch; S. Regenass; R. S. Ross; C. Sarrazin; H. Wedemeyer; H. Knechten; P. Braun (Medical Microbiology and Immunology, 2016)

Old but not ancient: coalescent species tree of New Caledonian geckos reveals recent post‐inundation diversification - Phillip L. Skipwith; Aaron M. Bauer; Todd R. Jackman; Ross A. Sadlier (Journal of Biogeography, 2016)
Aim New Caledonia is a remnant of the land mass Tasmantis that harbours high levels of endemism. Two primary hypotheses have been proposed for the origin of such endemic lineages; the first suggests a vicariant origin arising from the sundering of eastern Gondwana in the Cretaceous. The second posits more recent dispersal and colonization. We use concatenated and coalescent time‐calibrated phylogenies to test whether New Caledonian diplodactylid geckos diversified steadily following an ancient vicariance event or experienced an early burst of diversification followed by a decline in net diversification after long‐distance dispersal. Location New Caledonia, Gondwana. Methods Phylogenetic relationships were elucidated from a multilocus DNA data set. Divergence times were inferred using relaxed clock Bayesian methods on the concatenated data set and in a multispecies coalescent framework using * beast . In order to elucidate patterns of diversification for the New Caledonian clade we tested models of diversification using laser and ddd . Results The divergence of the New Caledonian clade from its Australian sister clade occurred well after Gondwanan fragmentation, and the age of the crown clade is younger than the proposed drowning period of the island. Diversification analyses strongly suggest that the group experienced an early burst of diversification, which has slowed towards the present. Main conclusions We demonstrate that the species‐rich diplodactylid geckos endemic to New Caledonia are of recent origin and that the diversification of the clade is consistent with the expectations of a recent radiation. Diversification in this clade does not conform to a constant‐rate model, but rather experienced an initial burst followed by a decline in net diversification. This pattern is consistent with a decline in diversification as ecological niche space was filled. Our results add to the growing body of evidence that recent adaptive radiations have contributed to the remarkable endemism of New Caledonia.

Ascochyta blight disease of pea (Pisum sativum L.): defence-related candidate genes associated with QTL regions and identification of epistatic QTL - Gail M. Timmerman-Vaughan; Leire Moya; Tonya J. Frew; Sarah R. Murray; Ross Crowhurst (Theoretical and Applied Genetics, 2016)

Comparing Postural Stability Entropy Analyses to Differentiate Fallers and Non-fallers - Peter C. Fino; Ahmad R. Mojdehi; Khaled Adjerid; Mohammad Habibi; Thurmon E. Lockhart; Shane D. Ross (Annals of Biomedical Engineering, 2016)

The diet of whiting Merlangius merlangus in the western Baltic Sea - S. D. Ross; H. Gislason; N. G. Andersen; P. Lewy; J. R. Nielsen (Journal of Fish Biology, 2016)
The diet of whiting Merlangius merlangus in the western Baltic Sea was investigated and compared to the diet in the southern North Sea. Clupeids were important prey in both areas, but especially in the western Baltic Sea where they constituted up to 90% of the diet of larger individuals. Gobies, brown shrimps and polychaetes were the main prey of juveniles in the western Baltic Sea, while a wider range of species were consumed in the North Sea. The shift to piscivory occurred at smaller sizes in the western Baltic Sea and the fish prey consumed was proportionately larger than in the southern North Sea. Estimates of prey abundance and food intake of M. merlangus are required to evaluate its predatory significance in the western Baltic Sea, but its diet suggests that it could be just as significant a fish predator here as in the southern North Sea.

Terrenolide S, a new antileishmanial butenolide from the endophytic fungus Aspergillus terreus - Ehab S. Elkhayat; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Samir A. Ross (Natural Product Research, 2016)

Enriched Groundwater Seeps in Two Vermont Headwater Catchments are Hotspots of Nitrate Turnover - Amninder J. Kaur; Donald S. Ross; James B. Shanley; Anna R. Yatzor (Wetlands, 2016)

Seafarers or castaways: ecological traits associated with rafting dispersal in tropical reef fishes - Osmar J. Luiz; Andrew P. Allen; D. Ross Robertson; Sergio R. Floeter; Joshua S. Madin (Journal of Biogeography, 2015)
Aim Rafting with natural flotsam is an important mechanism of long‐distance oceanic dispersal for many near‐shore marine organisms. Identifying the species‐level traits associated with this behaviour would aid in understanding and predicting a species' capacity for dispersal between isolated areas of benthic habitat. Location The tropical and subtropical Atlantic. Methods We assessed the relationships between species‐level traits (habitat use, position in water column, diet, body size, schooling activity) and rafting behaviour among 985 species of reef fish using generalized linear mixed‐effect modelling. To assess whether the relationships between rafting behaviour and species traits were mediated by raft type, our analysis included interactions between raft type and our predictor variables. Results The following species‐level traits are positively associated with rafting for reef fishes: (1) position in water column above reef substratum, which indicates a species' dependency on the substratum; (2) schooling behaviour, a trait linked to predation avoidance; (3) large adult size, which may be associated with enhanced survivorship and growth of rafting juveniles; and (4) broad habitat use, which may facilitate use of atypical habitats, including flotsam. Some correlations varied depending on the type of flotsam – broad habitat use is only positively correlated with the use of seaweed rafts, which may resemble patches of benthic macroalgal and seagrass beds that the reef fishes often use as ancillary habitat. In contrast, schooling behaviour is only positively correlated with rafting among logs and similar objects, perhaps because they represent poor refuges from predation. Main conclusions A species' propensity to use rafts is associated with specific ecological traits, some of which are contingent on characteristics of the raft. Thus, our findings suggest that increasing amounts of man‐made flotsam entering the ocean may differentially influence future rafting opportunities among tropical reef fishes, depending on their traits, which may have important implications for their biogeographical distributions.

Penguin activity influences soil biogeochemistry and soil respiration in rookeries on Ross Island, Antarctica - Becky A. Ball; Chelsey R. Tellez; Ross A. Virginia (Polar Biology, 2015)

Polybrominated diphenyl ethers from the marine organisms Lendenfeldia dendyi and Sinularia dura with anti-MRSa activity - Mohamed M. Radwan; Amira S. Wanas; Frank R. Fronczek; Melissa R. Jacob; Samir A. Ross (Medicinal Chemistry Research, 2015)

Field Observations of Canopy Flows over Complex Terrain - Eleanor R. Grant; Andrew N. Ross; Barry A. Gardiner; Stephen D. Mobbs (Boundary-Layer Meteorology, 2015)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Estimating heritability of disease resistance and factors that contribute to long-term survival in butternut (Juglans cinerea L.) - Nicholas R. LaBonte; Michael E. Ostry; Amy Ross-Davis; Keith E. Woeste (Tree Genetics & Genomes, 2015)

Inferring social structure from temporal data - Ioannis Psorakis; Bernhard Voelkl; Colin J. Garroway; Reinder Radersma; Lucy M. Aplin; Ross A. Crates; Antica Culina; Damien R. Farine; Josh A. Firth; Camilla A. Hinde; Lindall R. Kidd; Nicole D. Milligan; et al. (Behavioral Ecology and Sociobiology, 2015)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Geographic variation in polyandry of the Eastern Honey Bee, Apis cerana, in Thailand - D. S. DeFelice; C. Ross; M. Simone-Finstrom; N. Warrit; D. R. Smith; M. Burgett; P. Sukumalanand; O. Rueppell (Insectes Sociaux, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Zeaoxazolinone, a new antifungal agent from Zea mays roots - Gamal A. Mohamed; Sabrin R. M. Ibrahim; Mohamed S. A. Abdelkader; Nawal M. Al-Musayeib; Mohamed Ghoneim; Samir A. Ross (Medicinal Chemistry Research, 2014)

Evaluation of phytocannabinoids from high-potency Cannabis sativa using in vitro bioassays to determine structure–activity relationships for cannabinoid receptor 1 and cannabinoid receptor 2 - Afeef S. Husni; Christopher R. McCurdy; Mohamed M. Radwan; Safwat A. Ahmed; Desmond Slade; Samir A. Ross; Mahmoud A. ElSohly; Stephen J. Cutler (Medicinal Chemistry Research, 2014)

Pyrosequencing reveals regional differences in fruit‐associated fungal communities - Michael W. Taylor; Peter Tsai; Nicole Anfang; Howard A. Ross; Matthew R. Goddard (Environmental Microbiology, 2014)
Summary We know relatively little of the distribution of microbial communities generally. Significant work has examined a range of bacterial communities, but the distribution of microbial eukaryotes is less well characterized. Humans have an ancient association with grape vines ( V itis vinifera ) and have been making wine since the dawn of civilization, and fungi drive this natural process. While the molecular biology of certain fungi naturally associated with vines and wines is well characterized, complementary investigations into the ecology of fungi associated with fruiting plants is largely lacking. DNA sequencing technologies allow the direct estimation of microbial diversity from a given sample, avoiding culture‐based biases. Here, we use deep community pyrosequencing approaches, targeted at the 26 S rRNA gene, to examine the richness and composition of fungal communities associated with grapevines and test for geographical community structure among four major regions in N ew Z ealand ( NZ ). We find over 200 taxa using this approach, which is 10‐fold more than previously recovered using culture‐based methods. Our analyses allow us to reject the null hypothesis of homogeneity in fungal species richness and community composition across NZ and reveal significant differences between major areas.

Abundance of Latrodectus katipo Powell, 1871 is affected by vegetation type and season - Victoria R. Smith; Cor J. Vink; Ruedi G. Nager; James Ross; Adrian M. Paterson (Journal of Insect Conservation, 2014)

A comparison of potato seed-tuber sampling strategies using visual and DNA analyses to estimate incidence of major seed tuber-borne pathogens - Robert S. Tegg; Ross Corkrey; Calum R. Wilson (European Journal of Plant Pathology, 2014)

The Next Direction for Primatology? A Commentary on Setchell (2013) - Lydia M. Hopper; David B. Morgan; Stephen R. Ross (International Journal of Primatology, 2014)

Quantifying invasion resistance: the use of recruitment functions to control for propagule pressure - Alice L. Miller; Jeffrey M. Diez; Jon J. Sullivan; Steven R. Wangen; Susan K. Wiser; Ross Meffin; Richard P. Duncan (Ecology, 2014)
Invasive species distributions tend to be biased towards some habitats compared to others due to the combined effects of habitat‐specific resistance to invasion and non‐uniform propagule pressure. These two factors may also interact, with habitat resistance varying as a function of propagule supply rate. Recruitment experiments, in which the number of individuals recruiting into a population is measured under different propagule supply rates, can help us understand these interactions and quantify habitat resistance to invasion while controlling for variation in propagule supply rate. Here, we constructed recruitment functions for the invasive herb Hieracium lepidulum by sowing seeds at five different densities into six different habitat types in New Zealand's Southern Alps repeated over two successive years, and monitored seedling recruitment and survival over a four year period. We fitted recruitment functions that allowed us to estimate the total number of safe sites available for plants to occupy, which we used as a measure of invasion resistance, and tested several hypotheses concerning how invasion resistance differed among habitats and over time. We found significant differences in levels of H. lepidulum recruitment among habitats, which did not match the species' current distribution in the landscape. Local biotic and abiotic characteristics helped explain some of the between‐habitat variation, with vascular plant species richness, vascular plant cover, and light availability, all positively correlated with the number of safe sites for recruitment. Resistance also varied over time however, with cohorts sown in successive years showing different levels of recruitment in some habitats but not others. These results show that recruitment functions can be used to quantify habitat resistance to invasion and to identify potential mechanisms of invasion resistance.

Investigation of the Antimicrobial Activity of Bacillus licheniformis Strains Isolated from Retail Powdered Infant Milk Formulae - Avelino Alvarez-Ordóñez; Máire Begley; Tanya Clifford; Thérèse Deasy; Kiera Considine; Paula O’Connor; R. Paul Ross; Colin Hill (Probiotics and Antimicrobial Proteins, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Rapid evolution in response to increased temperature maintains population viability despite genetic erosion in a tropical ectotherm - Ross D. Breckels; Shawn R. Garner; Bryan D. Neff (Evolutionary Ecology, 2014)

Effect of Native Vegetation Loss on Stream Ecosystem Processes: Dissolved Organic Matter Composition and Export in Agricultural Landscapes - Darren P. Giling; Michael R. Grace; James R. Thomson; Ralph Mac Nally; Ross M. Thompson (Ecosystems, 2014)

The allure and peril of hematopoietic stem cell transplantation: overcoming immune challenges to improve success - Robert G. Newman; Duncan B. Ross; Henry Barreras; Samantha Herretes; Eckhard R. Podack; Krishna V. Komanduri; Victor L. Perez; Robert B. Levy (Immunologic Research, 2013)

Nutritional evaluation of autoclaved Salicornia bigelovii Torr. seed meal supplemented with varying levels of cholesterol on growth, nutrient utilization and survival of the Nile tilapia (Oreochromis niloticus) - M. G. Ríos-Durán; I. R. Valencia; L. G. Ross; C. A. Martínez-Palacios (Aquaculture International, 2013)

Morphology, gas exchange, and chlorophyll content of longleaf pine seedlings in response to rooting volume, copper root pruning, and nitrogen supply in a container nursery - R. Kasten Dumroese; Shi-Jean Susana Sung; Jeremiah R. Pinto; Amy Ross-Davis; D. Andrew Scott (New Forests, 2013)

Lupeol-3-O-decanoate, a new triterpene ester from Cadaba farinosa Forssk. growing in Saudi Arabia - Nawal M. Al-Musayeib; Gamal A. Mohamed; Sabrin R. M. Ibrahim; Samir A. Ross (Medicinal Chemistry Research, 2013)

Crustal architecture of the Capricorn Orogen, Western Australia and associated metallogeny - S. P. Johnson; A. M. Thorne; I. M. Tyler; R. J. Korsch; B. L. N. Kennett; H. N. Cutten; J. Goodwin; O. Blay; R. S. Blewett; A. Joly; M. C. Dentith; A. R. A. Aitken; et al. (Australian Journal of Earth Sciences, 2013)

Detecting hyperthermal stress in larvae of the hermatypic coral Porites astreoides: the suitability of using biomarkers of oxidative stress versus heat-shock protein transcriptional expression - K. Olsen; R. Ritson-Williams; J. D. Ochrietor; V. J. Paul; C. Ross (Marine Biology, 2013)

Unexpected redwood mortality from synergies between wildfire and an emerging infectious disease - Margaret R. Metz; J. Morgan Varner; Kerri M. Frangioso; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2013)
An under‐examined component of global change is the alteration of disturbance regimes due to warming climates, continued species invasions, and accelerated land‐use change. These drivers of global change are themselves novel ecosystem disturbances that may interact with historically occurring disturbances in complex ways. Here we use the natural experiment presented by wildfires in redwood forests impacted by an emerging infectious disease to demonstrate unexpected synergies of novel disturbance interactions. The dominant tree, coast redwood (fire resistant without negative disease impacts), experienced unexpected synergistic increases in mortality when fire and disease co‐occurred. The increased mortality risk, more than fourfold at the peak of the effect, was not predictable from impacts of either disturbance alone. Changes in fire behavior associated with changes to forest fuels that occurred through disease progression overwhelmed redwood's usual resilience to wildfire. Our results demonstrate the potential for interacting disturbances to initiate novel successional trajectories and compromise ecosystem resilience.

Polymorphisms and tissue expression of the feline leukocyte antigen class I loci FLAI-E, FLAI-H, and FLAI-K - Jennifer C. Holmes; Savannah G. Holmer; Peter Ross; Adam S. Buntzman; Jeffrey A. Frelinger; Paul R. Hess (Immunogenetics, 2013)

Towards improved socio-economic assessments of ocean acidification’s impacts - Nathalie Hilmi; Denis Allemand; Sam Dupont; Alain Safa; Gunnar Haraldsson; Paulo A. L. D. Nunes; Chris Moore; Caroline Hattam; Stéphanie Reynaud; Jason M. Hall-Spencer; Maoz Fine; Carol Turley; et al. (Marine Biology, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Spatially variable effects of a marine pest on ecosystem function - D. Jeff Ross; Andy R. Longmore; Michael J. Keough (Oecologia, 2013)

The in vitro pharmacological profile of TD-1211, a neutral opioid receptor antagonist - Pamela R. Tsuruda; Ross G. Vickery; Daniel D. Long; Scott R. Armstrong; David T. Beattie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

The in vivo pharmacodynamics of the novel opioid receptor antagonist, TD-1211, in models of opioid-induced gastrointestinal and CNS activity - Scott R. Armstrong; Christina B. Campbell; Carrie L. Richardson; Ross G. Vickery; Pamela R. Tsuruda; Daniel D. Long; Sharath S. Hegde; David T. Beattie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

A new isoflavone from Blepharis ciliaris of an Egyptian origin - Mohamed A. El-Shanawany; Hanaa M. Sayed; Sabrin R. M. Ibrahim; Marwa A. A. Fayed; Mohamed M. Radwan; Samir A. Ross (Medicinal Chemistry Research, 2013)

Effects of a competitive wrestling season on body composition, endocrine markers, and anaerobic exercise performance in NCAA collegiate wrestlers - Nicholas A. Ratamess; Jay R. Hoffman; William J. Kraemer; Ryan E. Ross; Christopher P. Tranchina; Stefanie L. Rashti; Neil A. Kelly; Jakob L. Vingren; Jie Kang; Avery D. Faigenbaum (European Journal of Applied Physiology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Short-term and latent post-settlement effects associated with elevated temperature and oxidative stress on larvae from the coral Porites astreoides - C. Ross; R. Ritson-Williams; K. Olsen; V. J. Paul (Coral Reefs, 2013)

Cyclodextrin-Crosslinked Poly(Acrylic Acid): Adhesion and Controlled Release of Diflunisal and Fluconazole from Solid Dosage Forms - Marguerite J. Kutyła; Michael W. Boehm; Jason R. Stokes; P. Nicholas Shaw; Nigel M. Davies; Ross P. McGeary; Jonathan Tuke; Benjamin P. Ross (AAPS PharmSciTech, 2013)

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Partial heat acclimation of athletes with spinal cord lesion - Paul C. Castle; B. Pasan Kularatne; John Brewer; Alexis R. Mauger; Ross A. Austen; James A. Tuttle; Nick Sculthorpe; Richard W. Mackenzie; Neil S. Maxwell; Anthony D. J. Webborn (European Journal of Applied Physiology, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Sea anemones may thrive in a high CO 2 world - David J. Suggett; Jason M. Hall‐Spencer; Riccardo Rodolfo‐Metalpa; Toby G. Boatman; Ross Payton; D. Tye Pettay; Vivienne R. Johnson; Mark E. Warner; Tracy Lawson (Global Change Biology, 2012)
Increased seawater p CO 2 , and in turn ‘ocean acidification’ (OA), is predicted to profoundly impact marine ecosystem diversity and function this century. Much research has already focussed on calcifying reef‐forming corals (Class: Anthozoa) that appear particularly susceptible to OA via reduced net calcification. However, here we show that OA‐like conditions can simultaneously enhance the ecological success of non‐calcifying anthozoans, which not only play key ecological and biogeochemical roles in present day benthic ecosystems but also represent a model organism should calcifying anthozoans exist as less calcified (soft‐bodied) forms in future oceans. Increased growth (abundance and size) of the sea anemone ( Anemonia viridis ) population was observed along a natural CO 2 gradient at Vulcano, Italy. Both gross photosynthesis ( P G ) and respiration (R) increased with p CO 2 indicating that the increased growth was, at least in part, fuelled by bottom up (CO 2 stimulation) of metabolism. The increase of P G outweighed that of R and the genetic identity of the symbiotic microalgae ( Symbiodinium spp.) remained unchanged (type A19) suggesting proximity to the vent site relieved CO 2 limitation of the anemones' symbiotic microalgal population. Our observations of enhanced productivity with p CO 2 , which are consistent with previous reports for some calcifying corals, convey an increase in fitness that may enable non‐calcifying anthozoans to thrive in future environments, i.e. higher seawater p CO 2 . Understanding how CO 2 ‐enhanced productivity of non‐ (and less‐) calcifying anthozoans applies more widely to tropical ecosystems is a priority where such organisms can dominate benthic ecosystems, in particular following localized anthropogenic stress.

Development and Advanced Validation of an Optimized Method for the Quantitation of Aβ42 in Human Cerebrospinal Fluid - Valerie C. Cullen; Ross A. Fredenburg; Cindy Evans; Phyllis R. Conliffe; Michael E. Solomon (The AAPS Journal, 2012)

Sleeping site selection by golden-backed uacaris, Cacajao melanocephalus ouakary (Pitheciidae), in Amazonian flooded forests - Adrian Ashton Barnett; Peter Shaw; Wilson R. Spironello; Ann MacLarnon; Caroline Ross (Primates, 2012)

Medical conditions and risk of adult myeloid leukemia - Kimberly J. Johnson; Cindy M. Blair; James M. Fink; James R. Cerhan; Michelle A. Roesler; Betsy A. Hirsch; Phuong L. Nguyen; Julie A. Ross (Cancer Causes & Control, 2012)

Comparison of the Potency of the Lipid II Targeting Antimicrobials Nisin, Lacticin 3147 and Vancomycin Against Gram-Positive Bacteria - Catalin Iancu; Aoife Grainger; Des Field; Paul D. Cotter; Colin Hill; R. Paul Ross (Probiotics and Antimicrobial Proteins, 2012)

The influences of climatic variation and vegetation on stream biota: lessons from the B ig D ry in southeastern A ustralia - James R. Thomson; Nick R. Bond; Shaun C. Cunningham; Leon Metzeling; Paul Reich; Ross M. Thompson; Ralph Mac Nally (Global Change Biology, 2012)
Aquatic biodiversity faces increasing threats from climate change, escalating exploitation of water and land use intensification. Loss of vegetation in catchments (= watersheds) has been identified as a substantial problem for many river basins, and there is an urgent need to better understand how climate change may interact with changes in catchment vegetation to influence the ecological condition of freshwater ecosystems. We used 20 years of biological monitoring data from V ictoria, southeastern A ustralia, to explore the influences of catchment vegetation and climate on stream macroinvertebrate assemblages. Southeastern A ustralia experienced a severe drought from 1997 to 2009, with reductions of stream flows >50% in some areas. The prolonged drying substantially altered macroinvertebrate assemblages, with reduced prevalence of many flow‐dependent taxa and increased prevalence of taxa that are tolerant of low‐flow conditions and poor water quality. Stream condition, as assessed by several commonly used macroinvertebrate indices, was consistently better in reaches with extensive native tree cover in upstream catchments. Prolonged drought apparently caused similar absolute declines in macroinvertebrate condition indices regardless of vegetation cover, but streams with intact catchment and riparian vegetation started in better condition and remained so throughout the drought. The largest positive effects of catchment tree cover on both water quality and macroinvertebrate assemblages occurred above a threshold of ca. 60% areal tree cover in upstream catchments and in higher rainfall areas. Riparian tree cover also had positive effects on macroinvertebrate assemblages, especially in warmer catchments. Our results suggest that the benefits of extensive tree cover via improved water quality and in‐channel habitat persist during drought and show the potential for vegetation management to reduce negative impacts of climatic extremes for aquatic ecosystems.

Opportunistic mimicry by a Jawfish - L. A. Rocha; R. Ross; G. Kopp (Coral Reefs, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Translational PK–PD modelling of molecular target modulation for the AMPA receptor positive allosteric modulator Org 26576 - Roberta Bursi; Gul Erdemli; Robert Campbell; Matthew M. Hutmacher; Thomas Kerbusch; David Spanswick; Ross Jeggo; Kari R. Nations; Peter Dogterom; Jacques Schipper; Mohammed Shahid (Psychopharmacology, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

Transition metal homeostasis: from yeast to human disease - Mark R. Bleackley; Ross T. A. MacGillivray (BioMetals, 2011)

Predicting Capacity Demand on Sanctuaries for African Chimpanzees (Pan troglodytes) - Lisa J. Faust; Doug Cress; Kay H. Farmer; Stephen R. Ross; Benjamin B. Beck (International Journal of Primatology, 2011)

Preferences for Timing of Wetland Loss Prevention in Louisiana - Daniel R. Petrolia; Ross G. Moore; Tae-goun Kim (Wetlands, 2011)

Thioarsenides: a case for long-range Lewis acid–base-directed van der Waals interactions - G. V. Gibbs; A. F. Wallace; R. T. Downs; N. L. Ross; D. F. Cox; K. M. Rosso (Physics and Chemistry of Minerals, 2011)

Further Identification of Novel Lantibiotic Operons Using LanM-Based Genome Mining - Orla O’Sullivan; Máire Begley; R. Paul Ross; Paul D. Cotter; Colin Hill (Probiotics and Antimicrobial Proteins, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Transfer and Acclimatization Effects on the Behavior of Two Species of African Great Ape (Pan troglodytes and Gorilla gorilla gorilla) Moved to a Novel and Naturalistic Zoo Environment - Stephen R. Ross; Katherine E. Wagner; Steven J. Schapiro; Jann Hau; Kristin E. Lukas (International Journal of Primatology, 2011)

Stepping in Elton’s footprints: a general scaling model for body masses and trophic levels across ecosystems - Jens O. Riede; Ulrich Brose; Bo Ebenman; Ute Jacob; Ross Thompson; Colin R. Townsend; Tomas Jonsson (Ecology Letters, 2011)
Ecology Letters (2011) 14: 169–178 Abstract Despite growing awareness of the significance of body‐size and predator–prey body‐mass ratios for the stability of ecological networks, our understanding of their distribution within ecosystems is incomplete. Here, we study the relationships between predator and prey size, body‐mass ratios and predator trophic levels using body‐mass estimates of 1313 predators (invertebrates, ectotherm and endotherm vertebrates) from 35 food‐webs (marine, stream, lake and terrestrial). Across all ecosystem and predator types, except for streams (which appear to have a different size structure in their predator–prey interactions), we find that (1) geometric mean prey mass increases with predator mass with a power‐law exponent greater than unity and (2) predator size increases with trophic level. Consistent with our theoretical derivations, we show that the quantitative nature of these relationships implies systematic decreases in predator–prey body‐mass ratios with the trophic level of the predator. Thus, predators are, on an average, more similar in size to their prey at the top of food‐webs than that closer to the base. These findings contradict the traditional Eltonian paradigm and have implications for our understanding of body‐mass constraints on food‐web topology, community dynamics and stability.

An adaptive gyroscope-based algorithm for temporal gait analysis - Barry R. Greene; Denise McGrath; Ross O’Neill; Karol J. O’Donovan; Adrian Burns; Brian Caulfield (Medical & Biological Engineering & Computing, 2010)

Changes in Atlantic salmon Salmo salar mucus components following short‐ and long‐term handling stress - R. H. Easy; N. W. Ross (Journal of Fish Biology, 2010)
This study examined changes in Atlantic salmon Salmo salar epidermal mucus proteins following short‐ and long‐term handling stress. Short‐term stress consisted of a single removal of fish from water for 15 s with long‐term stress consisting of daily removal of fish from water for 15 s over 21 days. In the long‐term handling stress study, there was a high level of individual variability with respect to mucus alkaline phosphatase, cathepsin B and lysozyme activities, with no correlation to treatment group. There was limited or no positive correlation between lysozyme, cathepsin B or alkaline phosphatase activities and plasma cortisol. There was a significant difference in lysozyme activity for both control and stressed fish at day 21 compared to other sampling days. In the short‐term study, there was again high variability in mucus enzyme activities with no difference observed between groups. Immunoblotting also showed variability in mucus actin breakdown products in both short‐ and long‐term handling stress studies. There appeared, however, to be a shift towards a more thorough breakdown of actin at day 14 in the stressed group. This shift suggested changes in mucus proteases in response to long‐term handling stress. In summary, there were correlations of some mucus enzyme/protein profiles with stress or cortisol; however, the variability in S. salar mucus enzyme levels and actin fragmentation patterns suggested other triggers for inducing changes in mucus protein composition that need to be investigated further in order to better understand the role of mucus in the response of S. salar to external stressors.

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Biodegradable Implants for Sustained Drug Release in the Eye - Susan S. Lee; Patrick Hughes; Aron D. Ross; Michael R. Robinson (Pharmaceutical Research, 2010)

Racial differences in PSA screening interval and stage at diagnosis - William R. Carpenter; Daniel L. Howard; Yhenneko J. Taylor; Louie E. Ross; Sara E. Wobker; Paul A. Godley (Cancer Causes & Control, 2010)

Evaluation of three portable blood lactate analysers: Lactate Pro, Lactate Scout and Lactate Plus - Rebecca K. Tanner; Kate L. Fuller; Megan L. R. Ross (European Journal of Applied Physiology, 2010)

Molecular sexing of African rhinoceros - Lindsay Peppin; Ross McEwing; Rob Ogden; Robert Hermes; Cindy Harper; Alan Guthrie; Gary R. Carvalho (Conservation Genetics, 2010)

Nutrient regulation of enteroendocrine cellular activity linked to cholecystokinin gene expression and secretion - K. N. Nilaweera; L. Giblin; R. P. Ross (Journal of Physiology and Biochemistry, 2010)

Genetic consequences of introducing allopatric lineages of Bluestriped Snapper ( Lutjanus kasmira ) to Hawaii - MICHELLE R. GAITHER; BRIAN W. BOWEN; ROBERT J. TOONEN; SERGE PLANES; VANESSA MESSMER; JOHN EARLE; D. ROSS ROBERTSON (Molecular Ecology, 2010)

Sediment and Nutrient Deposition Associated with Hurricane Wilma in Mangroves of the Florida Coastal Everglades - Edward Castañeda-Moya; Robert R. Twilley; Victor H. Rivera-Monroy; Keqi Zhang; Stephen E. Davis; Michael Ross (Estuaries and Coasts, 2010)

Low cancer incidence rates in Ohio Amish - Judith A. Westman; Amy K. Ferketich; Ross M. Kauffman; Steven N. MacEachern; J. R. Wilkins; Patricia P. Wilcox; Robert T. Pilarski; Rebecca Nagy; Stanley Lemeshow; Albert de la Chapelle; Clara D. Bloomfield (Cancer Causes & Control, 2010)

Genetic evaluation of marine biogeographical barriers: perspectives from two widespread Indo‐Pacific snappers ( Lutjanus kasmira and Lutjanus fulvus ) - Michelle R. Gaither; Robert J. Toonen; D. Ross Robertson; Serge Planes; Brian W. Bowen (Journal of Biogeography, 2010)
Aim In the Indo‐Pacific, the mass of islands of the Indonesian archipelago constitute a major biogeographical barrier (the Indo‐Pacific Barrier, IPB) separating the Pacific and Indian oceans. Evidence for other, more localized barriers include high rates of endemism at the Marquesas and other isolated peripheral islands in the Pacific. Here we use mitochondrial‐sequence comparisons to evaluate the efficacy of biogeographical barriers on populations of the snappers Lutjanus kasmira and Lutjanus fulvus across their natural ranges. Location Pacific and Indian oceans. Methods Mitochondrial cytochrome b sequence data were obtained from 370 individuals of L. kasmira and 203 individuals of L. fulvus collected from across each species’ range. Allele frequency data for two nuclear introns were collected from L. kasmira . Phylogenetic and population‐level analyses were used to determine patterns of population structure in these species and to identify barriers to dispersal. Results Lutjanus kasmira lacks genetic structure across the IPB and throughout 12,000 km of its central Indo‐Pacific range. In contrast, L. fulvus demonstrates high levels of population structure at all geographical scales. In both species, highly significant population structure results primarily from the phylogenetic distinctiveness of their Marquesas Islands populations ( L. kasmira , d = 0.50–0.53%; L. fulvus , d = 0.87–1.50%). Coalescence analyses of the L. kasmira data indicate that populations at opposite ends of its range (western Indian Ocean and the Marquesas) are the oldest. Coalescence analyses for L. fulvus are less robust but also indicate colonization from the Indian to the Pacific Ocean. Main conclusions The IPB does not act as a biogeographical barrier to L. kasmira , and, in L. fulvus , its effects are no stronger than isolating mechanisms elsewhere. Both species demonstrate a strong genetic break at the Marquesas. Population divergence and high endemism in that archipelago may be a product of geographical isolation enhanced by oceanographic currents that limit gene flow to and from those islands, and adaptation to unusual ecological conditions. Lutjanus kasmira shows evidence of Pleistocene population expansion throughout the Indo‐central Pacific that originated in the western Indian Ocean rather than the Marquesas, further demonstrating a strong barrier at the latter location.

Natural History of Innate Host Defense Peptides - A. Linde; B. Wachter; O. P. Höner; L. Dib; C. Ross; A. R. Tamayo; F. Blecha; T. Melgarejo (Probiotics and Antimicrobial Proteins, 2009)

The histone acetyltransferase GCN5 affects the inflorescence meristem and stamen development in Arabidopsis - Ross Cohen; John Schocken; Athanasios Kaldis; Konstantinos E. Vlachonasios; Amy T. Hark; Elizabeth R. McCain (Planta, 2009)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Dynamics of protein expression during pollen germination in canola (Brassica napus) - Inder S. Sheoran; Eric J. Pedersen; Andrew R. S. Ross; Vipen K. Sawhney (Planta, 2009)

Containment basin water quality fluctuation and implications for crop health management - Chuanxue Hong; John D. Lea-Cox; David S. Ross; Gary W. Moorman; Patricia A. Richardson; Sita R. Ghimire; Ping Kong (Irrigation Science, 2009)

Isolation and Analysis of Bacteria with Antimicrobial Activities from the Marine Sponge Haliclona simulans Collected from Irish Waters - Jonathan Kennedy; Paul Baker; Clare Piper; Paul D. Cotter; Marcella Walsh; Marlies J. Mooij; Marie B. Bourke; Mary C. Rea; Paula M. O’Connor; R. Paul Ross; Colin Hill; Fergal O’Gara; et al. (Marine Biotechnology, 2009)

Estuarine and Coastal Habitat Use of Gulf Sturgeon (Acipenser oxyrinchus desotoi) in the North-Central Gulf of Mexico - Stephen T. Ross; W. Todd Slack; Ryan J. Heise; Mark A. Dugo; Howard Rogillio; Bryant R. Bowen; Paul Mickle; Richard W. Heard (Estuaries and Coasts, 2009)

Indicators of abundance and spatial distribution of lobsters (Homarus americanus) from standard traps - M. John Tremblay; Carl Macdonald; Ross R. Claytor (New Zealand Journal of Marine and Freshwater Research, 2009)
Indicators of abundance for American lobster (Homarus americanus) based on 8 years of trap catch rates (catch‐per‐unit‐effort, CPUE) were evaluated. Volunteer harvesters recorded count, sex and size of lobsters captured in standard traps on a daily basis during the fishing season in coastal Nova Scotia, Canada. We examined the extent to which standardised CPUEs of prerecruits predict the future catches of legal sizes and explored spatial patterns in the abundance of lobsters of different size and reproductive status. The standardised CPUE of prerecruits was correlated with legal size catches in only one of five areas examined. This area had a strong signal of incoming recruitment. Improving the capacity of prerecruit CPUE for predicting legal size catches several years later most likely lies with model incorporation of variables associated with catchability. The spatial distribution of catch rates showed that the area with the highest historical landings per unit area also had the highest relative abundance of prerecruits. The spatial distribution data point to further areas of research related to recruitment processes in lobster in coastal Nova Scotia.

A case study of human exacerbation of the invasive species problem: transport and establishment of polygyne fire ants in Tallahassee, Florida, USA - Joshua R. King; Walter R. Tschinkel; Kenneth G. Ross (Biological Invasions, 2009)

Impact of the invasive cane toad (Bufo marinus) on an Australian frog (Opisthodon ornatus) depends on minor variation in reproductive timing - Michael R. Crossland; Ross A. Alford; Richard Shine (Oecologia, 2009)

Obstetric history and birth characteristics and Wilms tumor: a report from the Children’s Oncology Group - Julie L. Daniels; I-Jen Pan; Andrew F. Olshan; Norman E. Breslow; Greta R. Bunin; Julie A. Ross (Cancer Causes & Control, 2008)

Are Q ST – F ST comparisons for natural populations meaningful? - B. PUJOL; A. J. WILSON; R. I. C. ROSS; J. R. PANNELL (Molecular Ecology, 2008)
Comparisons between putatively neutral genetic differentiation amongst populations, F ST , and quantitative genetic variation, Q ST , are increasingly being used to test for natural selection. However, we find that approximately half of the comparisons that use only data from wild populations confound phenotypic and genetic variation. We urge the use of a clear distinction between narrow‐sense Q ST , which can be meaningfully compared with F ST , and phenotypic divergence measured between populations, P ST , which is inadequate for comparisons in the wild. We also point out that an unbiased estimate of Q ST can be found using the so‐called ‘animal model’ of quantitative genetics.

Contaminant Concentrations and Histopathological Effects in Sacramento Splittail (Pogonichthys macrolepidotus) - Ben K. Greenfield; Swee J. Teh; John R. M. Ross; Jennifer Hunt; GuoHua Zhang; Jay A. Davis; Gary Ichikawa; David Crane; Silas S. O. Hung; DongFang Deng; Foo-Ching Teh; Peter G. Green (Archives of Environmental Contamination and Toxicology, 2008)

Improved seasonal climate forecasts for the Caribbean region using the Florida State University Synthetic Superensemble - R. S. Ross; A. Chakraborty; A. Chen; L. Stefanova; S. Sirdas; T. N. Krishnamurti (Meteorology and Atmospheric Physics, 2007)

Exon size distribution and the origin of introns - Sigurbjorg Gudlaugsdottir; D. Ross Boswell; Graham R. Wood; Jun Ma (Genetica, 2007)

Frequency of sublethal injury in a deepwater ophiuroid, Ophiacantha bidentata, an important component of western Atlantic Lophelia reef communities - R. Allen Brooks; Martha S. Nizinski; Steve W. Ross; Kenneth J. Sulak (Marine Biology, 2007)

Potential protonation sites in the Al2SiO5 polymorphs based on polarized FTIR spectroscopy and properties of the electron density distribution - Jason B. Burt; Nancy L. Ross; G. V. Gibbs; George R. Rossman; Kevin M. Rosso (Physics and Chemistry of Minerals, 2007)

Replication profile of PCDH11X and PCDH11Y, a gene pair located in the non-pseudoautosomal homologous region Xq21.3/Yp11.2 - N. D. Wilson; L. J. N. Ross; J. Close; R. Mott; T. J. Crow; E. V. Volpi (Chromosome Research, 2007)

Hierarchical saturation of soil carbon pools near a natural CO 2 spring - DORIEN M. KOOL; HAEGEUN CHUNG; KEVIN R. TATE; DES J. ROSS; PAUL C. D. NEWTON; JOHAN SIX (Global Change Biology, 2007)
Soil has been identified as a possible carbon (C) sink to mitigate increasing atmospheric CO 2 concentration. However, several recent studies have suggested that the potential of soil to sequester C is limited and that soil may become saturated with C under increasing CO 2 levels. To test this concept of soil C saturation, we studied a gley and organic soil at a grassland site near a natural CO 2 spring. Total and aggregate‐associated soil organic C (SOC) concentration showed a significant increase with atmospheric CO 2 concentration. An asymptotic function showed a better fit of SOC and aggregation with CO 2 level than a linear model. There was a shift in allocation of total C from smaller size fractions to the largest aggregate fraction with increasing CO 2 concentration. Litter inputs appeared to be positively related to CO 2 concentration. Based on modeled function parameters and the observed shift in the allocation of the soil C from small to large aggregate‐size classes, we postulate that there is a hierarchy in C saturation across different SOC pools. We conclude that the asymptotic response of SOC concentration at higher CO 2 levels indicates saturation of soil C pools, likely because of a limit to physical protection of SOC.

Large losses of soil C and N from soil profiles under pasture in New Zealand during the past 20 years - L. A. SCHIPPER; W. T. BAISDEN; R. L. PARFITT; C. ROSS; J. J. CLAYDON; G. ARNOLD (Global Change Biology, 2007)
The conversion of two‐thirds of New Zealand's native forests and grasslands to agriculture has followed trends in other developed nations, except that pastoral grazing rather than cropping dominates agriculture. The initial conversion of land to pasture decreased soil acidity and elevated N and P stocks, but caused little change in soil organic C stocks. However, less is known about C and nutrient stock changes during the last two decades under long‐term pastoral management. We resampled 31 whole soil profiles in pastures spanning seven soil orders with a latitudinal range of 36–46°S, which had originally been sampled 17–30 years ago. We measured total C, total N, and bulk density for each horizon (generally to 1 m) and also reanalyzed archived soil samples of the same horizons for C and N. On average, profiles had lost significant amounts of C (− 2.1 kg C m −2 ) and N (− 0.18 kg N m −2 ) since initial sampling. Assuming a continuous linear decline in organic matter between sampling dates, significant losses averaged 106 g C m −2 yr −1 ( P =0.01) and 9.1 g N m −2 yr −1 ( P =0.002). Removal of C through leaching and erosion appears too small to explain these losses, suggesting losses from respiration exceed the inputs of photosynthate in the soil profile. These results emphasize that resampling soil profiles provide a robust method for detecting soil C changes, and add credence to the suggestion that soil C losses may be occurring in some temperate soil profiles. Further work is required to determine whether these losses are continuing and how losses might be extrapolated across landscapes to determine the implications for New Zealand's national CO 2 emissions and the sustainability of the implied rates of soil N loss.

Quantitative trait loci for phytate in rice grain and their relationship with grain micronutrient content - James C. R. Stangoulis; Bao-Lam Huynh; Ross M. Welch; Eun-Young Choi; Robin D. Graham (Euphytica, 2007)

Heterologous microarray experiments used to identify the early gene response to heat stress in a coral reef fish - KARIN S. KASSAHN; M. JULIAN CALEY; ALISTER C. WARD; ASHLEY R. CONNOLLY; GLENN STONE; ROSS H. CROZIER (Molecular Ecology, 2007)
Coral reef fishes are expected to experience rising sea surface temperatures due to climate change. How well tropical reef fishes will respond to these increased temperatures and which genes are important in the response to elevated temperatures is not known. Microarray technology provides a powerful tool for gene discovery studies, but the development of microarrays for individual species can be expensive and time‐consuming. In this study, we tested the suitability of a Danio rerio oligonucleotide microarray for application in a species with few genomic resources, the coral reef fish Pomacentrus moluccensis . Results from a comparative genomic hybridization experiment and direct sequence comparisons indicate that for most genes there is considerable sequence similarity between the two species, suggesting that the D. rerio array is useful for genomic studies of P. moluccensis . We employed this heterologous microarray approach to characterize the early transcriptional response to heat stress in P. moluccensis . A total of 111 gene loci, many of which are involved in protein processing, transcription, and cell growth, showed significant changes in transcript abundance following exposure to elevated temperatures. Changes in transcript abundance were validated for a selection of candidate genes using quantitative real‐time polymerase chain reaction. This study demonstrates that heterologous microarrays can be successfully employed to study species for which specific microarrays have not yet been developed, and so have the potential to greatly enhance the utility of microarray technology to the field of environmental and functional genomics.

Deep‐water chaunacid and lophiid anglerfishes (Pisces: Lophiiformes) off the south‐eastern United States - J. H. Caruso; S. W. Ross; K. J. Sulak; G. R. Sedberry (Journal of Fish Biology, 2007)
Recent research cruises to deep (80–910 m) reef habitats off the south‐eastern U.S. and in the northern Gulf of Mexico have provided new information on the diagnostic characteristics, behaviours, colour patterns in life, bottom associations, distributions and maximum sizes of species of the anglerfish genera Chaunax , Lophiodes and Sladenia . Chaunax stigmaeus occurred much further south than previously known (Blake Plateau off South Carolina), and all C. stigmaeus observed were found associated with dense beds of dead coral ( Lophelia pertusa ) rubble or on broken hard bottom. In contrast, Chaunax suttkusi was found on soft bottoms. Chaunax stigmaeus and C. suttkusi appear to be sympatric over a major portion of their ranges. Because knowledge of pigmentation in live or freshly caught Chaunax is critical to distinguish some members of the genus, changes in the colouration of C. suttkusi were noted and documented photographically immediately after death and after fixation. The yellow spots found on some, but not all specimens, temporarily disappeared completely after death, but they reappeared after fixation, slowly disappearing thereafter along with other carotenoid pigments. Lophiodes beroe and Lophiodes monodi were collected for the first time off the Atlantic coast of the U.S., being previously known only from the Gulf of Mexico, Caribbean Sea and the northern coast of South America. For both species ( L. beroe and L. monodi ), the collections included the two largest known representatives of the species (400 and 325 mm standard length, respectively). Lophiodes beroe commonly occurred on L. pertusa rubble, and seemed to prefer this habitat. Occupying such a habitat that is deep and difficult to sample probably explains how this common species escaped detection. Only a single L. monodi was collected or observed, so this species appears to be uncommon in this geographic area or at least so on coral rubble habitat. Detailed aspects of the colour patterns of both species were noted. In particular, L. beroe displayed a characteristic pattern of white patches in life that were not apparent after death. The first photographic documentation of the colour pattern in life and of the pharyngeal pigmentation of Lophiodes reticulatus is provided. The third known specimen of Sladenia shaefersi , and the first to be taken in U.S. waters was collected from coral rubble near the base of a steep 200 m scarp on the Blake Plateau.

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; Megan K. Laird; Blake B. Ross; David H. Vaughan; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; David H. Vaughan; Megan K. Laird; Blake B. Ross; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Genes flanking Xist in mouse and human are separated on the X chromosome in American marsupials - Alexander I. Shevchenko; Irina S. Zakharova; Eugeny A. Elisaphenko; Nicolay N. Kolesnikov; Siobhan Whitehead; Christine Bird; Mark Ross; Jennifer R. Weidman; Randy L. Jirtle; Tatiana V. Karamysheva; Nicolay B. Rubtsov; John L. VandeBerg; et al. (Chromosome Research, 2007)

A novel trinucleotide repeat expansion at chromosome 3q26.2 identified by a CAG/CTG repeat expansion detection array - S. E. Holmes; J. S. Wentzell; A. I. Seixas; C. Callahan; I. Silveira; C. A. Ross; R. L. Margolis (Human Genetics, 2006)

Complement-mediated activation of the adaptive immune responses - Franklin R. Toapanta; Ted M. Ross (Immunologic Research, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Breast-feeding and Wilms Tumor: A Report from the Children’s Oncology Group - Stephanie Saddlemire; Andrew F. Olshan; Julie L. Daniels; Norman E. Breslow; Greta R. Bunin; Julie A. Ross (Cancer Causes & Control, 2006)

Brook trout, Salvelinus fontinalis , microhabitat selection and diet under low summer stream flows - J. C. SOTIROPOULOS; K. H. NISLOW; M. R. ROSS (Fisheries Management and Ecology, 2006)
This study investigated the effects of low summer discharge on habitat, prey use and prey availability for age 1 brook trout, Salvelinus fontinalis (Mitchill), in two small streams in Massachusetts, USA. Stream discharge declined substantially from June to August, with corresponding decreases in microhabitat depth and velocity; but fish habitat preferences were consistent throughout the summer, with fish selecting deep, low current velocity locations. Invertebrate drift rate, drift density and trout stomach fullness were significantly greater in June than August samples. Diets were dominated by aquatic‐derived prey (chironomid larvae and adult blackflies) in June, but terrestrial invertebrates were the most frequent diet items in August. Consistent occupancy of low‐velocity, deep microhabitats with low invertebrate flux rates indicated that, despite variation in habitat and prey conditions, trout adopted a habitat‐use strategy of minimising risks and energy costs rather than maximising forage gain. This observation is consistent with, and provides a potential explanation for, the low summer growth rates of brook trout observed in small streams.

Soil and Hydrological Drivers of Typha latifolia Encroachment in a Marl Wetland - P. J. Drohan; C. N. Ross; J. T. Anderson; R. F. Fortney; J. S. Rentch (Wetlands Ecology and Management, 2006)

Bioinformatic and expression analysis of novel porcine β-defensins - Yongming Sang; Amar A. Patil; Guolong Zhang; Chris R. Ross; Frank Blecha (Mammalian Genome, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Characterization of TonB Interactions with the FepA Cork Domain and FecA N-terminal Signaling Domain - R. Sean Peacock; Valery V. Andrushchenko; A. Ross Demcoe; Matt Gehmlich; Lily Sia Lu; Alicia Garcia Herrero; Hans J. Vogel (BioMetals, 2006)

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Origin of the Nchanga copper–cobalt deposits of the Zambian Copperbelt - Ross R. McGowan; Stephen Roberts; Adrian J. Boyce (Mineralium Deposita, 2006)

The cystic fibrosis transmembrane conductance regulator gene and ion channel function in patients with idiopathic pancreatitis - Michele D. Bishop; Steven D. Freedman; Julian Zielenski; Najma Ahmed; Annie Dupuis; Sheelagh Martin; Lynda Ellis; Julie Shea; Isobel Hopper; Mary Corey; Paul Kortan; Gregory Haber; et al. (Human Genetics, 2005)

Weather and seasonal climate prediction for South America using a multi-model superensemble - Rosane R. Chaves; Robert S. Ross; T. N. Krishnamurti (International Journal of Climatology, 2005)

Recent invasion of the tropical Atlantic by an Indo‐Pacific coral reef fish - LUIZ A. ROCHA; D. ROSS ROBERTSON; CLAUDIA R. ROCHA; JAMES L. VAN TASSELL; MATTHEW T. CRAIG; BRIAN W. BOWEN (Molecular Ecology, 2005)
The last tropical connection between Atlantic and Indian–Pacific habitats closed c . 2 million years ago (Ma), with the onset of cold‐water upwelling off southwestern Africa. Yet comparative morphology indicates more recent connections in several taxa, including reef‐associated gobies (genus Gnatholepis ). Coalescence and phylogenetic analyses of mtDNA cytochrome b sequences demonstrate that Gnatholepis invaded the Atlantic during an interglacial period ∼145 000 years ago ( d = 0.0054), colonizing from the Indian Ocean to the western Atlantic, and subsequently to the central (∼100 000 years ago) and eastern Atlantic (∼30 000 years ago). Census data show a contemporary range expansion in the northeastern Atlantic linked to global warming.

Hormone replacement therapy is not associated with an increased risk of leukemia (United States) - Julie A. Ross; Penny J. Sinner; Cindy K. Blair; James R. Cerhan; Aaron R. Folsom (Cancer Causes & Control, 2005)

Reduction of forecast error for global numerical weather prediction by The Florida State University (FSU) Superensemble - R. S. Ross; T. N. Krishnamurti (Meteorology and Atmospheric Physics, 2005)

Novel microbial diversity adherent to plant biomass in the herbivore gastrointestinal tract, as revealed by ribosomal intergenic spacer analysis and rrs gene sequencing - Ross Larue; Zhongtang Yu; Victoria A. Parisi; Adrian R. Egan; Mark Morrison (Environmental Microbiology, 2005)
Summary It is well recognized that a dynamic biofilm develops upon plant biomass in the herbivore gastrointestinal tract, but this component of the microbiome has not previously been specifically sampled, or directly compared with the biodiversity present in the planktonic fraction of digesta. In this study, the digesta collected from four sheep fed two different diets was separated into three fractions: the planktonic phase, and the microbial populations either weakly or tightly adherent to plant biomass. The community DNA prepared from each fraction was then subjected to both ribosomal intergenic spacer analysis (RISA) and denaturing gradient gel electrophoresis (DGGE). Both types of analysis showed that dietary factors influence community structure, and that the adherent fractions produced more complex profiles. The RIS‐clone libraries prepared from the planktonic and adherent populations were then subjected to restriction fragment length polymorphism (RFLP) and DNA sequence analyses, which resulted in a far greater degree of discrimination among the fractions. Although many of the sequenced clones from the adherent populations were assigned to various clusters within the low G+C Gram‐positive bacteria, the clone libraries from animals consuming an all‐grass diet were largely comprised of novel lineages of Clostridium , while in animals consuming the starch‐containing diet, Selenomonas and Ruminococcus spp. were the dominant low G+C Gram‐positive bacteria. Additionally, the libraries from hay‐fed animals also contained clones most similar to asaccharolytic Clostridia, and other Gram‐positive bacteria that specialize in the transformation of plant phenolic compounds and the formation of cinnamic, phenylacetic and phenylpropionic acids. These results reveal, for the first time, the phylogeny of adherent subpopulations that specialize in the transformation of plant lignins and other secondary compounds, which potentiate polysaccharide hydrolysis by other members of the biofilm.

Lewis Ponds, a hybrid carbonate and volcanic-hosted polymetallic massive sulphide deposit, New South Wales, Australia - Michael W. Agnew; Ross R. Large; Stuart W. Bull (Mineralium Deposita, 2005)

Isolation and characterization of the bovine Stearoyl-CoAdesaturase promoter and analysis of polymorphisms in the promoter region in dairy cows - Aileen F. Keating; Catherine Stanton; John J. Murphy; Terry J. Smith; R. Paul Ross; Michael T. Cairns (Mammalian Genome, 2005)

Impacts of riparian afforestation on stream biofilms: An exotic forest‐native grassland comparison - Ross M. Thompson; Colin R. Townsend (New Zealand Journal of Marine and Freshwater Research, 2004)
The nature of benthic biofilm was assessed in four streams in New Zealand, two flowing through native tussock grassland and two through exotic Pinus radiata forest. Components of the biofilm were described using epi‐fluorescent staining (DAPI) and scanning electron microscopy (SEM) of rock and wood substrata. DAPI and SEM analyses showed significantly more bacteria and fungi on rock and wood in tussock as opposed to pine streams. This emphasises the importance of the heterotrophic community even in systems which have abundant light available for primary production. The lack of a significant heterotrophic biofilm in pine streams was unexpected, and we speculate that chemical characteristics of the water may be responsible.

Sorghum laxiflorum and S. macrospermum, the Australian native species most closely related to the cultivated S. bicolor based on ITS1 and ndhF sequence analysis of 25 Sorghum species - S. L. Dillon; P. K. Lawrence; R. J. Henry; L. Ross; H. J. Price; J. S. Johnston (Plant Systematics and Evolution, 2004)

Conservation genetics and demographic history of the endangered Cape Fear shiner ( Notropis mekistocholas ) - E. SAILLANT; J. C. PATTON; K. E. ROSS; J. R. GOLD (Molecular Ecology, 2004)
We examined allelic variation at 22 nuclear‐encoded markers (21 microsatellites and one anonymous locus) and mitochondrial (mt)DNA in two geographical samples of the endangered cyprinid fish Notropis mekistocholas (Cape Fear shiner). Genetic diversity was relatively high in comparison to other endangered vertebrates, and there was no evidence of small population effects despite the low abundance reported for the species. Significant heterogeneity (following Bonferroni correction) in allele distribution at three microsatellites and in haplotype distribution in mtDNA was detected between the two localities. This heterogeneity may be due to reduced gene flow caused by a dam built in the early 1900s. Bayesian coalescent analysis of microsatellite variation indicated that effective population size of Cape Fear shiners has declined in recent times (11–25 435 years ago, with highest posterior probabilities between 126 and 2007 years ago) by one–two orders of magnitude, consistent with the observed decline in abundance of the species. A decline in effective size was not indicated by analysis of mtDNA, where sequence polymorphism appeared to carry the signature of an older expansion phase that dated to the Pleistocene (∼12 700 > 1 million years ago). Cape Fear shiners thus appear to have undergone an expansion phase following a glacial cycle but to have declined significantly in more recent times. These results suggest that rapidly evolving markers such as microsatellites may constitute a suitable tool when inferring recent demographic dynamics of populations.

“Candidatus Phytoplasma australiense” in Coprosma robusta in New Zealand - Ross E. Beever; Garry A. Wood; Mark T. Andersen; Shaun R. Pennycook; Paul W. Sutherland; Richard L. S. Forster (New Zealand Journal of Botany, 2004)
A phytoplasma is reported from wild plants of Coprosma robusta, where it is associated with leaf reddening or bronzing and dieback of shoots and branches. It was detected by electron microscopy of phloem tissue, and by one‐step and nested PCR using phytoplasma‐specific primers targeting the 16S rRNA gene. The sequence of the 16S product closely matches that of the Phormium yellow leaf phytoplasma and places the phytoplasma in the putative species “Candidatus Phytoplasma australiense”. It was transmitted by grafting to C. robusta and C. macrocarpa. The symptoms of the disease caused by the phytoplasma ( Coprosma lethal decline) in clonally matched graft‐inoculated versus ungrafted cuttings of C. robusta included interveinal chlorosis and abnormal leaf yellowing or reddening, slowing of growth, and shoot dieback. A field survey of C. robusta indicated that shoot dieback and abnormal leaf coloration are common throughout much of New Zealand. “Ca. P. australiense” was detected in some, but not all, symptomatic plants, indicating it may play a role in causing such symptoms in the field. It is proposed that infected C. robusta plants provide a reservoir of “Ca. P. australiense” that leads to infection of other hosts.

Tilting and distortion of CaSnO 3 perovskite to 7 GPa determined from single-crystal X-ray diffraction - J. Zhao; N. L. Ross; R. J. Angel (Physics and Chemistry of Minerals, 2004)

An auxin-inducible gene from loblolly pine ( Pinus taeda L.) is differentially expressed in mature and juvenile-phase shoots and encodes a putative transmembrane protein - Victor B. Busov; Eva Johannes; Ross W. Whetten; Ronald R. Sederoff; Steven L. Spiker; Carmen Lanz-Garcia; Barry Goldfarb (Planta, 2004)

Interaction and impacts of two introduced species on a soft-sediment marine assemblage in SE Tasmania - D. J. Ross; C. R. Johnson; C. L. Hewitt; G. M. Ruiz (Marine Biology, 2004)

Mass flow sedimentology within the HYC Zn?Pb?Ag deposit, Northern Territory, Australia: evidence for syn-sedimentary ore genesis - Tim Ireland; Stuart W. Bull; Ross R. Large (Mineralium Deposita, 2004)

Dormancy termination of western white pine ( Pinus monticola Dougl. Ex D. Don) seeds is associated with changes in abscisic acid metabolism - J. Allan Feurtado; Stephen J. Ambrose; Adrian J. Cutler; Andrew R. S. Ross; Suzanne R. Abrams; Allison R. Kermode (Planta, 2004)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

VARIABILITY IN THE DIET OF HARBOR PORPOISES ( PHOCOENA PHOCOENA ) IN SCOTTISH WATERS 1992–2003 - M. B. Santos; G. J. Pierce; J. A. Learmonth; R. J. Reid; H. M. Ross; I. A. P. Patterson; D. G. Reid; D. Beare (Marine Mammal Science, 2004)
A bstract Interannual, seasonal, and regional variation in the diet of porpoises, Phocoena phocoena , in Scottish (UK) waters was studied using stomach contents of animals stranded between 1992 and 2003. Most samples came from the east coast (including many porpoises killed by bottlenose dolphins), with smaller numbers from the west coast and from Shetland. The most important prey types, in terms of contribution by number and mass, were whiting ( Merlangius merlangus ) and sand eels (Ammodytidae). Multivariate analysis confirmed the existence of regional, seasonal, and interannual variation in diet, as well as differences ( i. e. , biases) related to cause of death. These differences were further explored using univariate analyses. Sand eels were more important in the summer months (quarters 2 and 3) and on the east coast, whereas gadids were more important in winter and in the Shetland area. Some, but not all, observed trends in the numerical importance and size of prey taken were consistent with trends in abundance and size of fish taken during research trawl surveys. There was some evidence that porpoises Clupea harengus and sprat Sprattus sprattus ) formed a relatively small proportion of the diet, but their importance varied from year to year. Although possible methodological biases prevent firm conclusions, it appears that the importance of clupeids in porpoise diet may have decreased since the 1960s, mirroring the decline in North Sea herring abundance. The recovery of the North Sea herring stock in recent years is not as yet reflected in porpoise diet.

Characterisation of PtMYB1, an R2R3-MYB from pine xylem - Astrid Patzlaff; Lisa J. Newman; Christian Dubos; Ross W. Whetten; Caroline Smith; Stephanie McInnis; Michael W. Bevan; Ronald R. Sederoff; Malcolm M. Campbell (Plant Molecular Biology, 2003)

Growth of larval krill, Euphausia superba , in fall and winter west of the Antarctic Peninsula - L. B. Quetin; R. M. Ross; T. K. Frazer; M. O. Amsler; C. Wyatt-Evens; S. A. Oakes (Marine Biology, 2003)

Krill ( Euphausia superba ) recruitment indices from the western Antarctic Peninsula: are they representative of larger regions? - V. Siegel; R. M. Ross; L. B. Quetin (Polar Biology, 2003)

Mechanisms for changes in soil carbon storage with pasture to Pinus radiata land‐use change - Joanne C. Halliday; Kevin R. Tate; Ross E. McMurtrie; Neal A. Scott (Global Change Biology, 2003)
In this study, we simulated pasture to Pinus radiata land‐use change with the G eneric D ecomposition A nd Y ield (G'DAY) ecosystem model to examine mechanisms responsible for the change in soil carbon (C) under pine. We parameterized the model for paired sites in New Zealand. Our simulations successfully reproduced empirical trends in ecosystem productivity and soil inorganic nitrogen (N), and modeled an increase in soil C and a small decline in soil N after 30 years under pine. We determined the mechanisms contributing to soil C change based on an established hypothesis that attributes increases in soil C storage to three main factors: increased ecosystem N inputs relative to outputs, increased C/N ratios in plant and soil, or a shift of N from plant to soil. The mechanisms we attributed to the simulated increase in soil C under pine were increased soil C inputs through tree litterfall, and an increase in the soil C/N ratio. In the first 7 years following pine establishment, a decline in soil C was simulated; this was matched by a decline in soil N. The simulated longer‐term increase in soil C with afforestation by pine contrasts with results from published field studies, which show either a decline or no change in soil C under pine. The discrepancy between measured and simulated changes in soil C was attributed to the G'DAY model overestimating the transfer of litter C into the mineral soil.

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

The use of PNAs and their derivatives in mitochondrial gene therapy - P. M. Smith; G. F. Ross; T. M. Wardell; R. W. Taylor; D. M. Turnbull; R. N. Lightowlers (International Journal of Peptide Research and Therapeutics, 2003)

The electron localization function: a tool for locating favorable proton docking sites in the silica polymorphs - G. V. Gibbs; D. F. Cox; M.B. Boisen; R. T. Downs; N. L. Ross (Physics and Chemistry of Minerals, 2003)

An arabinogalactan protein associated with secondary cell wall formation in differentiating xylem of loblolly pine - Yi Zhang; Garth Brown; Ross Whetten; Carol A. Loopstra; David Neale; Marcia J. Kieliszewski; Ronald R. Sederoff (Plant Molecular Biology, 2003)

The use of PNAs and their derivatives in mitochondrial gene therapy - P. M. Smith; G. F. Ross; T. M. Wardell; R. W. Taylor; D. M. Turnbull; R. N. Lightowlers (International Journal of Peptide Research and Therapeutics, 2003)

Assessing the ecological impacts of an introduced seastar: the importance of multiple methods - D. Jeff Ross; Craig R. Johnson; Chad L. Hewitt (Biological Invasions, 2003)

Seasonal variation in the reproductive activity and biochemical composition of the Pacific oyster (Crassostrea gigas) from the Marlborough Sounds, New Zealand - Jeffrey S. Ren; Islay D. Marsden; Alex H. Ross; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2003)
Reproductive cycles of the Pacific oyster Crassostrea gigas (Thunberg) from the Marlborough Sounds, New Zealand, were followed between June 1998 and January 2000. Histological examination of the gonad confirms an annual cycle with a winter inactive period followed by rapid gonad development and a single short spawning period. The population gonad index correlated with seawater temperature and changes in tissue dry weight, condition index, and biochemical components. In winter, few individuals with early gametogenic stages were present and rapid development of primary oocytes (diam. 11 μm) occurred during spring (September‐November). The developmental rate and the diameter of mature oocytes (37 μm) was similar for the 1998 and 1999 seasons. For a standard 110‐mm‐length oyster, maximal tissue body weight and condition index were recorded in December. Rapid weight loss in January was length dependent and was attributed to spawning. Temperature was the environmental variable which best correlated with the timing of gametogenesis. Food availability (phytoplankton biomass) may have been responsible for inter‐annual variations. The biochemical composition (% glycogen, lipid, protein) of separated gonad and somatic tissues were variable seasonally and annually. Gametogenesis (oocyte diameter) was associated with increased gonad protein and glycogen and a decrease in lipid concentrations. These changes are similar to those in Pacific oyster populations from other parts of the world.

Raman scattering and X-ray diffraction study of the thermal decomposition of an ettringite-group crystal - R. A. Livingston; P. J. M. Monteiro; S. K. Deb; M. H. Manghnani; K. Ross (Physics and Chemistry of Minerals, 2003)

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

Correlates of vitamin supplement use in the United States: data from the California Teachers Study cohort - K.J. Hoggatt; L. Bernstein; P. Reynolds; H. Anton-Culver; D. Deapen; D. Peel; R. Pinder; R.K. Ross; D.W. West; W. Wright; A. Ziogas; P.L. Horn-Ross (Cancer Causes & Control, 2002)

Geology of the Atlantis Massif (Mid-Atlantic Ridge, 30° N): Implications for the evolution of an ultramafic oceanic core complex - Donna K. Blackman; Jeffrey A. Karson; Deborah S. Kelley; Johnson R. Cann; Gretchen L. Früh-Green; Jeffrey S. Gee; Stephen D. Hurst; Barbara E. John; Jennifer Morgan; Scott L. Nooner; D. Kent Ross; Timothy J. Schroeder; et al. (Marine Geophysical Research, 2002)

Global Distribution of Halogenated Dimethyl Bipyrroles in Marine Mammal Blubber - S. Tittlemier; A. Borrell; J. Duffe; P. J. Duignan; P. Fair; A. Hall; P. Hoekstra; K. M. Kovacs; M. M. Krahn; M. Lebeuf; C. Lydersen; D. Muir; et al. (Archives of Environmental Contamination and Toxicology, 2002)

Lantibiotics produced by lactic acid bacteria: structure, function and applications - Denis Twomey; R. P. Ross; Maire Ryan; Billy Meaney; C. Hill (Antonie van Leeuwenhoek, 2002)

Bacteriophage-resistance systems in dairy starter strains: molecular analysis to application - Aidan Coffey; R. Paul Ross (Antonie van Leeuwenhoek, 2002)

Recent diet and breast cancer risk: the California Teachers Study (USA) - Pamela L. Horn-Ross; K.J. Hoggatt; Dee W. West; Melissa R. Krone; Susan L. Stewart; Hoda Anton-Culver; Leslie Bernstein; Dennis Deapen; David Peel; Richard Pinder; Peggy Reynolds; Ronald K. Ross; et al. (Cancer Causes & Control, 2002)

Decomposability of C3 and C4 grass litter sampled under different concentrations of atmospheric carbon dioxide at a natural CO2 spring - D. J. Ross; K. R. Tate; P. C. D. Newton; H. Clark (Plant and Soil, 2002)

Genetic, physical, and comparative map of the subtelomeric region of mouse Chromosome 4 - Xia Li; Alexander A. Bachmanov; Shanru Li; Zhenyu Chen; Michael G. Tordoff; Gary K. Beauchamp; Pieter J. de Jong; Chenyan Wu; Lianchun Chen; David B. West; David A. Ross; Jeffery D. Ohmen; et al. (Mammalian Genome, 2002)

Commentary: phenotypic screening of radiation hybrid panels - Susan R. Ross (Mammalian Genome, 2001)

Modified California Roller for Measuring Transferable Residues on Treated Turfgrass - R. Fuller; D. Klonne; L. Rosenheck; D. Eberhart; J. Worgan; J. Ross (Bulletin of Environmental Contamination and Toxicology, 2001)

Nonsymbiotic hemoglobins in rice are synthesized during germination and in differentiating cell types - E. J. H. Ross; L. Shearman; M. Mathiesen; Y. J. Zhou; R. Arredondo-Peter; G. Sarath; R. V. Klucas (Protoplasma, 2001)

Amphibian Declines and Environmental Change: Use of Remote‐Sensing Data to Identify Environmental Correlates - Cynthia Carey; W. Ronald Heyer; John Wilkinson; Ross A. Alford; J. W. Arntzen; Tim Halliday; Laura Hungerford; Karen R. Lips; Elizabeth M. Middleton; Stan A. Orchard; A. Stanley Rand (Conservation Biology, 2001)
Populations of many amphibian species are declining worldwide, and a few species appear to have become extinct. In an attempt to evaluate the potential usefulness of remote‐sensing techniques as a tool for identifying the causes of these declines, we compiled a database that contains descriptions of 120 localities, both at which declines have been documented and at which no declines are yet known. The number of species involved, dates and degree of declines, habitat characteristics, and other factors are provided for each locality. Four relatively undisturbed areas in northeastern Australia, Costa Rica–Panama, central Colorado, and Puerto Rico were chosen for examination of environmental correlates coincident with mass mortalities at these localities. We used data predicted by models or collected by satellites, airplanes, or direct sampling on the ground to evaluate variations over time in temperature, precipitation, wind direction, UV‐B radiation, and concentrations of certain contaminants at these sites. We asked whether unusual changes in these environmental variables occurred either just in advance of or concurrent with dates of amphibian mass mortalities. The variation in certain environmental variables documented by others (Alexander & Eischeid 2001; Middleton et al. 2001; Stallard 2001 [all this issue]) appears unlikely to have directly caused amphibian deaths. But correlations between these environmental changes and the occurrence of amphibian die‐offs invite further investigation into synergistic interactions among environmental variables and possible indirect causal relationships.

Olfactory and behavioral response thresholds to odors of diseased brood differ between hygienic and non-hygienic honey bees ( Apis mellifera L.) - Masterman R.; Ross R.; Mesce K.; Spivak M. (Journal of Comparative Physiology A, 2001)

The crystal chemistry of synthetic potassium-bearing neighborite, (Na 1− x K x )MgF 3 - A. R. Chakhmouradian; K. Ross; R. H. Mitchell; I. Swainson (Physics and Chemistry of Minerals, 2001)

Pet Ownership and Childhood Acute Leukemia (USA and Canada) - Andrine R. Swensen; Julie A. Ross; Xiao Ou Shu; Gregory H. Reaman; Michael Steinbuch; Leslie L. Robison (Cancer Causes & Control, 2001)

A 48-h Larval Development Toxicity Test Using the Marine Polychaete Galeolaria caespitosa Lamarck (Fam. Serpulidae) - K. E. Ross, J. R. Bidwell (Archives of Environmental Contamination and Toxicology, 2001)

Feed-Forward Regulation of Gibberellin Deactivation in Pea - Robert C. Elliott; John J. Ross; Jennifer J. Smith; Diane R. Lester; James B. Reid (Journal of Plant Growth Regulation, 2001)

Size‐specific clearance, excretion, and respiration rates, and phytoplankton selectivity for the mussel Perna canaliculus at low levels of natural food - M. R. James; M. A. Weatherhead; A. H. Ross (New Zealand Journal of Marine and Freshwater Research, 2001)
Clearance, respiration, and ammonia excretion rates, and phytoplankton selectivity were measured for the Greenshell™ mussel Perna canal‐iculus (Gmelin) in Beatrix Bay, Marlborough Sounds, New Zealand. Functional equations were developed describing the relationship between body size (length and weight) and clearance and metabolic rates for this species feeding on natural food assemblages in New Zealand waters. Relationships with shell length were described by allometric power curves but the relationship with chlorophyll a concentrations in the water for a particular size of mussel suggested there was a threshold between 0.2 and 0.3 μg Chi. a litre −1 and an exponential decline in clearance rate from c. 0.5–0.6 μg Chi. a litre −1 with increasing chlorophyll concentrations. Under these field conditions ingestion rate would increase linearly with increasing chlorophyll concentrations up to c. 0.5 μg Chi. a litre −1 then remain constant at higher chlorophyll levels. Food levels, as measured by chlorophyll a or particulate carbon, were very low (generally a litre −1 and 300 μg C litre −1 ) throughout the study and this was reflected in low ingestion rates, despite clearance rates of up to 8.6 litre mussel 1 h −1 . P. canaliculus generally appears to be non‐selective, at least for phytoplankton in the size range 5–100 μm, but there was some evidence that larger diatoms and dinoflagellates were cleared more efficiently by larger mussels. Some of our observations on food levels and feeding rates help explain the low mussel growth and condition experienced in the Pelorus Sound during 1996–97.

Post-glacial population history and genetic structure of the northern clingfish ( Gobbiesox maeandricus ), revealed from mtDNA analysis - M. J. Hickerson; J. R. P. Ross (Marine Biology, 2001)

Elasticity of CaSnO 3 perovskite - J. Kung; R. J. Angel; N. L. Ross (Physics and Chemistry of Minerals, 2001)

Carbon and nitrogen pools and mineralization in a grassland gley soil under elevated carbon dioxide at a natural CO 2 spring - D. J. Ross; K. R. Tate; P. C. D. Newton; R. H. Wilde; H. Clark (Global Change Biology, 2000)
Summary The growth and chemical composition of most plants are influenced by elevated CO 2 , but accompanying effects on soil organic matter pools and mineralization are less clearly defined, partly because of the short‐term nature of most studies. Herein we describe soil properties from a naturally occurring cold CO 2 spring (Hakanoa) in Northland, New Zealand, at which the surrounding vegetation has been exposed to elevated CO 2 for at least several decades. The mean annual temperature at this site is ≈ 15.5 °C and rainfall ≈ 1550 mm. The site was unfertilized and ungrazed, with a vegetation of mainly C3 and C4 grasses, and had moderate levels of ‘available’ P. Two soils were present − a gley soil and an organic soil – but only the gley soil is examined here. Average atmospheric CO 2 concentrations at 17 sampling locations in the gley soil area ranged from 372 to 670 ppmv. In samples at 0–5 cm depth, pH averaged 5.4; average values for organic C were 150 g, total N 11 g, microbial C 3.50 g, and microbial N 0.65 g kg −1 , respectively. Under standardized moisture conditions at 25 °C, average rates of CO 2 ‐C production (7–14 days) were 5.4 mg kg −1 h −1 and of net mineral‐N production (14 −42 days) 0.40 mg kg −1 h −1 . These properties were all correlated positively and significantly ( P 2 concentrations, but not with soil moisture (except for CO 2 ‐C production) or with clay content; they were, however, correlated negatively and mainly significantly with soil pH. In spite of uncertainties associated with the uncontrolled environment of naturally occurring springs, we conclude that storage of C and N can increase under prolonged exposure to elevated CO 2 , and may include an appreciable labile fraction in mineral soil with an adequate nutrient supply.

Selective effects on NGFI-A, MR, GR and NGFI-B hippocampal mRNA expression after chronic treatment with different subclasses of antidepressants in the rat - Lisa Bjartmar; Inga-Maj Johansson; Jan Marcusson; Svante B. Ross; Jonathan R. Seckl; Tommy Olsson (Psychopharmacology, 2000)

Simulation Studies of Vestibular Macular Afferent-Discharge Patterns Using a New, Quasi-3-D Finite Volume Method - Muriel D. Ross; Samuel W. Linton; Bruce R. Parnas (Journal of Computational Neuroscience, 2000)

A General Method for Constrained Analysis of Fluorescence Anisotropy Decay: Application of the Steady-State Anisotropy - Edward L. Rachofsky; Barnabas Wolf; Carl N. Bialik; J. B. Alexander Ross; William R. Laws (Journal of Fluorescence, 1999)

Developing applications for lactococcal bacteriocins - R. Paul Ross; Mary Galvin; Olivia McAuliffe; Sheila M. Morgan; Maire P. Ryan; Denis P. Twomey; William J. Meaney; Colin Hill (Antonie van Leeuwenhoek, 1999)

Manipulation of S -adenosylmethionine decarboxylase activity in potato tubers - A. Rafart Pedros; M. R. MacLeod; H. A. Ross; D. McRae; A. F. Tiburcio; H. V. Davies; M. A. Taylor (Planta, 1999)

Lack of Association Between GBV-C Infection and Spontaneous Abortion - M. Roggendorf; R. S. Ross; C. A. Seemayer; K. R. Alberts; S. Viazov (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Immunization of rats reduces nicotine distribution to brain - Yoko Hieda; Dan E. Keyler; John T. VanDeVoort; R. Sam Niedbala; Donna E. Raphael; Cathy A. Ross; P. R. Pentel (Psychopharmacology, 1999)

CCG repeats in cDNAs from human brain - John J. Kleiderlein; Paul E. Nisson; Joel Jessee; W.-B. Li; K. G. Becker; Michael L. Derby; Christopher A. Ross; R. L. Margolis (Human Genetics, 1998)

Mixture in the distribution of haloperidol-induced oral dyskinesias in the rat supports an animal model of tardive dyskinesia - Takeshi Hashimoto; David E. Ross; Xue-Min Gao; Deborah R. Medoff; C. A. Tamminga (Psychopharmacology, 1998)

Approximate Analytical Solution of the Nonlinear Diffusion Equation for Arbitrary Boundary Conditions - J.-Y. Parlange; W. L. Hogarth; M. B. Parlange; R. Haverkamp; D. A. Barry; P. J. Ross; T. S. Steenhuis (Transport in Porous Media, 1998)

Relationships among species inCarex sect.Phyllostachys (Cyperaceae) based on allozyme divergence - Bruce A. Ford; Julian R. Starr; D. A. Ross McQueen; Robert F. C. Naczi (Plant Systematics and Evolution, 1998)

The impact of species-specific traits and phylogenetic relatedness on allozyme diversity inCarex sect.Phyllostachys (Cyperaceae) - Bruce A. Ford; D. A. Ross McQueen; Julian R. Starr; Robert F. C. Naczi (Plant Systematics and Evolution, 1998)

Mouse mammary tumor virus and its interaction with the immune system - Susan R. Ross (Immunologic Research, 1998)

Rapid isolation of muscle and heart mitochondria, the lability of oxidative phosphorylation and attempts to stabilize the process in vitro by taurine, carnitine and other compounds - Hans R. Scholte; Yihong Yu; John D Ross; Imma I. Oosterkamp; Adriana M.C. Boonman; Herman F.M. Busch (Molecular and Cellular Biochemistry, 1997)

Distribution of parvalbumin isotypes in adult snook and their potential applications as species‐specific biomarkers - C. Ross; R. W. Tilghman; J. X. Hartmann; F. Mari (Journal of Fish Biology, 1997)
The highly stable Ca 2+ binding protein, parvalbumin, is prevalent in fish white muscle tissue. The properties of this protein make it a promising antigen for use as a specific biomarker for fish identification. Parvalbumin was purified from white muscle of an adult common snook Centropomus undecimalis using ammonium sulfate precipitation, size‐exclusion chromatography (SEC) and anion‐exchange HPLC. Parvalbumins were characterized by the presence of an 11‐kDa band following gradient‐SDS gel electrophoresis and by their immunoreactivity against mouse anti‐parvalbumin antibodies. Anion‐exchange chromatography of the parvalbumin fraction separated from the SEC column yielded nine fractions. Subsequent analysis of these fractions by isoelectric focusing gel electrophoresis led to a total of seven parvalbumin isotypes, which may lend themselves as biomarkers in fish identification. The presence of these seven parvalbumin isotypes was confirmed independently by reversed‐phase HPLC. A dilution endpoint immunoassay was developed for C. undecimalis parvalbumin using a monoclonal antibody directed against its highly conserved calcium binding site. The utility of parvalbumin isotype distribution and specific monoclonal antibodies against fish parvalbumin in species identification is discussed.

Southern analysis for detection of CAG repeat expansions associated with dentatorubral pallidoluysian atrophy - R. L. Alford; R. L. Margolis; C. A. Ross; C. S. Richards (Human Genetics, 1997)

Negative effects of ant foraging on spiders in Douglas-fir canopies - J. Halaj; D. W. Ross; A. R. Moldenke (Oecologia, 1997)

The pterin lumazine inhibits growth of methanogens and methane formation - Kesava R. Nagar-Anthal; Veronica E. Worrell; Ross Teal; D. P. Nagle (Archives of Microbiology, 1996)

Inertial properties of the human trunk of males determined from magnetic resonance imaging - D. J. Pearsall; J. G. Reid; R. Ross (Annals of Biomedical Engineering, 1994)

Family pesticide use and childhood brain cancer - James R. Davis; Ross C. Brownson; Richard Garcia; Barbara J. Bentz; Alyce Turner (Archives of Environmental Contamination and Toxicology, 1993)

Updated listing of potato species names, abbreviations and taxonomic status - Z. Huamán; R. W. Ross (American Journal of Potato Research, 1985)

Isolation of polysaccharide antigens from the cell wall of group B Streptococcus, Type Ib - C. G. Cumming; P. W. Ross; I. R. Poxton (Antonie van Leeuwenhoek, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

The effects of ultraviolet and ionizing radiation on herpesviruses, SV 40 and adenoviruses in relation to the small-plaque effect - K. R. Cameron; Lesley M. Tomkins; R. P. Eglin; L. J. N. Ross; P. Wildy; W. C. Russell (Archives of Virology, 1979)

Klinik und Therapie einer erfolgreich behandelten, schweren Bromisovalerianylcarbamid-, Methaqualon- und Meprobamat-Vergiftung bei einem 12 Jahre alten Kind - F. Schindera; R. Gädeke; C. Ross; H. Höhmann; K. D. Pohl; M. Sauer; W. Bischoff (Archives of Toxicology, 1973)

A rapid method for the determination of sulphur dioxide in sulfited potato flakes - L. R. Ross; R. H. Treadway (American Journal of Potato Research, 1972)

Objective measurement of texture variables in raw and processed French fried potatoes - L. R. Ross; W. L. Porter (American Journal of Potato Research, 1971)

Lester Carl Peterson 1914–1970 - G. C. Kent; R. L. Plaisted; A. F. Ross (American Journal of Potato Research, 1970)

Objective measurements of french fried potato quality. Laboratory techniques for research use - L. R. Ross; W. L. Porter (American Journal of Potato Research, 1969)

Utilizing the frost resistance of diploid solanum species - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1969)

Interpretation of multiple-peak shear force curves obtained with French fried potatoes - L. R. Ross; W. L. Porter (American Journal of Potato Research, 1968)

Preliminary studies on application of objective tests to texture of French fried potatoes - L. R. Ross; W. L. Porter (American Journal of Potato Research, 1966)

Frost resistance among theSolanum species in the ir-1 potato collection - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1965)

A new and rapid method for determining fat in French fried potatoes - L. R. Ross; R. H. Treadway (American Journal of Potato Research, 1962)

Factors affecting the sulfur dioxide uptake in sulfited pre-peeled potatoes - L. R. Ross; R. H. Treadway (American Journal of Potato Research, 1961)

A rapid method for the determination of sulfur dioxide in sulfited pre-peeled potatoes - L. R. Ross; R. H. Treadway (American Journal of Potato Research, 1960)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

The use of foreign introductions in breeding American potato varieties - R. W. Hougas; R. W. Ross (American Journal of Potato Research, 1956)